Construction of Ni3S2/NiFe-LDH heterostructure via in-situ sulfidation for enhanced electrocatalytic urea oxidation with overall water splitting - Feng Fu; Min Wang; Jili Ren; Jindou Hu; Zhenjiang Lu; Jing Xie; Yali Cao (Fuel, 2027)

Artificial intelligence and digital sensing for multiscale soil structure: from observation to decision-making - Yongwei Fu; Hu Zhou; Joshua Heitman; Budiman Minasny; Tusheng Ren; Baoguo Li; Andrew Binley; Zhuangji Wang; Robert Horton (Computers and Electronics in Agriculture, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Precipitation chemistry in a semi-arid city: Insights from the driving factors of acidity - Dongqi Chen; Bing Sun; Haijun Zhou; Wenjing Sun; Huifang Ren; Ying Sun; Xiaoqin Zhao; Xiaotao Fu; Zhonghua Li (Atmospheric Research, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Single-cell transcriptomics reveals heterogeneous stress responses and Mg2+-mediated survival mechanisms in Lactobacillus delbrueckii subsp. bulgaricus during freeze-drying and storage - Liang Liu; Jing Ren; Zhongxia Li; Xinyue Hao; Can Di; Zixin Fu; Liang Li; Xiaolei Ze; Ruikun He; Lanwei Zhang; Pimin Gong (Food Research International, 2026)

High-performance Ti3C2-mediated adsorptive membrane for selective lithium recovery from shale gas wastewater - Dandan Zhao; Feiyang Yuan; Yuchun Ren; Yan Li; Keji Zhou; Xiaoying Huang; Chen Fu; Zhengjun Gong (Desalination, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Hydrology–topography controls on biomass responses of emergent wetland plants to drought and flooding in a Yangtze River-connected floodplain wetland - Jiawei Shi; Kerun He; Lianlian Xi; Yining Xia; Peng' ao Liu; Zenghui Peng; Hui Fu; Guixiang Yuan; Yonghong Xie; Youzhi Li; Bo Ren (CATENA, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Object preference versus novelty preference: The importance of object selection and recommendations for the Novel Object Recognition test in mice - Yuan Yuan; Jing Li; Xiaoying Gu; Shuangshuang Ye; Yuanze Li; Zhuangfei Chen; Ping Ren; Yu Fu (Applied Animal Behaviour Science, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Optimized straw–nitrogen management enhances crop yield, soil carbon sequestration, and economic returns in dryland maize systems of Northwest China - Yunfei Ren; Jiayi Li; Fu Liu; Longchuang Zhang; Xiu Chen; Haibo Hu; Xiaoyu Ning; Yeye Zhang; Jinxia Wang; Xiaozhou Li; Shuangguo Zhu; Fei Mo (Soil and Tillage Research, 2026)

Sedimentary characteristics and palaeo-ocean environment evolution of the Hejiazhai Formation in the early Tonian Period, Western Henan - Boyang Xu; Deshun Zheng; Qianqian Li; Sha Ren; Fengbo Sun; Jiaqi Fu; Xin Wang; Wentong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Molecular-level source contribution of dissolved organic matter in a typical plateau lake using end-member mixing analysis based on spectroscopic, stable isotope and molecular fingerprint - Yunxuan Cheng; Shasha Liu; Rui Fu; Yi Ren; Yuxuan Zhang; Ziwen Yin; Fengchang Wu (Journal of Hydrology, 2026)

Physics-constrained neural network modeling of soil thermal conductivity curve across full saturation - Yongwei Fu; Lingzao Zeng; Hu Zhou; Joshua Heitman; Tusheng Ren; Robert Horton (Journal of Hydrology, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Design of dual-function soil amendment via co-roasting K-feldspar with soda residue and oyster shell for acidity amelioration and potassium supply - Ernest Uwiringiyimana; Ren-Yong Shi; Jiu-Yu Li; Jia-Ning Gao; Yong-Ming Fu; Md. Romel Biswash; Cong-Ming Wu; Ren-Kou Xu (Journal of Environmental Chemical Engineering, 2026)

Preparation and performance analysis of a novel composite dust suppressant considering wind and train vibration effects - Hao-kui Wang; Ming-yi Chen; Zi-ting Pei; Fu-chao Tian; Yue Ren; Xing-jun Ma; Ming-xin Li (Journal of Environmental Chemical Engineering, 2026)

Integrated photoelectrocatalytic reduction and oxidation processes to achieve efficient degradation of fluoxetine in pharmaceutical wastewater - Yanpeng Liu; Zixiao Zhu; Miao Ren; Jingyi Fu; Bo Yang; Xu Zhao (Journal of Environmental Sciences, 2026)

β-Cyclodextrin-mediated co-encapsulation of peptide PPHG and gallic acid: Synergistic thrombin-inhibitory activity, enhanced stability, and sustained simulated gastrointestinal release - Zi-Han Qu; Zi-Han Liu; Xue-Fu Li; Hai-Bin Ren; Di-Feng Ren; Jun Lu (Food Bioscience, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

From structural limitations to modification strategies: A review of Prussian blue analogs electrode for efficient and stable capacitive deionization - Haiyun Ding; Zhiqiang Wu; Hao Zhou; He Ren; Hao Fu; Chuanyan Li; Jun Yang (Desalination, 2026)

A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

Micro-scale confinement-mediated green synthesis of carbon dots retaining the intrinsic fluorescence of biomass - Fu Qin; Jianliang Bai; Guohui Yang; Mingxing Zhang; Xu Yu; Jiawen Shang; Xiaohai Cui; Xiaoyue Wang; Lili Ren (Chemical Engineering Journal, 2026)

How grazing intensity modulates precipitation driven processes of soil moisture, nutrients, and microbially mediated carbon cycling in a desert steppe - Xu Li; Wenling Fu; Yang Chen; Dandan Chen; Xin Li; Xiaoqian Li; Tianming Gao; Jianying Guo; Xinchuang Chen; Yiqun Ren; Zhi Dong (CATENA, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Promoting mechanism of weathered coal on methane production from anaerobic digestion of pig manure - Hongyu Guo; Yuanbo Dou; Xiao Zhou; Wen Fu; Hengxing Ren; Changjiang Ji; Lijiao Yue; Shufeng Zhao; Shuaishuai Xu (Biomass and Bioenergy, 2026)

Balancing N₂O and NH₃ emissions with maize yield: Investigating the role of alternate drip irrigation and 3,4-dimethylpyrazole phosphate (DMPP) - Junming Liu; Yuanyuan Fu; Le Yang; Zhuanyun Si; Sunusi Amin Abubakar; Huijie Li; Tao Zhou; Ruiqi Ren; Hongchen Li; Peng Li; Bingcheng Si; Yang Gao; et al. (Soil and Tillage Research, 2026)

Numerical investigation on hydrodynamic interference in parallel water entry of vehicles with deflection angles - Xiao-Qiang Chen; Jia-Jie Wang; Chang Liu; Meng-Chao Zhang; Fu-Ren Ming (Ocean Engineering, 2026)

Enhanced PM filtration and self-adaptive oxygen supply by intelligent powered respirators under extreme conditions with high dust and low oxygen - Jintuo Zhu; Wei-Wei Huang; Xuejing Liu; Bo Ren; Yunhui Nie; Dayong Fu; Weihua Zhu; Wenjie Fan; Liang Wang; Yuzhen Hou; Huan Xu (Journal of Hazardous Materials, 2026)

Triclosan induces cardiac malformations via an estrogen receptor–ERK–mitochondrial apoptotic signaling axis in zebrafish embryos - Jing Fu; Jin Chen; Yaolin He; Wenzhuo Li; Jing Ren; Yongkang Shen; Ningman Tang; Anfei Liu; Yi Gao; Ming Huang; Zhenzhong Liu (Journal of Hazardous Materials, 2026)

pH and polyphenol-controlled release dual-responsive intelligent hydrogel absorbent pad strategy: methylcellulose‑sodium alginate and anthocyanin@MOFs for chilled pork preservation - Yanpei Huang; Conghui Lang; Fei Ren; Jinsheng Fu; Shengmin Liu; Chuang Zhang; Kai Shan; Chunbao Li; Wenxue Chen; Ming Zhang; Qiujin Zhu; Haiming Chen (Food Research International, 2026)

Mixed planting of Eucalyptus with native tree species enhances soil enzyme activity by optimizing bacterial co-occurrence network connectivity - Daihan Fu; Yuxing Xu; Shiqi Ren; Zhichao Wang; Wankuan Zhu; Runxia Huang; Apeng Du (Forest Ecology and Management, 2026)

Hyperoside-based self-assembled hydrogel for modulating osteoimmune microenvironment to combat bacterial infections and facilitate bone repair - Xiang Gao; Xiaojing Zhang; Hang Liu; Xinwei Fu; Tao Zhang; Xiao Liang; Yifan Ren; Xingyu Yang; Xinliang Peng; Liqun Xu; Prasathkumar Murugan; Yuejun Kang; et al. (Chemical Engineering Journal, 2026)

Thrombin-triggered in situ anchoring of a biomimetic bilayer scaffold synergizes with PRP to promote osteochondral regeneration - Zijian Yan; Yongan Lin; Jiayi Chen; Ruibin Lin; Zhuhao Tan; Yunqi Fu; Feifan Luan; Chenxiao Zheng; Li Ren (Chemical Engineering Journal, 2026)

Mapping Whole-Brain Nonlinear Structure-Function Dynamics in Aging via Neural Granger Causality - Meng Niu; Shanli Ren; Chen Lin; QingChen Wang; Yongzhi Yin; Hanning Guo; Yu Fu (Brain Topography, 2026)

How has Shanghai built a sustainable municipal solid waste management system through 30 years of socio-ecological practice? - Xiangyu Ren; Kgosietsile Velempini; Jun Tai; Bitian Fu; Yue Che (Socio-Ecological Practice Research, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Probing the sound speed and clustering of dark energy - Yuhang Yang; Qingqing Wang; Xin Ren; Emmanuel N. Saridakis; Yi-Fu Cai (Science Bulletin, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Numerical investigation of dynamic response of HDPE raft-cage aquaculture systems under combined wave-current conditions: Multi-System coupling analysis - Fei Fu; Xiaoying Zhang; Zhanbin Meng; Di Ren; Xiangxi Han; Jianxing Yu; Zhe Hu (Ocean Engineering, 2026)

A specific strategy for accelerating strength-development rate of self-generated proppants: the gel effect related autoacceleration - Xianyan Ren; Zhenyong Li; Yating Chen; Xiaoji Fu; Yirui Zhang; Dan Fang; Xirui Chen; Cheng Bian (Fuel, 2026)

Caffeic acid-grafted high-amylose maize starch for self-stabilizing emulsion gels: efficient encapsulation and protection of pterostilbene - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Food Chemistry, 2026)

Deciphering Er3+ energy level population in La2Sn2O7 nanocrystals via tailored short-range energy transfer for multidimensional applications - Jiamei Ren; Bin Duan; Kejie Li; Jiaqi Zhao; Dongxu Guo; Ruiying Lu; Tianqi Sheng; Zuoling Fu (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

From biomarkers to the risk index: a novel integrated model using multidimensional urinary biomarkers to quantify e-cigarette exposure - Lili Cui; Shulei Han; Pengpeng Yu; Ruijuan Miao; Xingfang Cun; Yuan Zhang; Peipei Ren; Pengxia Feng; Lingxiao Song; Yaning Fu; Hongjuan Wang; Yushan Tian; et al. (Archives of Toxicology, 2026)

Spatiotemporal variability of turbulent stress and the mean longshore current driven by instabilities - Chunping Ren; Zhanhao Zhang; Nannan Fu; Baolei Geng; Minghan Huang (Acta Oceanologica Sinica, 2026)

Analysis, isolation and anti-tumour activity of the alkaloids from Ceratocarpus arenarius L - Aimulaguli Kuerban; Hanghang Fu; Yanni Ma; Dongyu Lei; Xingyu Ren; Lu Jin; Le Pan (Natural Product Research, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

Acceleration of Fe2+/Fe3+ cycle in core-shell MIL-88A(Fe)@1T-WS2 heterojunction to promote peroxymonosulfate activation for phenol degradation - Dachao Yan; Hongjin Chen; Ning Fu; Guanguo Zhang; Yuxiang Chen; Peng Wang; Shuai Guo; Xuechang Ren (Process Safety and Environmental Protection, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Symbiotic chlorine-resistant bacteria and fungi in urban building drinking water plumbing pipe biofilms - Zhen-Ning Luo; Tian-Yang Zhang; Huan He; Ren-Jie Pan; Yun-Qiao Zeng; Zhu Peng; Jun Shi; Qi Fu; Minyuan Pan; Chao Zeng; Qian Xiao; Ling Hu; et al. (Journal of Hazardous Materials, 2026)

Enhanced electroosmosis-induced delivery of persulfate for remediation of PAHs contaminated soil via time-modulated electric fields: A novel zoned processing concept - Dongdong Wen; Yuhuan Zhu; Junxian Wang; Yuqing Ren; Wei Teng; Jian Hu; Yajun Zhang; Rongbing Fu (Journal of Hazardous Materials, 2026)

Sources of total and dissolved aerosol iron at Xi’an, Northwest China: implications for solubility of aerosol iron from different sources - Yizhu Chen; Tianyu Zhang; Zhenyu Wang; Zhenming Zhu; Yifan Zhang; Mingyuan Liu; Fu Wang; Yan Ren; Guoliang Shi; Guohua Zhang; Xinming Wang; Mingjin Tang (Journal of Environmental Sciences, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Mechanism-based inactivation of CYP2D6 by imperatorin and drug-drug interaction in vitro and in vivo - Hualu Wu; Lu Cao; Peiqi Wang; Ruibin Li; Jun Wu; Haoxin Fu; Yan Chen; Shiqi Jiang; Ren-ai Xu (Archives of Toxicology, 2026)

Surface wave tomography reveals potential ice-bedrock interaction in the Larsemann Hills, East Antarctica - Changcheng Li; Lei Fu; Zhengbo Li; Kun Luo; Sheng Dong; Hengxin Ren; Xiaofei Chen (Science China Earth Sciences, 2026)

Prenatal Cerium Exposure and Neural Tube Defect Risk: A Case-control Study in Shanxi, China - Jing Wei; Fuyuan Yin; Zuqun Jin; Ning Kang; Dezheng Fu; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Aiguo Ren; Shengju Yin (Biological Trace Element Research, 2026)

Salt cavern identification method based on spectrum decomposition of matching pursuit algorithm - Ping Ren; Ya-ping Huang; Dong-lin Zhou; Si-han Luo; Jian-fu Wang; Jia-hao Yan; Shao-hua Liu; Zhi-feng Shi (Applied Geophysics, 2026)

Atmospheric radioactive emissions from coal-fired power plants in China under green and low-carbon transition: Historical evolution and projected decline - Zhiqiang Fu; Zhongling Guo; Xinchen Liao; Zehui Yao; Junqi Yang; Jiahao Ren; Xuehan Li; Weiyi Fan; Hezhong Tian (Resources, Conservation and Recycling, 2026)

Degradation of bisphenol A using a three-dimensional electrochemical reactor: Synergistic effects of H2O2 and mechanistic insights - Xu Ren; Lin Chen; Haifeng Fu; Meng Shen; Kai Song; Qiang Ma; Xin Peng (Process Safety and Environmental Protection, 2026)

Experimental investigation on near and far wake interference of two flexible pipes with a tandem arrangement in bidirectionally sheared flow - Shunzhao Cheng; Haojie Ren; Shixiao Fu; Hao Ren; Liang Guo; Mengmeng Zhang (Ocean Engineering, 2026)

Spin-state engineering via ionic mismatch in MnO2 for high-performance hybrid capacitive deionization - Xiaoke Li; Jinghua Yang; Xuejing Wang; Shiyu Wang; Jingyu Wu; Ruilong Liu; Guixi Wang; Jun Wang; Weikun Ren; Feike Zhang; Weijie Fu; Yingjie Ji; et al. (Desalination, 2026)

Wearable and breathable double-sided alginate/silk fibroin aerogel-nanofiber-based flexible sensor for personal thermal management and distinguishable multimodal sensing applications - Yu Fu; Peng Liu; Zhenshuai Wan; Ye Tian; Peng Wang; Chong Liu; Peng Sun; Shaoshuai Li; Dengjie Zhu; Caixia Ren (Chemical Engineering Journal, 2026)

Rapid cooling of lithium-ion battery thermal runaway achieved by high-silica fabric based on dual-functional fire-extinguishing microcapsule coating - Yijun Ren; Zihao Zhao; Chenxi Wang; Chen Li; Jiachao Zhang; Peng Zhang; Jijie Fu; Fangsheng Huang; Zhiqiang Zhu (Chemical Engineering Journal, 2026)

Molybdenum isotopes in metamorphic and magmatic rocks may record substantial fluid activity in continental subduction zones - Wei Fang; Li-Qun Dai; Ren-Xu Chen; Zi-Fu Zhao (Chemical Geology, 2026)

The mechanistic nexus between microplastics and chronic liver disease: A review of current evidence - Shiyun Pu; Changyu Ren; Jiao Liu; Jingyi Zhang; Yan Wang; Ke Fu; Tong Wu (Chemico-Biological Interactions, 2026)

Medicinal seahorses (Hippocampus spp.) for Alzheimer’s disease within species conservation framework: an integrated review of ethnopharmacology, bioactivity, bibliometrics, and network pharmacology - Peng Song; Mengyu Wang; Tao Liu; Zhuoqing Zhang; Xia Ren; Yao Liu; Jerome P. L. Ng; Vincent Kam Wai Wong; Betty Yuen Kwan Law; Xianjun Fu; Liqun Qu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of β-carotene hydroxylase gene from Limnospira platensis: expression in Escherichia coli for the production of zeaxanthin - Zhen-Wei Shi; Liu-Yu Jian; Jun Ma; Xue-Fu Li; Li-Jie Peng; Di-Feng Ren (Journal of Applied Phycology, 2026)

Fish community and its relationships with environmental factors in the Jiupan River, a secondary tributary of the Three Gorges Reservoir - Junquan Ren; Zhenxin Chen; Kaiyang Wu; Lilong Chen; Rongchao He; Mengqiao Long; Yankun Shen; Hanlin Wang; Mei Fu; Hongjian Lv; Weizhi Yao (Environmental Biology of Fishes, 2026)

An ultrasensitive electrochemical immunosensor for SLC2A3 detection enables prognostic prediction in acute ischemic stroke - Yu Ren; Qing Fu; Juncheng Huang; Chengying Du; Juanjuan An; Qin Yang; Du Cao (Analytica Chimica Acta, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Cuproptosis: a novel mechanism and 3PM-oriented therapeutic strategy for cancer - Ding Yang; Wei-Ting Hu; Miao Li; Fang-Qing Shen; Hao-Yu Wang; Jin-Ying Ye; Fu-Lu Ren; Yun Wang (EPMA Journal, 2026)

A review of antibiotic treatment by bioelectrochemical systems: Degradation mechanisms, resistance gene control, and hybrid technologies - Hexing Li; Hong-Yu Ren; Qiang Fu; Tianxiao Li; Fanying Kong (Process Safety and Environmental Protection, 2026)

Spatially compartmentalized dual-epitope engineering: A strategy for multilayered plant defense - Xiumei Luo; Ramesh Raju Vetukuri; Kerimaliev Janybek; Zheng Qing Fu; Maozhi Ren (Molecular Plant, 2026)

Material proportion guided hyperspectral image super-resolution via unmixing - Yinghao Xu; Xuanwen Tao; Zihao Ni; Zonghua Liu; Yimin Fu; Peng Ren (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Flavor characterization of Chenxiang-type baijiu-Daoguang nianwu aged in wooden Jiuhai with different vintages integrating GC-E-nose, GC-IMS, GC-MS-O, ROAV and chemometrics approaches - Na Wang; Xiangyang Zhang; Li Xue; Zhen Zhang; Li Fu; Xuejiao Ren; Hui Zhang; Bo Zhang; Xiaoyu Jiang; Lili Zhang; Mei Wang (Food Research International, 2026)

Lactiplantibacillus plantarum ZJUIDS51 improves androgenic alopecia via gut-skin axis - Jinfeng Fu; Yanghui He; Lulu Qiao; Zeyu Wu; Yuan Wei; Eng Huan Hau; Ying Xiao; Daxi Ren (Food Research International, 2026)

Volatile metabolomics and Metaproteomics reveal key flavor formation mechanisms in mixed-culture fermented Rice slurry - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Research International, 2026)

Suppression of lipid oxidation in frozen unwashed surimi by polyphenols-extract of foods: Investigating the synergistic mechanism of targeting hemoglobin and key radical-producing enzymes - Guiyuan Xiang; Jiangtao Li; Zhao Long; Jianan Zhang; Xiangjin Fu; Tianqing Lan; Kangzi Ren; Amna Jabeen (Food Bioscience, 2026)

38 years of micronutrient fertilization, particularly copper, enhance winter wheat yield during drought on the Loess Plateau without yield penalties - Xiaozhou Li; Fu Liu; Yunfei Ren; Jinxia Wang; Haibo Hu; Shuangguo Zhu; Fei Mo (Field Crops Research, 2026)

Development and hypermobility of the Basu rock avalanche in the Nu River ophiolitic mélange, southeastern Tibetan Plateau - Yunjian Gao; Jianhui Deng; Siyuan Zhao; C.F. Lee; Xin Yao; Fuchu Dai; Stuart Lane; Yongbo Tie; Kaiyu Ren; Fei Wang; Ziguo Fu (Engineering Geology, 2026)

Surface-engineered Mn–Prussian Blue analogue with dual redox centers for high-performance hybrid capacitive deionization - Jianeng Ji; Jun Yang; Zhiqiang Wu; He Ren; Hao Fu; Chunyan Li; Minjie Shi; Edison Huixiang Ang (Chemical Engineering Journal, 2026)

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

A novel Pickering emulsion stabilized solely by n-butyric acid-modified high-amylose corn starch for resveratrol delivery - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Qisheng Tian; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Carbohydrate Polymers, 2026)

Research on performance differences and mechanisms of sulfur-iron composite packing materials prepared from different iron sources in nitrogen and phosphorus removal from wastewater - Dejun Wang; Ziyao Ren; Weizhang Fu (Bioresource Technology, 2026)

Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

A review for bioactive peptides from oyster: functional properties, structure-function relationships and challenges - Zihan Zheng; Jiongqi Lin; Dongmei Li; Zhanming Li; Caili Fu; Zhongyang Ren (Trends in Food Science & Technology, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Secondary metabolites from the endophytic fungus Hypoxylon sp. HK-37 derived from Aquilaria sinensis - Zheng-Zhuo Ren; Kai-Lei He; Fei Wu; Li Yang; Jing-Zhe Yuan; Ze-Sheng Li; Hao-Fu Dai; Wen-Jian Zuo; Hui-Qin Chen (Phytochemistry Letters, 2026)

Accelerated degradation of antibiotics via UV irradiation in the presence of chlorite: roles of reactive species, degradation pathways, and toxicity - Yu-qiong Gao; Xue-ting Ren; Yang-yang Liu; Ju-xiang Chen; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2026)

Unlocking the promotion mechanism of cerium in Ni-based hydrotalcite catalysts for enhanced CO2 methanation - Jie Ren; Lei Huang; Tongqi Ye; Fu Wei; Shenjie Li; Yanyan Chen; Yanqing Wang; Feng Zeng; Jing-Pei Cao; Maofeng Zhang (Fuel, 2026)

Synchronous enhancement of radical and non-radical pathways in Fenton-like reaction mediated by CuCo bimetallic heterostructure - Jing Zhang; Yating Fu; Ye Liu; Yi Ren; Xingxing An; Bo Lai (Chemical Engineering Journal, 2026)

Time-dependent dynamics of starch structure, functionality and quality in rice noodles during inoculated fermentation - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Carbohydrate Polymers, 2026)

Bioinspired nanocellulose-based ultrathin hydrogel bioadhesives with sweat-resistant properties - Boshi Feng; Juanli Shen; Jinlong Zhang; Junli Ren; Xiaohong Liu; Shiyu Fu (Carbohydrate Polymers, 2026)

Transcriptomic and Physiological Insights into GA₃-Mediated Regulation of Fruit Abscission in Lonicera Caerulea L - Kailin Shao; Jing Chen; Bingbing Ren; Dong Qin; Xueting Wang; Chunlin Fu; Ran Gu; Jiacheng Li; Zhonglin Jia; Zhenyu Li; Junwei Huo; Huixin Gang (Journal of Plant Growth Regulation, 2026)

Unraveling the halotolerant degradative machinery of Candida tropicalis JH: a novel biocatalyst for sustainable treatment of hypersaline azo dye effluents - Jiahui Ren; Haiyun Zhang; Bingwen Xu; Xinmei Fu; Liang Tan (World Journal of Microbiology and Biotechnology, 2026)

Anti-inflammatory diterpenoids from the wasp nest ( Nidus vespae ) of Vespula vulgaris against MSU-induced inflammation in Raw264.7 cells - Zhiling Yao; Tao Liu; Leyi Fu; Zitian Peng; Liju Zhang; Zhe Ren; Zhiping Wang; Xiaofei Zheng; Yifei Wang (Natural Product Research, 2026)

A new generation of embodied intelligent plant protection unmanned vehicle integrated with hydrostatic transmission and four-wheel drive technology: design, development and application - Zhigang Ren; Jian Chen; Mingjiang Sun; Renzhong Fu (Computers and Electronics in Agriculture, 2026)

Assessing road network resilience to extreme rainstorms: A percolation and hydrodynamic approach - Fei Ma; Rong Fu; Wei Ren; Qing-Chang Lu; Qing Liu; Zhijie Yang; Zhong Ma (Transportation Research Part D: Transport and Environment, 2026)

Sulfur vacancies in Z-scheme ZnS/MIL-88A(Fe) heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced OFX degradation - Xuechang Ren; Bowen Zheng; Xingyu Liu; Hongjin Chen; Deze Yang; Zhongshan Li; Ning Fu; Yong Zhang (Process Safety and Environmental Protection, 2026)

Social-economic-natural complex ecosystem (SENCE) theory and its application: Historical contributions and future prospects - Hua Zheng; Liding Chen; Weiqi Zhou; Ranhao Sun; Guangyao Gao; Weihua Xu; Shuai Wang; Chuanbin Zhou; Xiaoming Feng; Yajuan Shi; Yi Xiao; Lingqiao Kong; et al. (Journal of Environmental Sciences, 2026)

Advancements in metal-organic frameworks for alkaline oxygen evolution reaction: mechanistic insights, catalyst stability and applications - Ruo-Jin Liu; Xue-Ying Yang; Zheng-Yi Wu; Na Xu; Fu-Li Wang; Ren-Qing Lv; Guanqun Han; Bin Dong; Yong-Ming Chai (Fuel, 2026)

Construction of a novel Mn3O4/NiCo2S4 composite catalyst for enhanced peroxymonosulfate activation toward rapid degradation of ofloxacin: Mechanistic and toxicity assessment - Xuechang Ren; Zhongshan Li; Duxudong Huang; Deze Yang; Bowen Zheng; Jianzhao Wang; Ning Fu (Environmental Research, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Solar-driven one-pot synthesis of freezing-tolerant and self-healing nanocellulose eutectogels for sustainable flexible electronics - Chaoqiang Fu; Sanwei Hao; Jun Yang; Jifei Zhang; Jialong Wen; Wenfeng Ren; Bing Wang; Ling-Ping Xiao; Changyou Shao; Runcang Sun (Chemical Engineering Journal, 2026)

Bioinspired optical/electrical dual-modal flexible strain sensor with microcrack structure based on fluorescent hydrogel - Dingkun Wang; Guoqi Chen; Canjie Zhu; Jiayuan Ren; Yang Cong; Hailong Yang; Jun Fu (Chemical Engineering Journal, 2026)

Effects of dietary nanoplastics exposure on muscle quality, immunity, antioxidative capacity and digestive gland function of abalone (Haliotis discus hannai) - Jiping Zhang; Qiyuan Fu; Sisi Cheng; Hai Ren; Ye Mu; Jiahuan Liu (Aquatic Toxicology, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Chiral Ratiometric Fluorescent Silicon Nanoparticles for “Turn-on” Enantioselective Recognition of Tryptophan - Chen Liu; Yaning Duan; Cancan Lu; Yu Fu; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Hollow NiCo₂S₄ microspheres synergistically promote peroxymonosulfate activation for efficient ofloxacin degradation: Performance, mechanism and degradation pathways - Zhongshan Li; Xuechang Ren; Guanguo Zhang; Duxudong Huang; Gongrong Chen; Huiying Lei; Yaoling He; Ning Fu (Journal of Water Process Engineering, 2026)

Two-layer dynamic flood risk analysis model for real-time flood control operation of a multi-reservoir system - Jieyu Li; Zhihui Ren; Gang Liu; Weifeng Liu; Jisi Fu; Qingwen Lu (Journal of Hydrology, 2026)

Transboundary transport of organophosphate esters from Nepal to the Tibetan Plateau: Sources, distribution, and monsoon-driven pathways - Yiyao Pan; Yifan Chen; Chengzheng Ouyang; Qianchen Fu; Wenqiang Ren; Honghua Li; Ruiqiang Yang; Qinghua Zhang; Guibin Jiang (Journal of Hazardous Materials, 2026)

A new method for constructing dynamic-static conversion models for rock mechanics based on acoustic wave propagation characteristics - Sheng Wang; Kaizhou Xu; Haixue Wang; Xiaofei Fu; Chengxuan Ren (Journal of Applied Geophysics, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Self-assembly of bayberry-like porous BiVO4 nanospheres for self-powered marine underwater optical communication - Ping Wang; Shuai Ren; Kun Fu; Yizhou Lv; Yayue Wang; Ping Rong; Weipeng Chen; Jianhua Zhang; Xifei Li; Qi Yu (Chemical Engineering Journal, 2026)

Tracing fertilizer transformation and leaching in karst soils via soil column experiments and nitrogen isotopes - Ping Zhang; Yi-Meng Ren; Xiao-Dan Wang; Fu-Jun Yue (CATENA, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Calcium carbonate modified Biochar ameliorates acid soil properties and promotes soybean growth - Ren Hu; Limin Wang; Jun Zhu; Wenfeng Tan; Mingyue Gao; Qingling Fu; Hongqing Hu; Zaryab Murad (Journal of Soils and Sediments, 2026)

Chemical armed allies promote plant resistance to pathogen: The contribution of arbuscular mycorrhizal fungi to an invasive weed - Shanshan Qi; Zhixiang Shu; Misbah Naz; Ying Li; Ruike Zhang; Guangqian Ren; Deli Zhai; Wei Wei; Weiguo Fu; Zhicong Dai; Daolin Du (Mycorrhiza, 2026)

Effects of land-use change on soil total carbon pool: a meta-analysis - Zhuobing Ren; Changjia Li; Shuai Wang; Wenxin Zhou; Lindsay C. Stringer; Bojie Fu (Agriculture, Ecosystems & Environment, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Exploring the impacts of flavonoid compounds on escitalopram metabolism: a combined in vitro and in vivo study - Hailun Xia; Jun Wu; Haoxin Fu; Peiqi Wang; Ruibin Li; Lu Cao; Ya-nan Liu; Lu Shi; Ren-ai Xu (Molecular Diversity, 2026)

Arching patterns in compacted clay: insights from plane-strain trapdoor tests - Xiang-Shen Fu; Han-Lin Wang; Zi-Jian Zhai; Ren-Peng Chen; Daniel Dias (Transportation Geotechnics, 2026)

Evolutionary mechanism of passive soil arching effect in sand at various relative densities and heights of fill - Han-Lin Wang; Zi-Jian Zhai; Xiang-Shen Fu; Xiao-Hu Zhang; Daniel Dias; Ren-Peng Chen (Transportation Geotechnics, 2026)

Corrigendum to “Chlorpyrifos induces placental oxidative stress and barrier dysfunction by mediating mitochondrial apoptosis via ERK/MAPK signaling pathway: In vitro and in vivo studies” [Sci. Total Environ. 903 (2023), 166449] - Jun Bai; Siwei Deng; Huiyang Fu; Qing Yang; Fazheng Ren; Shenming Zeng; Zhaohui Chen; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2026)

Catalytic ozonation of cyanide in gold leaching efluent by EDTA-Coir/copper slag: Efficacy and mechanisms - Wanzhen Zhong; Gang Meng; Jiacheng Cui; Xinshenghui Zhu; Siyi Luo; Weiqiang Tan; Zongliang Zuo; Weizhang Fu; Dongdong Ren (Process Safety and Environmental Protection, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mass transfer in electrochemical advanced oxidation processes: A comprehensive review of characterization, influencing factors, and computational fluid dynamics simulations - Zhen Liu; Hongze Yang; Bangxing Ren; Yu Qin; Yiwei Fu; Mingyang Si; Zhuoyuan Li; Jiahui Zhang; Yao Chen (Journal of Water Process Engineering, 2026)

The solubilization effects and microscopic mechanisms of a novel sugar-based Gemini surfactant for multiple DNAPLs - Yu Yao; Xueming Qin; Yufeng Fu; Yeping Gao; Hui Zhang; Chuanyu Qin; Bing Qin; Liming Ren (Journal of Hazardous Materials, 2026)

The Hongjianbingshan W–Li–(Be) deposit in the Beishan Orogenic Belt is not related to carboniferous magmatic–hydrothermal events: Insights from multi-mineral U-Pb and zinnwaldite Rb-Sr geochronology - Yong Yin; Heng-Feng Zhang; Zhuang Duan; Bing-Fei Yu; Heng Luo; Yan-Gang Fu; David R. Lentz; Tao Luo; Ke-Yu Ren; Zhe Ren; Hao Hu (Journal of Geochemical Exploration, 2026)

Contrastive mechanisms of lacustrine groundwater discharge and associated pollutant fluxes into two typical inland lakes in Inner Mongolia, Northwest China - Yuanzhen Zhao; Xiaohui Ren; Shen Qu; Fu Liao; Keyi Zhang; Muhan Li; Juliang Wang; Ruihong Yu (Journal of Environmental Sciences, 2026)

The comprehensive fingerprints of VOCs from complex coking emissions and their temporal evolution in the atmosphere based on backward inference method - Hongyan Li; Shidan Huang; Yuanchun Ren; Yanru Zhang; Jing'’ai Bai; Hongyu Li; Guozhong Zhang; Xueying Gao; Yang Cui; Lili Guo; Jie Fan; Yongchun Liu; et al. (Atmospheric Research, 2026)

Decoding the regulatory role of AmiC in amicoumacins production through transcriptomics and metabolic profiling in Bacillus subtilis fmb60 - Antuo Hu; Yangfan Fu; Di Ren; Haifeng Tang; Qingzheng Zhu; Hucheng Jiang; Yanan Liu; Saikun Pan; Jie Yang; Xiaoying Bian (World Journal of Microbiology and Biotechnology, 2026)

Synergistic Neuroprotection of Combined Shenmai and Hypothermia in Cerebral Ischemia–Reperfusion Injury via ERK-Dependent Anti-inflammatory Effects - Yuan Wang; Hangui Ren; Yufei Qiu; Rongchen Dai; Mengfan Liu; Shiting Mo; Yibo Zhang; Wang Fu; Qianqian Bi; Yongpeng Wang; Yunuo Zhou; Zhichao Xi; et al. (Molecular Neurobiology, 2026)

Soil CO2-fixation by cbbL-harboring microorganisms in different types of permafrost peatlands - Yanyu Song; Xianwei Wang; Huanhuan Feng; Shouyang Luo; Jia Qi; Jiusheng Ren; Yisong Feng; Wenkai Mei; Fangcong Fu; Yiting Zhao; Changchun Song (Applied Soil Ecology, 2026)

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

A systematic review for degradation of tetracycline antibiotics by microbial fuel cells: Performance, mechanisms, microbial community and coupled system - Jiayi Li; Hong-Yu Ren; Qiang Fu; Tianxiao Li; Fanying Kong (Process Safety and Environmental Protection, 2025)

Phytochemical profiling of Bai traditional food: Eight previously undescribed meroterpenoids derivatives with cytotoxic potential from the flowers of Rhododendron pachypodum - Ying Wang; Jie Luan; Ji-Ai Wang; Xiu Chen; Fu-Cai Ren; Bing Chen; Jing Jia; Gao-Hong Zhang; Yong Li; Jiang-Bo He (Phytochemistry, 2025)

Comprehensive fatigue assessment in deep-sea enclosed cabins using optimized multi-dimensional weighting - Wei-lan An; Jing Chen; Jin-chi Fu; Zhao-xian Ren; Deng-kai Chen (Ocean Engineering, 2025)

The Bujinhei Pb-Zn deposit in the southern Great Xing'an Range, China: An example of the reduced hydrothermal vein type Pb-Zn mineralization system - Cheng-yang Wang; Yun-sheng Ren; Yi-cun Wang; Zhen-jun Sun; Li-juan Fu (Journal of Geochemical Exploration, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Electrochemical advanced oxidation processes for treating wastewater containing tetracycline antibiotics: Methods, mechanisms, and perspectives - Lin Chen; Haifeng Fu; Xu Ren; Yinqi Chen; Kai Song; Xinjie Cheng; Yong Liu (Journal of Environmental Chemical Engineering, 2025)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Preparation of Prussian blue analogues and investigation of their micro-ammonia adsorption properties - Guancheng Wang; Abdulla Eziz; Abulikemu Abulizi; Hongyu Fu; Kenji Okitsu; Tiezhen Ren; Aisha Nulahong (Journal of Environmental Chemical Engineering, 2025)

Deciphering microbial and metabolite dynamics in rice noodle fermentation: A metagenomic and untargeted metabolomic approach - Yuanyuan Ren; Yuhang Li; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Chemistry, 2025)

Flavonoids of Lycium barbarum L. leaves alleviate DSS-induced ulcerative colitis by microbiota-gut-liver axis - Shuang Liu; Tao Zhang; Jing Ren; Jinwang Liu; Jing Fu; Junwei Yu; Yanli Fan; Yuan Liu (Food Bioscience, 2025)

Enhanced degradation of pharmaceutical contaminants by medium-pressure UV irradiation in the presence of nitrate: Reactive species, toxicity and DBPs formation - Xiang-mei Zhong; Xiang Fu; Yu-qiong Gao; Yang-yang Liu; Xue-ting Ren; Ji-yue Li; Lei Li; Nai-yun Gao (Environmental Research, 2025)

Multigraph fusion neural network for predicting available cadmium levels in farmland soils - Ren-Jie Zhang; Shu-Fang Pan; Huai-Zeng Xing; Tian-Hao Dong; Sai-Hua Liu; Tao Xue; Fa-Xiang Tian; Hong-Yu Fu; Yun-He Xie; Xiong-Hui Ji (Environmental Pollution, 2025)

Hyperspectral modeling of colored dissolved organic matter (CDOM): Insights from machine learning and band ratio models - Jinyue Chen; Chongyang Wang; Shuisen Chen; Shilong Ren; Lei Fang; Yanxia Li; Wenjun Sun; Zhenyu Gao; Zehui Wang; Rao Fu; Guoqiang Wang; Qiao Wang (Estuarine, Coastal and Shelf Science, 2025)

Ultralow-overpotential pH-universal hydrogen evolution on Ru-incorporated CoP/MXene via regulated interfacial water - Xiaoming Liu; Yanqi Han; Jiachun Liu; Yu Fu; Xiaolei Wang; Zhiyu Ren (Chemical Engineering Journal, 2025)

AI-assisted data extraction helps uncover spatiotemporal patterns and socioeconomic drivers of wildlife crime involving sea turtles - Changjian Fu; Weijia Ren; Emilio Pagani-Núñez; Yuqing Han; Jincheng Yang; Huijie Qiao; Zhongqiu Li (Biological Conservation, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Ultrasonic high efficiency preparation of arctigenin from the fruits of Arctium lappa L using Aspergillus niger with deep eutectic solvent assisted - Yubin Ren; Shuang Jin; Weili Liu; Cailiang Peng; Hongyao Cai; Huayong Zhao; Yupeng Cheng; Yujie Fu; Na Zhang; Siyuan Wang; Chen Lv (Biotechnology Letters, 2025)

Meiotic cytokinesis defects in cultured Arabidopsis flowers induce diploid microspores - Huiqi Fu; Yuting Chen; Xueying Cui; Huishan He; Jingru Wang; Chong Wang; Ziming Ren; Bing Liu (Plant Reproduction, 2025)

Research on the application of sulfur-autotrophic denitrifying microorganisms Thiobacillus and Sulfurimonas in wastewater treatment - Dejun Wang; Yanyan Sang; Weizhang Fu; Zongqiang Pang; Wanzhen Zhong; Xinhao Liu; Yuanjie Cui; Lizhi Zhang; Ke Liu; Ziyao Ren (Environment, Development and Sustainability, 2025)

Forecasting China's carbon emissions using a novel nonlinear interactive multivariable grey model - Youyang Ren; Yuhong Wang; Lin Xia; Dongdong Wu; Yiyang Fu; Wentao Huang (Environment, Development and Sustainability, 2025)

Exploring the impact of drying temperature on Camellia oleifera fruit shelling through shrinkage strain, case hardening and microstructure - Pei Yang; Hanyu Fu; Penggeng Sun; Liuyang Ren; Zhaohui Zheng; Yanlong Bu; Deyong Yang (Biosystems Engineering, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Effects of rainfall intensity distribution and extreme events on groundwater recharge dynamics in a shallow karst aquifer - Huimin Ren; Fa Wang; Hamid M. Behzad; Jun Zhang; Hongsong Chen; Zhiyong Fu; Yunpeng Nie; Jinjiao Lian (Journal of Hydrology, 2025)

Effects of fermentation by different strains on the Physico- chemical properties, quality, and metabolic profile of Rice noodles - Yuanyuan Ren; Yuhang Li; Rui He; Yingjie Lei; Yi Zhao; Zikuan Meng; Ding Ma; Jin Fu; Geng Zhong (Food Chemistry, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

A novel strategy based on mouse organoid biosensor for detecting umami substances and their synergistic effect - Minbo Li; Min Fan; Baifeng Fu; Zhihui Chang; Junjie Yi; Yingqi Xie; Wenwen Ren; Yu Tian; Qiyue Zhao; Shuzhen Cheng; Xianbing Xu; Ming Du (Food Chemistry, 2025)

Low-temperature processed samarium-doped ceria interlayers enabling durable methanol-fueled SOFCs for transportation applications - Wei Han; Changyang Liu; Liuzhen Bian; Peng Fu; Dongsheng Ren; Hewu Wang; Xiwen Song; Minggao Ouyang (Chemical Engineering Journal, 2025)

Synergistic effects of metal‑carbon composites in catalytic ozonation: Structure, catalytic pathway and application - Jing Zhang; Kexin Tian; Ye Liu; Yating Fu; Yi Ren; Bo Lai (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

First come, more benefit: roles of arbuscular mycorrhizal fungi in the intraspecific competition of an invasive clonal plant - Shanshan Qi; Francis Kwaku Nkansah; Xinqi Jiang; Hu’anhe Xiong; Mengting Yan; Ying Li; Guangqian Ren; Wei Wei; Weiguo Fu; Zhicong Dai; Daolin Du (Plant and Soil, 2025)

Correction: The PGC-1α/SIRT3 pathway mediates the effect of DON on mitochondrial autophagy and liver injury in mice - Yihan Wang; Jiali Fu; Danni Zhou; Zhihua Ren; Junliang Deng (Mycotoxin Research, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

External and internal controls on decadal precipitation variability over North America - Xiaolu Fan; Jianping Huang; Yongkun Xie; Wenmin Wei; Yu Ren; Yihui Xu; Ming Peng; Li Fu (Climate Dynamics, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Ubiquitin-conjugating enzyme StUBC19 regulates osmotic and salt stress in potato transgenic plants - Xue Fu; Xun Tang; Ning Zhang; Xinyu Ren; Peishan Li; Huaijun Si (Plant Science, 2025)

Unveiling DNAPLs solubilization mechanisms: How hydrophobic chain length governs characteristics in novel sugar-based Gemini surfactants - Yu Yao; Xueming Qin; Yufeng Fu; Yeping Gao; Chengwu Zhang; Hui Zhang; Chuanyu Qin; Bing Qin; Liming Ren (Journal of Hazardous Materials, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Mechanistic study on the enhanced activation of peroxymonosulfate by the bimetallic Mo/Co Co-doped g-C₃N₄ composite catalyst 8-CNMC for phenol degradation: Applicable for neutral and alkaline condition - Xuechang Ren; Miao Tian; Ning Fu; Hongjin Chen; Zuoyan Chen; Yajun Wei; Qiongqiong Wang (Journal of Environmental Chemical Engineering, 2025)

Magnetic recyclable MIL-88A(Fe)@WS2/CuFe2O4 ternary composite promotes peroxymonosulfate activation for efficient phenol removal: Performance, mechanism and toxicity evaluations - Ning Fu; Yuxiang Chen; HongJin Chen; Bowen Zheng; Miao Tian; Qiongqiong Wang; Xuechang Ren (Journal of Environmental Chemical Engineering, 2025)

New silicon nanoparticles for “turn-on” detection of salicylaldehyde in food based on ESIPT mechanism - Jialu Zhang; Yu Fu; Peng Chen; Bowen Liu; Cuiling Ren (Food Chemistry, 2025)

Improving surimi gel quality by corn oligopeptide-chitosan stabilized high-internal phase Pickering emulsions - Yufeng Xue; Jiahui Song; Siyu Chen; Caili Fu; Zhanming Li; Wuyin Weng; Linfan Shi; Zhongyang Ren (Food Hydrocolloids, 2025)

In-situ crystallization of rigid porous nanoparticles in the GO membrane for stable dye desalination - Yun-Han Ren; Wen-Hai Zhang; Ming-Jie Yin; Zhi-Jie Liu; Quan-Fu An (Desalination, 2025)

Antinode-centre near-infrared tandem OLEDs enabled by ultrathin emissive layers - Min Song; Zheng Ren; Sheng-Fu Wang; Xiao-Bo Shi; Wei-Zhi Liu; Zi-Qi Feng; Dong-Ying Zhou; Pi-Tai Chou; Liang-Sheng Liao (Chemical Engineering Journal, 2025)

Highly selective reduction of CO2 to CH4 mediated by 2D/0D Cs3Bi2Br9/BiOBr heterojunctions with atomic-level intimate interfaces - Tingting Ren; Yanqing Zhang; Suning Fu; Yuanming Hou; Jiaxin Wang; Jingyi Qin; Zhengzheng Xie; Jianjun Yang; Zhongjie Guan; Shilong Jiao; Qiuye Li; Xianwei Fu (Chemical Engineering Journal, 2025)

Performance optimization and microbial community analysis of integrated anaerobic BES-aerobic MBBR system for azo dye treatment with related wastewater remediation - Fanying Kong; Qiang Fu; Lihong Wang; Hong-Yu Ren (Chemical Engineering Journal, 2025)

Effect of Attribute Information of Recycled Water on Willingness to Accept: Evidence from an Event-Related Potential (ERP) Experiment - Hanliang Fu; Bo Dong; Zhifang Wu; Caixia Hou; Yanjun Ren (Water Resources Management, 2025)

Plant community‐dominating species can sustain population biomass by modifying and strengthening their own growth traits to deal with long‐term grazing - Yu-Wen Zhang; Ze-Chen Peng; Zhao-Feng Wang; Sheng-Hua Chang; Yu-Feng An; Duo-Cai Li; Fu-Jiang Hou; Ji-Zhou Ren (Agriculture, Ecosystems & Environment, 2025)

UWS-YOLO: Advancing Underwater Sonar Object Detection via Transfer Learning and Orthogonal-Snake Convolution Mechanisms - Liang Zhao; Xu Ren; Lulu Fu; Qing Yun; Jiarun Yang (Journal of Marine Science and Engineering, 2025)
Accurate and efficient detection of underwater targets in sonar imagery is critical for applications such as marine exploration, infrastructure inspection, and autonomous navigation. However, sonar-based object detection remains challenging due to low resolution, high noise, cluttered backgrounds, and the scarcity of annotated data. To address these issues, we propose UWS-YOLO, a novel detection framework specifically designed for underwater sonar images. The model integrates three key innovations: (1) a C2F-Ortho module that enhances multi-scale feature representation through orthogonal channel attention, improving sensitivity to small and low-contrast targets; (2) a DySnConv module that employs Dynamic Snake Convolution to adaptively capture elongated and irregular structures such as pipelines and cables; and (3) a cross-modal transfer learning strategy that pre-trains on large-scale optical underwater imagery before fine-tuning on sonar data, effectively mitigating overfitting and bridging the modality gap. Extensive evaluations on real-world sonar datasets demonstrate that UWS-YOLO achieves a mAP@0.5 of 87.1%, outperforming the YOLOv8n baseline by 3.5% and seven state-of-the-art detectors in accuracy while maintaining real-time performance at 158 FPS with only 8.8 GFLOPs. The framework exhibits strong generalization across datasets, robustness to noise, and computational efficiency on embedded devices, confirming its suitability for deployment in resource-constrained underwater environments.

Genome-wide association and genomic selection studies on feed efficiency with fishmeal-free feed in large yellow croaker (Larimichthys crocea) - Gongsi Wang; Yingbo Yuan; Xiaotong Li; Ranxin Fu; Xingcheng Zhu; Zhenye Zhao; Yuhan Jin; Sen Zhang; Peng Ren; Lining Zhang; Qinghui Ai; Ming Fang; et al. (Aquaculture, 2025)

Regional airflow velocity control to meet the diverse requirements of unevenly distributed maize threshing mixtures - Meng Zhang; Chao Cheng; Jun Fu; Zhi Chen; Luquan Ren (Biosystems Engineering, 2025)

Self-assembled Fe-HTO/MXene/PSF lithium ion-sieve membrane for efficient lithium extraction from shale gas wastewater - Yuchun Ren; Dandan Zhao; How Yong Ng; Chen Fu; Yuan Liu; Yongsheng Fu; Zhenglian Wu (Water Research, 2025)

Retrofitting green spaces based on dispersion and absorption of mobile-source carbon emissions - Xinlu Bai; Xin Fu; Zeqi Ren; Christopher Auffrey; Qi Wang (Transportation Research Part D: Transport and Environment, 2025)

A novel multifunctional suction-controlled apparatus for investigating tensile strength of unsaturated soils - Xiang-Shen Fu; Han-Lin Wang; Ren-Peng Chen; Cheng-Shuang Yin; Yue-Hui Sun; Xiao-Hu Zhang; Daniel Dias (Transportation Geotechnics, 2025)

Experimental study of geogrid role on long-term settlement in geosynthetic-reinforced pile-supported embankment subjected to cyclic loading - Kai-Fu LIU; Shi-Yu XU; Wei-Qiang FENG; Kai-Ren XUE; Yu-Xiao Li (Transportation Geotechnics, 2025)

Anti-inflammatory abietane-type diterpenoids from the roots of Salvia przewalskii - Yan-Fang Chen; Yu-Qing Lu; Wan-Yun Gao; Bo-Yi Fan; Fu-Cai Ren; Chuan-Pu Shen (Phytochemistry, 2025)

Photobiomodulation mitigates DHT-induced apoptosis in dermal papilla cells via mitochondrial rescue and Wnt/TGF-β/BMP signaling modulation - Yi Ren; Xiaojing Miao; Hui Jiang; Angze Li; Longfei Huo; Xuran Zhang; Qiqi Fu; Jiali Yang; Jing Tian; Muqing Liu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Simulation and experimental study of potato slices during cooking - Hanyu Fu; Pei Yang; Penggeng Sun; Liuyang Ren; Jingshen Xu; Qing Liang; Zhaohui Zheng; Weijun Xie; Deyong Yang (International Journal of Gastronomy and Food Science, 2025)

Studies on the key enzyme for the conversion of limonene to α-terpineol by Penicillium digitatum DSM62840 - Boyu Yang; Yingying Zhang; Xiwen Hu; Jingnan Ren; Gang Fan; Jinchu Yang; Qiuling Wang; Yongfeng Yang; Zhenzhen Huang; Yongming Xu; Haoliang Li; Yufeng Fu; et al. (Food Bioscience, 2025)

Three-atom bridged centers activate inert electrons in MXene via Ti 3d orbital engineering to enhance electrocatalysis in lithium‑oxygen batteries - Rongchang Ren; Yaning Fu; Mengyao Huang; Zhongjun Li; Youcai Lu; Qingchao Liu (Chemical Engineering Journal, 2025)

Degradation of mesotrione in bioelectrochemical system: Performance, mechanisms, and microbial communities - Zhibing Xing; Qiang Fu; Hong-Yu Ren; Lihong Wang; Fanying Kong (Chemical Engineering Journal, 2025)

Corrigendum to “Toxic effects of anionic polyacrylamide on the developmental stages of Oryzias melastigma embryos and larvae” [Aquatic Toxicology, 284 (2025) 107402] - Xinya Zhao; Jiangwei Zan; Zhaohui Sun; Xiangping Xue; Hai Ren; Huiru Fu; Fei Si; Xiaomin Jin (Aquatic Toxicology, 2025)

Blue light preconditioning as a novel strategy for reducing transport stress in zebrafish - Longfei Huo; Xiaojing Miao; Xuran Zhang; Yi Ren; Qiqi Fu; Jiali Yang; Muqing Liu (Behavioural Processes, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

Potato–rice and garlic–rice rotation increases soil phosphorus availability through phosphate-solubiliing bacteria and root exudates in upland–paddy cropping systems - Qi Liu; Wei Zhou; Zhiping Yang; Tao Wang; Yong Fu; Xueping Yue; Haixiao Xia; Youfeng Tao; Fei Deng; Xiaolong Lei; Yong Chen; Wanjun Ren (Agriculture, Ecosystems & Environment, 2025)

Effects of high temperature on gonadal development of gynogenetic Megalobrama amblycephala and acquisition of fertile pseudo-male fish - Wen Fu; Ze Li; Xin Ren; Feng Liu; Wenbin Liu; Jinhui Liu; Liangyue Peng; Yamei Xiao (Aquaculture, 2025)

Path analysis of trace elements and physiological and biochemical indices associated to mild cognitive impairment in elderly Chinese - Peiyi Liu; Haiyan Huang; Qimei Zhou; Ying Zhi; Jiahui Wang; Ying Fu; Erwei Gao; Xiaohu Ren; Xiao Chen; Xinfeng Huang; Jianjun Liu; Xifei Yang (Environmental Pollution, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

scSAGRN: Inferring gene regulatory networks from single-cell multi-omics using spatial association - Qing Ren; Mengdi Nan; Yuhan Fu; Xiang Chen; Yibing Ma; Yongle Shi; Jie Gao (BioSystems, 2025)

The PGC-1α/SIRT3 pathway mediates the effect of DON on mitochondrial autophagy and liver injury in mice - Yihan Wang; Jiali Fu; Danni Zhou; Zhihua Ren; Junliang Deng (Mycotoxin Research, 2025)

Mobile Genomic Island GEI-FN1A in Aeromonas salmonicida FN1 Contributes to the Spread of Antibiotic-Resistance Genes - Xinru Xie; Zhaorui Ren; Rong Wang; Kanglu Tian; Xindi Huang; Yang Lyu; Guangxiang Cao; Jiafang Fu (Current Microbiology, 2025)

Arbuscular mycorrhizal fungi enhance glyphosate resistance in an invasive weed: Implications for eco-environmental risks - Shanshan Qi; Daiyi Chen; Mengting Yan; Zhiyun Huang; Haochen Yu; Guangqian Ren; Hu'anhe Xiong; Wei Fu; Biying Zhao; Zhicong Dai; Daolin Du; Torsten Thomas (Applied Soil Ecology, 2025)

Detecting Zone‐Type Thresholds for Soil Organic, Inorganic, and Total Carbon Pools in China's Drylands - Zhuobing Ren; Changjia Li; Bojie Fu; Wenxin Zhou; Xinli Chen; Shuai Wang; Lindsay C. Stringer (Global Change Biology, 2025)
Growing concerns about the accelerating global changes in drylands have intensified interest in understanding the impacts of diverse environmental factors on various soil carbon components, particularly their potential threshold effects, which may lead to abrupt nonlinear changes in both the quantity and composition of soil carbon. However, most research has predominantly focused on identifying key environmental drivers of either organic or inorganic carbon separately, often neglecting the presence and range of multiple critical thresholds. This study addresses this gap by analyzing extensive field data, including soil carbon measurements and ecosystem variables, collected across a ~4000 km transect in China's drylands. Utilizing a gradient forest model combined with threshold analyses, we assess the impacts of key drivers, including sand content, total nitrogen, aridity, and cation exchange capacity, on soil carbon pools. Our findings indicate that nitrogen content is the most influential factor for soil organic carbon, which was sensitive to low levels of nitrogen (0.07%–0.08%), with a slower response observed at higher levels. Aridity significantly affects both organic and inorganic carbon pools, with identified threshold zones for organic carbon at aridity levels of 0.48–0.52 and 0.75–0.85, and for inorganic carbon at 0.82–0.88. Threshold zones of sand content for total carbon are identified at lower levels and a wider range (51.4%–64.1% and 87.3%–88.1%), due to its negative effects on both organic and inorganic carbon, impacting 20% of the dryland area. Spatial variations in threshold effects revealed a trade‐off between nitrogen and pH in regulating soil total carbon. The combined threshold effects of climate warming and aridification may pose a greater threat to soil organic carbon in high‐latitude regions. This research enhances understanding of soil carbon dynamics in arid environments and offers novel approaches and insights for identifying thresholds in ecosystems that are increasingly at risk of reaching tipping points.

Performance and mechanism analysis of a novel conjunctival composite dust suppressant for metal mines - Zhian Huang; Keying Meng; Jiaze Ren; Rongxia Yu; Mingming Fu; Gaowen Wang; Yinghua Zhang; Hongsheng Wang; Jinyang Li; Ye Xu; Md Yasin; Asim Farooq (Process Safety and Environmental Protection, 2025)

Numerical investigation of aerated water entry by multiphase Riemann SPH method - Ke Zhao; Sheng-Fa Yang; Pei-Yin Yuan; Fu-Long Shi; Fu-Ren Ming (Ocean Engineering, 2025)

Analysis of intrinsic effects of compound curing agents on small molecule metabolites and microbial communities in Xuanwei ham based on metabolomics and high-throughput sequencing - Zhijie Zheng; Wenxi Fu; Guiying Wang; Bo Li; Wen Xun; Nannan Zhou; Chunfang Yang; Ruwei Ren; Shuai Tang; Yanfei Du; Jiayan Tan; Dahai Gu; et al. (Meat Science, 2025)

Impacts of non-thermal pretreatments on banana slices during microwave vacuum dehydration using THz-TDS and NIR-HSI techniques - Ying Fu; Yuqiao Ren; Da-Wen Sun (Journal of Food Engineering, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Upper Jurassic radiolarian assemblages and chert geochemistry of the Shiquanhe ophiolite, NW Tibet: Implications for the evolution of the Meso–Tethyan ocean - Xiaohui Cui; Yichun Zhang; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Qinggao Zeng; Guangying Ren; Hui Luo (Gondwana Research, 2025)

Diffusion-driven zircon Zr isotopic fractionation during ultramafic–mafic magmatic differentiation - Li-Tao Ma; Li-Qun Dai; Shao-Bing Zhang; Ren-Xu Chen; Qiong-Xia Xia; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2025)

Smartphone app with cloud-based machine learning and visual sensor array for instrument-free detection of species, geographic origin, and quality marker in functional food Gancao - Yun Huang; Aifen Hu; Lixue Ren; WanJun Long; Wei Lan; Yi He; Yuanbin She; Hengye Chen; Haiyan Fu (Food Control, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Seismic behaviour of prefabricated square reinforced concrete-filled steel tubular pier with a grouting sleeve connection - Xiaoqian Ren; Yan-Gang Zhao; Chunhui Zhang; Yan Li; Longwei Xu; Tao Fu (Engineering Structures, 2025)

Fe-doped H2TiO3 for rapid and efficient lithium extraction from shale gas wastewater - Yuchun Ren; Dandan Zhao; Chen Fu; Fei Zhou; Qian Wang; Yongsheng Fu; Tao Gong; Zhenglian Wu (Desalination, 2025)

Toxic effects of anionic polyacrylamide on the developmental stages of Oryzias melastigma embryos and larvae - Xinya Zhao; Jiangwei Zan; Zhaohui Sun; Xiangping Xue; Hai Ren; Huiru Fu; Fei Si; Xiaomin Jin (Aquatic Toxicology, 2025)

SKA3 promotes lung adenocarcinoma progression via the EGFR/E2F1/SKA3/integrin β1 signaling loop - Xiufen Zheng; Zedong Sun; Shi Wang; Qibing Liu; Biqing Zhu; Zhijian Ren; Dingwei Fan; Chunping Zhang; Xinyin Fu; Yan Jin; Jing Luo; Jie Wang; et al. (Molecular and Cellular Biochemistry, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

Effect of ponatinib on the metabolism of cariprazine in vitro and in vivo and the underlying mechanism - Hualu Wu; Haoxin Fu; Fangyuan Xia; Jun Wu; Peiqi Wang; Lu Cao; Ren-ai Xu; Lu Shi (Toxicology and Applied Pharmacology, 2025)

Effective degradation of phenol using magnetic MoS2/SnFe2O4 composite activated peroxysulfate: Mechanism study and catalytic performance evaluation - Gongrong Chen; Xuechang Ren; Zhongshan Li; Hongjin Chen; Huiying Lei; Guanguo Zhang; Duxudong Huang; Ning Fu (Journal of Environmental Chemical Engineering, 2025)

Abundance correlations of carbon fixation and pollutant degradation functions in oil-contaminated soils: Insights derived from integrated metagenomic and quantitative PCR analyses - Jiayu Song; Yakui Chen; Yilei Han; Xingchun Li; Zheng Liu; Ziyi Peng; Aimin Fu; Jinman Ren; Diannan Lu; Chunmao Chen (Journal of Environmental Chemical Engineering, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Pullulanase-catalyzed hydrolysis of V-type starch produced high-adsorbency V-type porous starch attaching by nano-spherical particles - Xing Zhou; Yanxin Chen; Miaomiao Fu; Zhengye Sun; Tizazu Yirga Bereka; Mudassar Hussain; Guo Chen; Ren Wang; Zhengyu Jin (Food Bioscience, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

Effects of tourmaline on anaerobic ammonia oxidation process: Mechanistic Understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Shan Qiu; Baojian Jing; Shuoqi Ren; Jue Wang; Mengxuan Deng; Mengqi Fu; Zhongqi Jiang; Fengxia Deng; Jinghui Wang; Jie Qiu (Chemical Engineering Journal, 2025)

Exosome-Mediated Communication in Thyroid Cancer: Implications for Prognosis and Therapeutic Targets - Yiwei Wang; Qiang Li; Xinrui Yang; Hanyu Guo; Tian Ren; Tianchi Zhang; Pantea Ghadakpour; Fu Ren (Biochemical Genetics, 2025)

A Year Marked by Extreme Precipitation and Floods: Weather and Climate Extremes in 2024 - Wenxia Zhang; Tianjun Zhou; Wanheng Ye; Tingyu Zhang; Lixia Zhang; Piotr Wolski; James Risbey; Zhuo Wang; Seung-Ki Min; Hamish Ramsay; Michael Brody; Alice Grimm; et al. (Advances in Atmospheric Sciences, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Distribution and influencing factors of antibiotic resistance genes in two mussel species along the coasts of the East China Sea and the Yellow Sea - Peipei Fu; Jiaying Zhai; Xiaoao Yang; Jiaxin Gao; Zhongjie Ren; Baoying Guo; Pengzhi Qi (Journal of Hazardous Materials, 2025)

Emergy-based sustainability analysis and comprehensive evaluation of individual heating systems: A case study from rural northern China - Yun Deng; Xueling Ran; Yaohong Yu; Yongkun Fu; Sihao Ren; Mingyang Liu; Renjie Dong; Yuguang Zhou (Journal of Cleaner Production, 2025)

Multi-omics joint analysis: Pachymic acid ameliorated non-alcoholic fatty liver disease by regulating gut microbiota - Guilin Ren; Yiyou Lin; Yilong Fu; Fucai Liu; Ruiqi Wang; Congcong Zhang; Jiannan Qiu; Lin Chen; Xiaobing Dou (Food Research International, 2025)

Morphologically regulated nanocellulose from soybean residues for stabilizing Pickering emulsions via interfacial interaction - Yanyi Xue; Wenliang Wang; Xinyi Zheng; Xiufeng Duan; Xiaoxiao Ren; Yishuai Fu; Jinbao Cheng; Chengyuan Liang (Food Hydrocolloids, 2025)

Facile and scalable synthesis of bio-based adsorbents from tannin for economical uranium extraction from seawater - Xingyu Fu; Minsi Shi; Dingyang Chen; Zixu Ren; Qing Bai; Rui Zhao (Desalination, 2025)

MXene-bridged HMO/PSF adsorptive membrane for selective lithium recovery from shale gas wastewater with suppressed Mn leaching - Yuchun Ren; Dandan Zhao; Fei Zhou; Yuan Liu; Chen Fu; Yongsheng Fu; Tao Gong; Zhenglian Wu; Xinyu Yang; Zefeng Cai (Desalination, 2025)

Growth Onset Rather Than Photosynthesis Strongly Regulates Autumn Senescence Termination Besides Climate Change - Shuping Ji; Shilong Ren; Yann Vitasse; Constantin M. Zohner; Yongshuo H. Fu; Xiaoqiu Chen; Xiaoyang Zhang; Charlotte Grossiord; Huiying Liu; Matthias Peichl; Dailiang Peng; Shuai An; et al. (Global Ecology and Biogeography, 2025)
Aim Plant senescence largely influences the global carbon cycle by regulating the growing season length. However, the driving mechanisms of plant senescence remain unclear, particularly the role of developmental factors. This study aims to investigate how environmental and developmental factors drive autumn senescence and evaluate whether woody and herbaceous plants exhibit divergent responses to these drivers. Location Eurasia. Time Period 1982–2014. Major Taxa Studied Woody and herbaceous species. Methods Using 120,833 long‐term ground phenological observations, we employed partial correlation analysis to investigate the influence of environmental and developmental factors on senescence termination. Experimental records from literature and pasture survey observations from China were separately utilised to further validate the influence of developmental factors on senescence termination. Structural equation modelling was applied to analyse the pathways of growth onset affecting senescence termination. Additionally, multiple linear regression was used to examine the tendency of the sensitivity of senescence termination to plant development rate. Results We find that earlier growth onset primarily leads to earlier senescence termination directly in herbaceous plants, but indirectly in woody plants by accelerating early‐season development. The sensitivity of senescence termination to plant development rate shows a declining trend, particularly in early‐season negative effects on woody plants and late‐season positive effects on herbaceous plants, suggesting diminished impacts of future warming on senescence timing. The impact of growing season photosynthetic activity on senescence termination is not pronounced for both woody and herbaceous plants. Main Conclusions The results demonstrate that growth onset may affect woody and herbaceous senescence termination through different pathways, whereas the carry‐over effects of growing season photosynthetic activity are not widely discovered. This emphasises that the introduction of developmental factors into phenological models needs to be considered carefully according to plant type.

Transillumination imaging for detection of stress cracks in maize kernels using modified YOLOv8 after pruning and knowledge distillation - Jingshen Xu; Shuyu Yang; Qing Liang; Zhaohui Zheng; Liuyang Ren; Hanyu Fu; Pei Yang; Weijun Xie; Deyong Yang (Computers and Electronics in Agriculture, 2025)

Numerical study of deformation inhomogeneity and its effect on mechanical properties of the heavy-wall offshore pipeline fabricated by different processes - Ling-zhi Xu; Gui-ying Qiao; Ying-long Ma; Yu Gu; Kai Xu; Xiao-wei Chen; Fu-ren Xiao (Ocean Engineering, 2025)

In situ regeneration of phenol-saturated activated carbon fiber via an electro-permanganate process - Zhen Liu; Lang Liu; Yiwei Fu; Huan He; Chuanliang Zhao; Xiaodi Duan; Bangxing Ren; Zhe Zhang; Shaochun Yuan; Yao Chen (Journal of Water Process Engineering, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Development and validation of deformation-dependent theoretical model for soil arching effect under unloading - Ren-Peng Chen; Xiang-Shen Fu; Qi-Wei Liu; Xiao-Hu Zhang; Han-Lin Wang (Computers and Geotechnics, 2025)

Bacterial indole-3-propionic acid inhibits macrophage IL-1β production through targeting methionine metabolism - Ziyi Han; Jian Fu; Aiyan Gong; Wenkai Ren (Science China Life Sciences, 2025)

Dry season residual straw reduces nitrous oxide emissions during rice season in upland-paddy rotation systems by inhibiting soil denitrification - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Zhiping Yang; Yong Fu; Xueping Yue; Fei Deng; Xiaolong Lei; et al. (Biology and Fertility of Soils, 2025)

Seismic interaction and improved design method of substation equipment with multiple electrical configurations - Enrui Guo-Dai; Xing Fu; Gang Li; Hongnan Li; Liang Ren (Earthquake Engineering and Engineering Vibration, 2025)

Mechanism study of the effect of a surface liquid film on the collision adhesion behaviour of rice stalks - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Biosystems Engineering, 2025)

Traffic prediction and road space optimization for the integration of dockless bike-sharing and subway - Ganmin Yin; Chen Fu; Shuliang Ren; Xiaoqin Yan; Junnan Qi; Yi Bao; Zhou Huang (Sustainable Cities and Society, 2025)

mtNET-mineral complex: a building block of calculus - Yutong Fu; Meichen Wan; Yina Zhu; Dongxiao Hao; Qianqian Wan; Wen Niu; Zhaoyang Ren; Kehui Xu; Weijun Qin; Shiren Sun; Wei Yi; Kai Jiao; et al. (Science Bulletin, 2025)

Spatiotemporal evolution characteristics of ground deformation in the Beijing Plain from 1992 to 2023 derived from a novel multi-sensor InSAR fusion method - Yuanzhao Fu; Jili Wang; Yi Zhang; Honglei Yang; Lu Li; Zhengzhao Ren (Remote Sensing of Environment, 2025)

Prenatal high-sucrose diet affects pulmonary artery contractile functions via MT receptors - Xueqin Feng; Hongwei Fu; Xiao Sun; Hua Shu; Yongning Zhu; Yanyan Bai; Qinggui Ren; Xinying Liu; Meng Liu; Fanyong Zhang; Yanping Wang (Reproductive Toxicology, 2025)

Machine learning-based analysis of microplastic-induced changes in anaerobic digestion parameters influencing methane yield - Zhenghui Gao; Zongqiang Ren; Tianyi Cui; Yao Fu (Journal of Environmental Management, 2025)

Treatment of cold pressed Zanthoxylum schinifolium oil wastewater: Process, sludge characteristics, and microbial diversity analysis using biochemical methods - Fenglan Zhou; Pimiao Huang; Chenyang Ma; Xiaowei Peng; Mingze Fu; Tingyuan Ren; Jianquan Kan (Journal of Environmental Management, 2025)

In-situ gel injection of poloxamer-based metamizole provides long-acting antipyretic effects - Yueli Wang; Dongbo Li; Xiaojuan Li; Dandan Ren; Wei Zhang; Gang Shu; Juchun Lin; Haohuan Li; Funeng Xu; Guangneng Peng; Hualin Fu (Drug Delivery and Translational Research, 2025)

Characterization of Organic Aerosols in the Ambient Air of Raipur, Central India: Distribution, Seasonal Variations, and Source Apportionment - Shobhana Ramteke; Bharat Lal Sahu; Khageshwar Singh Patel; Piyush Kant Pandey; Sema Yurdakul; Pablo Martín-Ramos; Hong Ren; Pingqing Fu (Aerosol Science and Engineering, 2025)

Cadmium exposure induces inflammation, oxidative stress and DNA damage in HUVEC and promotes THP-1 adhesion: A possible mechanism on the formation of atherosclerotic plaque - Haotian Liu; Mingyang Fu; Ziqi Ren; Zhaoshuo Liu; Xiangyu Cao; Jiahe Chen; Yulin Pang; Jianli Liu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Electrostatically self-assembled Fe3O4@Ti3C2Tx electrodes for efficient capacitive deionization driven by ultrafast ion pumps - Fu Feng; Li Wang; Ning Hu; Zhuang Ren; Yuhe Bai; Qiangqiang Tao; Kang Li; Shuai Lu; Aixin Zhang; Qingmiao Wang (Journal of Environmental Chemical Engineering, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

A novel dual-way inference modeling method for coal coking: Predicting H2 and CH4 concentrations in coke oven gas and inferring optimal reaction conditions - Xiaoguo Zhang; Danni Ren; Xiaolan Fu; Wei Lu; Shenfu Yuan (Fuel, 2025)

H2O2-generating casein hydrogels used in food packaging: Rapid photocrosslinking and antimicrobial activity - Qinchao Zhu; Jinfeng Fu; Zhidan Wang; Juxin Pei; Wuzhou Yi; Daxi Ren (Food Research International, 2025)

Integrated network pharmacology, bioinformatics, and experiment analysis to decipher the molecular mechanism of Salidroside on Gastric cancer via targeting NCOA4-mediated ferritinophagy - Yu Fu; Guiqin Huang; Yawen Cai; Menghui Ren; Run Cheng; Yuhui Chai; Yingdi Wang; Yunqi An; Tianhua Yan; Lingpeng Zhu; Xinxin Liu (Chemico-Biological Interactions, 2025)

A case study from a critical stopover site in the East Asian-Australasian Flyway provides lessons for optimal high-tide roost management to support shorebird conservation - Jia Guo; Waner Liang; Yan Zhou; Yifei Jia; Hongyan Yang; Lili Sun; Qing Chen; Ting Fu; Sicheng Ren; Wenkui Jiang; Guangchun Lei; Li Wen (Biological Conservation, 2025)

Underground laboratories · Deep underground observation · Scientific questions—Insights from observations of multi-physic fields in deep underground labs - Huiqi Ren; Yun Wang; Chang Chen; Guangyu Fu; Longqing Qiu; Lianghui Guo; Chengliang Xie; Yongsheng He; Heping Sun; Jiwen Teng (Science China Earth Sciences, 2025)

MRG15 promotes cell apoptosis through inhibition of mitophagy in hyperlipidemic acute pancreatitis - Boyuan Gu; Wenhao Yu; Zhiwei Huang; Junjie Bai; Shenglu Liu; Bingyu Ren; Pengru Wang; Lei Sun; Jian Wen; Yang Zheng; Peng Tan; Wenguang Fu (Apoptosis, 2025)

Profiling of chromatin accessibility and regulatory elements toward understanding the mechanisms underlying growth regulation in the Pacific oyster (Crassostrea gigas) - Ke Wan; Chenyu Shi; Yongjing Li; Liting Ren; Huiru Fu; Qi Li; Shikai Liu (Aquaculture, 2025)

Intestinal microbiota was closely related to feed efficiency of Larimichthys crocea fed two fishmeal-free diets - Xiaotong Li; Gongsi Wang; Ranxin Fu; Xingcheng Zhu; Peng Ren; Lining Zhang; Qinghui Ai; Yunzhang Sun; Zhiyong Wang (Aquaculture, 2025)

Nitrogen-driven shifts in molecular composition of soil dissolved organic matter linked to rare bacterial sub-communities - Xiaochun Yuan; Quanxin Zeng; Xinyu Bai; Xiaoqing Zhang; Xiaoting Fu; Mengxiao Ren; Juyan Cui; Qiufang Zhang; Xiaoli Gao; Jiacong Zhou; Yong Zheng; Kaimiao Lin; et al. (Science of The Total Environment, 2025)

UV-aging process of titanium dioxide nanoparticles aggravates enterohepatic toxicity of bis(2-ethylhexyl)-2,3,4,5-tetrabromophthalate to zebrafish - Yuxi Zhou; Kaiyu Fu; Fan Li; Yindan Zhang; Xinxin Ren; Bingjie Li; Shengmin Wu; Jian Han; Lihua Yang; Bingsheng Zhou (Science of The Total Environment, 2025)

A boundary enforcement method for the truncated ship structure model during underwater contact explosion experiments - Liang Zhang; Xin Lin; Hong-Na Yang; Fu-Ren Ming (Ocean Engineering, 2025)

The synergistic effect of pulsed red light and leonurus inhibits primary dysmenorrhea induced by oxytocin in mice by modulating calcium signaling and inhibiting inflammatory responses - Qiqi Fu; Hui Jiang; Jiali Yang; Haokuan Qin; Longfei Huo; Yi Ren; Shangfei Lin; Muqing Liu; Jinghui Yao (Journal of Photochemistry and Photobiology B: Biology, 2025)

CO enhancement in coal gasification with CO2: Effect of minerals - Xiaolan Fu; Xiaoguo Zhang; Danni Ren; Wei Lu; Shenfu Yuan (Fuel, 2025)

Low-temperature glucose foaming to construct three-dimensionally porous bulk CoMo catalyst for thiophene hydrodesulfurization - Yeqiang Du; Longzhou Ren; Wenjing Song; Ziqi Wan; Qinqin Zhang; Liancheng Bing; Fang Wang; Guangjian Wang; Haitao Fu; Dezhi Han (Fuel, 2025)

Molecularly imprinted polymer gel with superior recognition and adsorption capacity for amphenicol antibiotics in food matrices - Ruiyu Fu; Xiaoqin Hai; Qingxin Lu; Hongbo Li; Jiaxiao Niu; Yanhui Zhang; Tingze Ren; Xiaoli Guo; Xin Di (Food Chemistry, 2025)

Regulation of the unconventional luminescence behaviors of phenylenediamine-based carbon dots with high PLQY values - Pinyi He; Jianliang Bai; Guohui Yang; Fu Qin; Xinyu Wang; Xu Yu; Yongkang Yao; Xin Tang; Lili Ren (Chemical Engineering Journal, 2025)

On-board and in-situ identification of cell-individual hydrogen crossover in fuel cell stacks based on electrochemical dynamics during shutdown - Xi Fu; Pucheng Pei; Peng Ren; Zijing Zhu; He Wang; Xin Song; Zhezheng Wang (Chemical Engineering Journal, 2025)

Rapid analysis of salivary glucose content using MOF/MIPs biomimetic microfluidic paper chips - Ningning Li; Ying Zhou; Hao Sun; Nan Wang; Nan Yang; Peiyao Ren; Lanjun Fu; Yiming Zhang; Wei Liu; Yanjie Li; Juan Jin (Chemical Engineering Journal, 2025)

Volumetric internal Joule heating of a catalyst packed SiSiC foam for efficient dry reforming of methane - Lei Zheng; Di Wang; Yunfeng Jiang; Yingyu Ren; Yihai Wu; Yu Fu; Jun Zhang (Chemical Engineering Journal, 2025)

BI1 Activates Autophagy and Mediates TDP43 to Regulate ALS Pathogenesis - Yu Wang; Yuxiang Wang; Hanlan Yin; Zixuan Xiao; Zhichao Ren; Xueting Ma; Jingtian Zhang; Xueqi Fu; Fuqiang Zhang; Linlin Zeng (Molecular Neurobiology, 2025)

Thickness monitoring of threshing mixture on the oscillating plate of corn grain harvester - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Computers and Electronics in Agriculture, 2024)

Efficient and green preparation of baicalein from Radix scutellariae with deep eutectic solvent pretreated bioconversion of cellulose-based microreactor - Shuang Jin; Yubin Ren; Yupeng Cheng; Weili Liu; Cailiang Peng; Bingyou Yang; Haixue Kuang; Yujie Fu; Chen Lv; Hongyao Cai (Sustainable Chemistry and Pharmacy, 2024)

Enhanced removal of tetracycline using three-dimensional electrochemical system with Fe/N/S co-doped coffee grounds biochar particle electrodes: Performance and mechanism - Peixin Tang; Xu Ren; Jiahao Mei; Yucheng Liu; Kai Song; Haifeng Fu; Xin Peng; Li Zeng; Qiang Ma; Zhicheng Pan (Process Safety and Environmental Protection, 2024)

The role of deep learning in aortic aneurysm segmentation and detection from CT scans: A systematic review and meta-analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Next Research, 2024)

Hydrocyclone-induced classification reduction and spin desorption of contaminated soil remediation with heavy metal and organics - Yi Liu; Jiahui Ren; Kai Ma; Jianping Li; Pengbo Fu; Kuangfei Lin; Hualin Wang (Journal of Hazardous Materials, 2024)

Optimizing multiple ecosystem services in Eucalyptus plantations: Dual effects of intercropping and restoration - Lei Zhang; Siyu Liu; Yanjia Wang; Fangwei Zhang; Qiuyu Luo; Yongbiao Lin; Dafeng Hui; Shenglei Fu; Jun Wang; Zhanfeng Liu; Ruoyi Lin; Hai Ren; et al. (Journal of Cleaner Production, 2024)

Understory plant diversity supports the delivery of ecosystem multifunctionality on the Loess Plateau: A comparative of plantations and natural forests - Guoliang Sha; Huan Yu; Yuxuan Chen; Kang Ren; Pengcheng Xin; Xin Guo; Jing Xiao; Yanchao Fu (Journal of Environmental Management, 2024)

Surfactant-modified ZnFe2O4/CaOPS porous acid-base bifunctional catalysts for biodiesel production from waste cooking oil and process optimization - Hongyu Fu; Yunxue Xiao; Abulikemu Abulizi; Kenji Okitsu; Yasuaki Maeda; Tiezhen Ren (Journal of Environmental Chemical Engineering, 2024)

Electron transfer mechanism mediated MOF-derived nanoflowers catalyst for promoting peroxymonosulfate activation and ciprofloxacin degradation - Hao Li; Xiangyi Gong; Hua Tong; Fu Feng; Dajung Ren (Journal of Environmental Chemical Engineering, 2024)

HyperDehazing: A hyperspectral image dehazing benchmark dataset and a deep learning model for haze removal - Hang Fu; Ziyan Ling; Genyun Sun; Jinchang Ren; Aizhu Zhang; Li Zhang; Xiuping Jia (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Structural properties and antioxidant capacity of different aminated starch-phenolic acid conjugates - Feng-Kun An; Meng-Yun Li; Hai-Lu Luo; Xing-Long Liu; Zhen Fu; Min-Hong Ren (Food Chemistry, 2024)

Safflower dietary fiber alleviates functional constipation in rats via regulating gut microbiota and metabolism - Jinmei Wang; Mengjie Ren; Lijun Fu; Li Liu; Xiumin Zhang; Yong Sun; Lijun Liu (Food Bioscience, 2024)

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Shell structure impacts Camellia oleifera fruit splitting during dehydration - Pei Yang; Hanyu Fu; Penggeng Sun; Liuyang Ren; Zhaohui Zheng; Jingshen Xu; Lanlan Lv; Qing Liang; Deyong Yang (Food and Bioproducts Processing, 2024)

Occurrence and fate of five representative neonicotinoid insecticides across different wastewater treatment plants and the impact on receiving water bodies - Yuhan Ke; Wanbing Zheng; Di Tian; Siyu Ke; Shuna Fu; Zhe Zhang; Yue Xie; Junyu Zhu; Bangxing Ren; Chao Zhang; Xiaohui Yi; Mingzhi Huang (Environmental Research, 2024)

Elementomics of 32 elements in cord serum depicts the risk of orofacial clefts: A case-control study in Shanxi, China - Jing Wei; Dezheng Fu; Siyu Guo; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Weiping Ye; Aiguo Ren; Shengju Yin (Environmental Pollution, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Integrative experimental and computational analysis of the impact of KGM's polymerization degree on wheat starch's pasting and retrogradation characteristics - Yi Zhao; Juan Wang; Rui He; Yuanyuan Ren; Jin Fu; Yunjun Zeng; Kangyi Zhang; Geng Zhong (Carbohydrate Polymers, 2024)

Development and challenges of emerging biological technologies for algal-bacterial symbiosis systems: A review - Zhijun Ren; Huixue Li; Peng Sun; Ruiyao Fu; Zijia Bai; Guangming Zhang; Li Sun; Yanjie Wei (Bioresource Technology, 2024)

A bounding surface model of methane hydrate-bearing carbonate sand-silt mixtures - Lu Ma; Yuzhe Ren; Jincheng Ren; Shan Chang; Xuemin Zhu; Kaiyu Fu; Huan Ye; Bi Sun (Marine Georesources & Geotechnology, 2024)

Functional characterization of Arabidopsis hydroxynitrile lyase in response to abiotic stress and the regulation of flowering time - Lei Xue; Duo Bu; Jiangyan Fu; Zhe Zhou; Meng Gao; Ren Wang; Sheng Xu (Molecular Biology Reports, 2024)

The hepatoprotective effect of sodium butyrate on hepatic inflammatory injury mediated by the NLRP3 inflammatory pathway in subchronic fluoride-exposed mice - Wen Li; Zhiyu Ma; Cuijing Su; Funing Liu; Nan Yan; Xiaoxu Duan; Zhenxiang Sun; Hongbo Wang; Yufei Ma; Zhengdong Wang; Fu Ren (Molecular Biology Reports, 2024)

Whether hypoxia tolerance improved after short-term fasting is closely related to phylogeny but not to foraging mode in freshwater fish species - Ke-Ren Huang; Qian-Ying Liu; Yong-Fei Zhang; Yu-Lian Luo; Cheng Fu; Xu Pang; Shi-Jian Fu (Journal of Comparative Physiology B, 2024)

Effect of nitrogen and phosphorus level on growth, development and biochemical composition of Neoporphyra haitanensis conchocelis - Xiujuan Wang; Xing Ren; Hui Zhu; Donghuan Fu; Peng Zhang; Yubo Wu (New Zealand Journal of Marine and Freshwater Research, 2024)
Neoporphyra haitanensis is an important economic alga. A 3 × 2 factorial layout containing three nitrogen levels (1, 5, 10 mg L −1 ) and two phosphorus levels (1, 5 mg L −1 ) were designed to examine the effect of nitrogen and phosphorus levels on physiological responses of N. haitanensis conchocelis during growth phase (trial I) and development phase (trial II). In trial I, a higher phosphorus concentration inhibited the relative growth rate of N. haitanensis conchoceli at each nitrogen level. Contents of chlorophyll a and carotenoids were higher at high nitrogen level. Contents of phospholipids were higher at high phosphorus concentration at 5 mg L −1 nitrogen level. In trial II, high phosphorus concentration increased the formation of conchosporangia at 1 mg L −1 nitrogen level. Higher contents of phycoerythrin and phycocyanin were at high nitrogen level. Higher contents of phospholipids were at high phosphorus concentration at 1 mg L −1 nitrogen level. Higher contents of triglycerides were at low nitrogen level both in trial I and II. These results indicated that high nitrogen level increased the contents of pigment. High phosphorus level favoured the formation of conchosporangia and deposition of phospholipids. These results lay the groundwork for research into mechanism of growth and development of N. haitanensis .

The role of mitochondrial dysfunction in the association between trace metals and QTc prolongation in the aged population - Jiahui Wang; Peiyi Liu; Yankui Lin; Xia Zhang; Lingling Lin; Fengqi Wu; Ying Fu; Desheng Wu; Xiaohu Ren; Haiyan Huang; Xifei Yang; Jianjun Liu (Science of The Total Environment, 2024)

Tower-based profiles of wintertime secondary organic aerosols in the urban boundary layer over Guangzhou - Yao Li; Hong Ren; Shengzhen Zhou; Chenglei Pei; Min Gao; Yuxuan Liang; Dian Ye; Xijing Sun; Fenghua Li; Jun Zhao; Jian Hang; Shaojia Fan; et al. (Science of The Total Environment, 2024)

Mechanisms and characterization of interzone mass transfer inhomogeneity in PEM fuel cells - Huicui Chen; Enyang Shi; Ruirui Zhang; Peng Ren; He Wang; Zijing Zhu; Xi Fu; Pucheng Pei (Chemical Engineering Journal, 2024)

Effects of tourmaline on the establishment, idling, and recovery of partial nitrification: Mechanistic understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Baojian Jing; Jue Wang; Mengqi Fu; Mengxuan Deng; Shuoqi Ren; Zhongqi Jiang; Fengxia Deng; Shan Qiu (Chemical Engineering Journal, 2024)

A skin-inspired anisotropic multidimensional sensor based on low hysteresis organohydrogel with linear sensitivity and excellent robustness for directional perception - Shengnan Li; Zibo Xiao; Hailong Yang; Canjie Zhu; Guoqi Chen; Jingxia Zheng; Jiayuan Ren; Wenquan Wang; Yang Cong; Luqman Ali Shah; Jun Fu (Chemical Engineering Journal, 2024)

Dynamic Mechanical Properties and Constitutive Model of Coal Rock Under Direct Tension - Hui Zhou; Huiqi Ren; Quanmin Xie; Hongen Zhang; Qiang Fu; Chaomin Mu (Rock Mechanics and Rock Engineering, 2024)

Study on Elastoplastic Damage Constitutive Model and Permeability Evolution Law of Gas-Bearing Coal - Jiale Fu; Bobo Li; Chonghong Ren; Qiaoyun Cheng; Pingping Ye; Sandong Zhou (Rock Mechanics and Rock Engineering, 2024)

Limited Sea Surface Temperature Cooling Due to the Barrier Layer Promoting Super Typhoon Mangkhut (2018) - Huipeng Wang; Jiagen Li; Junqiang Song; Liang Sun; Fu Liu; Han Zhang; Kaijun Ren; Huizan Wang; Chunming Wang; Jinrong Zhang; Hongze Leng (Advances in Atmospheric Sciences, 2024)

A new split-ring protoilludane-type sesquiterpenoid and prenylated aromatic compounds from Coriolopsis trogii - Xin-Meng Zhai; Lu-Lu Wang; Ning Li; Fu-Cai Ren (Phytochemistry Letters, 2024)

Experimental study on the elastic response characteristics of a rotating body under an oblique water impact load - Shao-Bo Li; Fu-Ren Ming; Tong-Shuai Peng; Yu-Tong Sui (Ocean Engineering, 2024)

Impacts of chloride ions on the electrochemical decomplexation and degradation of Cr(III)-EDTA: Reaction mechanisms of HO• and RCS - Shujie Zheng; Jiani Yao; Ying Huang; Jiaqi Ren; Yang Hou; Bin Yang; Lecheng Lei; Jianjie Fu; Abdulaziz Al-Anazi; Guibin Jiang; Zhongjian Li (Journal of Hazardous Materials, 2024)

The preparation and characterization of WS2 nanomaterials with different morphologies and the mechanistic study of peroxymonosulfate activation for phenol degradation - Xuechang Ren; Zhenyu Yang; Xuchuang Pang; Hongjin Chen; Ning Fu (Journal of Environmental Chemical Engineering, 2024)

Does risk preference matter to consumers’ willingness to pay for functional food: Evidence from lab experiments using the eye-tracking technology - Shihang Zhen; Xianli Xia; Luchen Huang; Yihan Cao; Hanliang Fu; Yanjun Ren (Food Quality and Preference, 2024)

Greenhouse gas emissions during the rice season are reduced by a low soil C:N ratio using different upland-paddy rotation systems - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Chunlian Jin; Wenwen Song; Fei Deng; Xiaolong Lei; Youfeng Tao; et al. (Field Crops Research, 2024)

Emulation and detection of physical faults and cyber-attacks on building energy systems through real-time hardware-in-the-loop experiments - Guowen Li; Lingyu Ren; Ojas Pradhan; Zheng O’Neill; Jin Wen; Zhiyao Yang; Yangyang Fu; Mengyuan Chu; Jiajing Huang; Teresa Wu; K. Selcuk Candan; Veronica Adetola; et al. (Energy and Buildings, 2024)

Size-modulated Pt nanoparticles for low-temperature plasmon-enhanced hydrogen production from aqueous phase reforming of methanol - Naiwei Fu; Ruiyi Wang; Xianmo Gu; Yunwei Wang; Jun Ren; Zhanfeng Zheng (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Tailored GO nanosheets for porous framework to high CO2 adsorption - Zhi-Jie Liu; Wen-Hai Zhang; Ming-Jie Yin; Yun-Han Ren; Quan-Fu An (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Organosilica with tunable pore structure and antibacterial activity for intelligent humidity control - Jin-Wei Liu; Tao Fu; Yang He; Liang-Jie Wang; Ke-Ren Ding; Hua-Zhang Zhao (Chemical Engineering Journal, 2024)

A deep learning model incorporating frequency domain information for ultra multi-step air pollutant forecasting: A case study of Shanghai - Hai-chao Huang; Hong-di He; Qing-yan Fu; Jun Pan; Zhong-ren Peng (Atmospheric Pollution Research, 2024)

Current trends and perspectives on aquatic-derived protein: A focus on structure-technofunctional properties relationship and application for food preservation - Jingxuan Zhou; Qiaohui Feng; Huixian Fu; Kun Ren; Wenting Shang; Chuan Li; Xiaoshuan Zhang; Thi Tuyet Nga MAI; Yanfu He (Trends in Food Science & Technology, 2024)

Tick saliva interference with LTβR signaling facilitates the transmission of Lyme disease spirochetes - Lin Jin; Bao-Gui Jiang; Yizhu Yin; Jingya Guo; Jia-Fu Jiang; Xiaopeng Qi; Gary Crispell; Shahid Karim; Wu-Chun Cao; Ren Lai (Toxicon, 2024)

Quintom cosmology and modified gravity after DESI 2024 - Yuhang Yang; Xin Ren; Qingqing Wang; Zhiyu Lu; Dongdong Zhang; Yi-Fu Cai; Emmanuel N. Saridakis (Science Bulletin, 2024)

Root activity and rhizospheric bacteria in response to nitrogen management in rice (Oryza sativa L.) - Kuanyu Zhu; Jiangyao Fu; Yajun Zhang; Weicheng Ren; Weiyang Zhang; Junfei Gu; Yunji Xu; Hao Zhang; Zhiqin Wang; Lijun Liu; Jianhua Zhang; Jianchang Yang (European Journal of Agronomy, 2024)

Built-in electric field construction and lattice oxygen activation for boosting alkaline electrochemical water/seawater oxidation - Xinyu Wang; Xu Yu; Pinyi He; Guohui Yang; Fu Qin; Yongkang Yao; Lili Ren (Chemical Engineering Journal, 2024)

Skin-inspired ultra-tough, self-healing anisotropic wood-based electronic skin for multidimensional sensing - Yongyue Zhang; Zongying Fu; Tong Wu; Bohua Ren; Jiaxing Chen; Feifan Xie; Weiqi Leng; Jiangtao Shi; Yun Lu (Chemical Engineering Journal, 2024)

Identification of stripe rust resistance gene YrBDT in Chinese landrace wheat Baidatou using BSE-seq and BSR-seq - Jingchun Wu; Yukun Cheng; Weihao Hao; Bin Bai; Luping Fu; Yan Ren; Yuanfeng Hao; Fengju Wang; Ruiming Lin; Hongqi Si; Chuanxi Ma; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

Discovery and Exploration of Lipid-Modifying Drug Targets for ALS by Mendelian Randomization - Zheng Jiang; Xiao-Jing Gu; Wei-Ming Su; Qing-Qing Duan; Kang-Fu Yin; Yan-Lin Ren; Yi Wang; Bei Cao; Yong-Ping Chen (Molecular Neurobiology, 2024)

Prediction of arsenic and fluoride in groundwater of the North China Plain using enhanced stacking ensemble learning - Wengeng Cao; Zhuo Zhang; Yu Fu; Lihua Zhao; Yu Ren; Tian Nan; Huaming Guo (Water Research, 2024)

Experimental investigation on hydrodynamic characteristics of water intake riser undergoing vortex-induced vibration in uniform flow - Yingli Bai; Mengmeng Zhang; Shixiao Fu; Yuwang Xu; Haojie Ren; Jing Wang (Ocean Engineering, 2024)

Synergistic mechanism and toxicity reduction potential in medium-pressure UV/chlorine/TiO2 system for metronidazole removal - Yu-qiong Gao; Xiang-mei Zhong; Xue-ting Ren; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2024)

Evaluation of potential prebiotic activity of a novel fucose-containing trisaccharide prepared from bacterial exopolysaccharides - Mengshi Xiao; Jiayuan Bi; Xinmiao Ren; Xiaodan Fu; Dongyu Li; Rong Li; Haijin Mou (Food Bioscience, 2024)

Molecular-level insight into the origin-dependent adsorption fractionation of dissolved organic matter on ferrihydrite in aquatic environment: Implications for carbon sink in eutrophic lakes - Chengyu Suo; Wensi Zhao; Shasha Liu; Rui Fu; Yi Ren; Yue Qiu; Yuxin Zhang; Zhongqi He; Baoshan Xing; Fengchang Wu (Chemical Engineering Journal, 2024)

Effects of agricultural mulch film on swine manure composting: Film degradation and nitrogen transformation - Zhiqiang Chen; Jie Ren; Zerui Yun; Qinxue Wen; Qiqi Fu; Shan Qiu (Bioresource Technology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Deep Learning Models for Aorta Segmentation in Computed Tomography Images: A Systematic Review And Meta-Analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Kuan-Ting Wu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Journal of Medical and Biological Engineering, 2024)
Purpose This systematic review and meta-analysis was conducted to evaluate the usefulness of deep learning (DL) models for aorta segmentation in computed tomography (CT) images. Methods Adhering to 2020 PRISMA guidelines, we systematically searched PubMed, Embase, and Web of Science for studies published up to March 13, 2024, that used DL models for aorta segmentation in adults’ chest CT images. We excluded studies that did not use DL models, involved nonhuman subjects or aortic diseases (aneurysms and dissections), or lacked essential data for meta-analysis. Segmentation performance was evaluated primarily in terms of Dice scores. Subgroup analyses were performed to identify variations related to geographical location and methodology. Results Our review of 16 studies indicated that DL models achieve high segmentation accuracy, with a pooled Dice score of 96%. We further noted geographical variations in model performance but no significant publication bias, according to the Egger test. Conclusion DL models facilitate aorta segmentation in CT images, and they can therefore guide accurate, efficient, and standardized diagnosis and treatment planning for cardiovascular diseases. Future studies should address the current challenges to enhance model generalizability and evaluate clinical benefits and thus expand the application of DL models in clinical practice.

Saprobic Dothideomycetes from Yunnan, China: introducing a new species, Queenslandipenidiella lingcangensis , and a new host record for Periconia byssoides - Guang-Cong Ren; Er-Fu Yang; Jutamart Monkai; Kandawatte W. T. Chethana; Heng Gui; Antonio Roberto Gomes de Farias (New Zealand Journal of Botany, 2024)

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Microscopic and spectroscopic analysis of atmospheric iron-containing single particles in Lhasa, Tibet - Junyu Chen; Daobin Zhang; Yiran Fu; Jinhu Wang; Xiaomei Cui; Ci-ren Qu-zong; Qiangying Zhang; Chan Jin; Bu Duo (Journal of Environmental Sciences, 2024)

Innovative fertilizer management system maintains higher maize productivity with lower environmental costs in the Loess Plateau region of China - Peng Wu; Hua Huang; Qi Wu; Fu Liu; Liangqi Ren; Zihui Zhang; Benzheng Liu; Guoxia Zhou; Bingbing Cao; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

The effect of quorum sensing on cadmium- and lead-containing wastewater treatment using activated sludge: Removal efficiency, enzyme activity, and microbial community - Taotao Zeng; Liangqin Wang; Xiaoya Ren; Naif Abdullah Al-Dhabi; Haichao Sha; Yusong Fu; Wangwang Tang; Jie Zhang (Environmental Research, 2024)

An efficient photo-Fenton In2O3@FeIn2S4 composite catalyst for tetracycline degradation - Shengyu Jing; Jing Ren; Anhu Wang; Ruolin Cheng; Huagen Liang; Hai Liu; Fu Chen; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Impact of physicochemical properties on biological effects of lipid nanoparticles: Are they completely safe - Ziyi Yuan; Ruyu Yan; Zuyi Fu; Tao Wu; Chaoxiu Ren (Science of The Total Environment, 2024)

Drying stress analysis and cracking prediction of the component of maize based on viscoelastic stress-strain model - Zhaohui Zheng; Liuyang Ren; Weijun Xie; Shuo Wei; Hanyu Fu; Pei Yang; Jingshen Xu; Deyong Yang (Innovative Food Science & Emerging Technologies, 2024)

Effect of protein from endosperm on the structure and gelatinization behavior of corn starch under radio frequency treatment - Liuyang Ren; Zhaohui Zheng; Pei Yang; Hanyu Fu; Jingshen Xu; Weijun Xie; Deyong Yang (Innovative Food Science & Emerging Technologies, 2024)

GC/MS-based untargeted metabolomics reveals the differential metabolites for discriminating vintage of Chenxiang-type baijiu - Na Wang; Lili Zhang; Li Fu; Mei Wang; Hui Zhang; Xiaoyu Jiang; Xiaohui Liu; Zhen Zhang; Xuejiao Ren (Food Research International, 2024)

Three-dimensional fluorescence combined with alternating trilinear decomposition and random forest algorithm for the rapid prediction of species, geographical origin and main components of Glycyrrhizae Radix et Rhizoma (Gancao) - Hengye Chen; Lixue Ren; Yinan Yang; Wanjun Long; Wei Lan; Jian Yang; Haiyan Fu (Food Chemistry, 2024)

Switchable deep eutectic solvent as green and efficient media for liquid-phase microextraction of phenoxyacetic acid herbicides in water and food matrices - Jiaxiao Niu; Yanhui Zhang; Hongbo Li; Xiaoqin Hai; Qingxin Lu; Ruiyu Fu; Tingze Ren; Xiaoli Guo; Xin Di (Food Chemistry, 2024)

Preparation of Fe3O4 magnetic nanomaterials for the enrichment of phosvitin phosphopeptides - Shuze Ren; Songming Li; Mahmoud Abou-Elsoud; Rui Cui; Xing Fu; Xi Huang (Food Bioscience, 2024)

Preparation, structural characterization and rheological properties of a novel fucose-containing exopolysaccharide from Clavibacter michiganensis - Mengshi Xiao; Luying Tang; Xiaodan Fu; Xinmiao Ren; Jiayuan Bi; Jia Wang; Dongyu Li; Qing Kong; Haijin Mou; Changliang Zhu (Food Hydrocolloids, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Optimizing fertilization depth can promote sustainable development of dryland agriculture in the Loess Plateau region of China by improving crop production and reducing gas emissions - Guangzhou Chen; Liangqi Ren; Junying Wang; Fu Liu; Gaoxiang Liu; Hui Li; Peng Zhang; Zhikuan Jia (Plant and Soil, 2024)

Automatic Lung Ventilation Estimation Using Supervoxel Multi-Feature Fusion Combined with CT Image Registration - Meirong Ren; Peng Xue; Yu Fu; Taohui Xiao; Zhili Zhang; Enqing Dong (Journal of Medical and Biological Engineering, 2024)

Phycosphere bacterial disturbance of Saccharina japonica caused by white rot disease relates to seawater nutrients - Chen Ma; Chengxiang Peng; Longwen Fu; Chenggang Ren; Xintian Liu; Zhengyi Liu; Song Qin; Zhihai Zhong (Environmental Science and Pollution Research, 2024)

Novel analysis of food processes by terahertz spectral imaging: A review of recent research findings - Ying Fu; Yuqiao Ren; Da-Wen Sun (Trends in Food Science & Technology, 2024)

The standardized precipitation evapotranspiration index based on cumulative effect attenuation - Wei Pei; Lei Hao; Qiang Fu; Yongtai Ren; Tianxiao Li (Journal of Hydrology, 2024)

Nanoplastic toxicity induces metabolic shifts in Populus × euramericana cv. '74/76' revealed by multi-omics analysis - Liren Xu; Chong Liu; Yachao Ren; Yinran Huang; Yichao Liu; Shuxiang Feng; Xinyu Zhong; Donglin Fu; Xiaohong Zhou; Jinmao Wang; Yujun Liu; Minsheng Yang (Journal of Hazardous Materials, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Long-chain acyl-CoA synthetase 4-mediated mitochondrial fatty acid metabolism and dendritic cell antigen presentation - Yan Li; Wenlong Fu; JinYing Xiang; Yinying Ren; Yuehan Li; Mi Zhou; Jinyue Yu; Zhengxiu Luo; Enmei Liu; Zhou Fu; Bo Liu; Fengxia Ding (Inflammation Research, 2024)

Chemodiversity of organic nitrogen emissions from light-duty gasoline vehicles is governed by engine displacements and driving speed - Huixia Han; Hongxuan Du; Shuang Chen; Yisheng Xu; Lihong Ren; Yu Chen; Yeguang Cai; Kexin Wang; Xinping Yang; Mingliang Fu; Yan Ding; Pingqing Fu (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

Heat storage and release characteristics of a prototype CaCO3/CaO thermochemical energy storage system based on a novel fluidized bed solar reactor - Fuliang Nie; Tianzeng Ma; Qiangqiang Zhang; Zheshao Chang; Ting Ren; Khurshida F. Sayfieva; Mingkai Fu; Xin Li (Journal of Cleaner Production, 2024)

Grafting modification of thin-film composite membrane with quaternary ammonium polyelectrolyte for Mg2+/Li+ separation - Xiaomin Ren; Yingying Chen; Yu Wang; Hongyan Fu; Dan Hu; Xudong Feng (Journal of Environmental Chemical Engineering, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Dynamics of carbon storage driven by land use/land cover transformation in coal mining areas with a high groundwater table: A case study of Yanzhou Coal Mine, China - Yanhua Fu; Yanan He; Wenqi Chen; Wu Xiao; He Ren; Yichen Shi; Zhenqi Hu (Environmental Research, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Robust and ultra-tough lignocellulosic organogel with zipper-like sliding noncovalent nanostructural design: Towards next-generation bio-derived flexible electronics - Haonan Zhang; Yanchen Zhu; Tongtong Fu; Cheng Hao; Yang Huang; Hao Ren; Ning Yan; Huamin Zhai (Chemical Engineering Journal, 2024)

Characteristics of intracloud lightning to cloud-to-ground lightning ratio in thunderstorms over Eastern and Southern China - Yushu Ren; Weixin Xu; Jiaolan Fu (Atmospheric Research, 2024)

Identification and validation of major and stable quantitative trait locus for falling number in common wheat (Triticum aestivum L.) - Zhi Li; Qinyi Luo; Yujie Gan; Xinli Li; Xia Ou; Yawen Deng; Shulan Fu; Zongxiang Tang; Feiquan Tan; Peigao Luo; Tianheng Ren (Theoretical and Applied Genetics, 2024)

Assessing the effects of extreme climate risk on urban ecological resilience in China - Zongrun Wang; Haiqin Fu; Xiaohang Ren (Environmental Science and Pollution Research, 2024)

Two undescribed benzopyran derivatives from Ranunculus sceleratus L. with their in vitro anti-inflammatory activity in lipopolysaccharide-activated RAW 264.7 cells - Zhen Shi; Si-jia Zhou; Qun-lin Zhang; Fu-cai Ren; Shan-shan Cao; Long-kang Cao; Ya-zhong Zhang; Wen-ming Cheng (Natural Product Research, 2024)

Hazards and influence factors of arsenic in the upper pleistocene aquifer, Hetao region, using machine learning modeling - Yu Fu; Wengeng Cao; Tian Nan; Yu Ren; Zeyan Li (Science of The Total Environment, 2024)

Unraveling biological behavior and influence of magnetic iron-based nanoparticles in algal-bacterial systems: A comprehensive review - Zhijun Ren; Ruiyao Fu; Li Sun; Huixue Li; Zijia Bai; Yu Tian; Guangming Zhang (Science of The Total Environment, 2024)

Late Ordovician lingulid brachiopods from the Pingliang Formation (Shaanxi Province, North China): Morphological and ecological implications - Yue Liang; Rao Fu; Yazhou Hu; Fan Liu; Baopeng Song; Mei Luo; Xinyi Ren; Jiayue Wang; Caibin Zhang; Ruisen Fang; Xuan Yang; Lars E. Holmer; et al. (Journal of Asian Earth Sciences, 2024)

Subducted serpentinite contributes to the formation of arc lavas with heavy Mo isotopic compositions - Fu-Qiang Dai; Yi-Xiang Chen; Ren-Xu Chen; Zi-Fu Zhao; Jie Li; Yu Wang (Geochimica et Cosmochimica Acta, 2024)

Investigation on damage-permeability model of dual-porosity coal under thermal-mechanical coupling effect - Pingping Ye; Bobo Li; Chonghong Ren; Haosheng Song; Jiale Fu; Xuehai Wu (Gas Science and Engineering, 2024)

Defective copper-based metal-organic frameworks for the efficient extraction of organosulfur compounds from garlic-processing wastewater - Xin Sun; Quanbin Fu; Jun Ren; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Xuguang Qiao (Food Chemistry, 2024)

Light on multi-mode optical properties of carbon dots through rational surface engineering tuning strategies - Runfang Pei; Pinyi He; Fu Qin; Jianlong Ma; Cuixing Xu; Libo Qin; Wei Gao; Chun Han; Xinyu Wang; Xu Yu; Jianliang Bai; Zhijun Wang; et al. (Chemical Engineering Journal, 2024)

Analysis of spring drought in Northeast China from the perspective of atmosphere, snow cover, and soil - Wei Pei; Lei Hao; Qiang Fu; Hui Liu; Yongtai Ren; Tianxiao Li (CATENA, 2024)

Genome‑wide Identification, Evolutionary and Expression Analyses of CrRLK1L Gene Family in Peanut (Arachis hypogaea L.) - Qinghua Qiao; Xuezhen Fu; Zhenxin Ren; Wei Qiao; Dong Xiao; Longfei He (Tropical Plant Biology, 2024)

Feeding experience on hairy vetch induces a loss of host-specific adaptation to maize and changes in the gut microbiota communities of the fall armyworm - Lin Ma; Dao-Tong Wang; Qi-Lin Ren; Lei Zhang; Yun-Xia Cheng; Xing-Fu Jiang (Journal of Pest Science, 2024)

Observing eddy dye patches induced by shear instabilities in the surf zone on a plane beach - Chunping Ren; Nannan Fu; Chong Yu; Yuchuan Bai; Kezhao Fang (Acta Oceanologica Sinica, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

A Data-Driven Approach to Identify Major Air Pollutants in Shanghai Port Area and Their Contributing Factors - Xing-Zhou Li; Zhong-Ren Peng; Qingyan Fu; Qian Wang; Jun Pan; Hongdi He (Journal of Marine Science and Engineering, 2024)
Air pollution is a growing concern in metropolitan areas worldwide, and Shanghai, as one of the world’s busiest ports, faces significant challenges in local air pollution control. Assessing the contribution of a specific port to air pollution is essential for effective environmental management and public health improvement, making the analysis of air pollution contributions at a selected port in Shanghai a pertinent research focus. This study aims to delve into the distribution patterns of atmospheric pollutants in port areas and their influencing factors, utilizing a data-driven approach to unveil the relationship between pollution sources and dispersion. Through a comparative analysis of pollution levels in the port’s interior, surrounding regions, and urban area concentrations, we ascertain that carbon monoxide (CO) and nitric oxide (NO) are the primary pollutants in the port, with concentrations significantly exceeding those of the surrounding areas and urban area levels. These two pollutants exhibit an hourly pattern, with lower levels during the day and higher concentrations at night. Employing a random forest model, this study quantitatively analyzes the contribution rates of different factors to pollutant concentrations. The results indicate that NO concentration is primarily influenced by operational intensity and wind speed, while CO concentration is mainly affected by meteorological factors. Further, an orthogonal experiment reveals that maintaining daily operational vehicle numbers within 5000 effectively controls NO pollution, especially at low wind speeds. Additionally, humidity and temperature exhibit similar trends in influencing NO and CO, with heightened pollution occurring within the range of 75% to 90% humidity and 6 °C to 10 °C temperature. Severe pollution accumulates under stagnant wind conditions with wind speeds below 0.2 m/s. The results help to explore the underlying mechanisms of port pollution further and use machine learning for early pollution prediction, aiding timely warnings and emission reduction strategy formulation.

Interactive image segmentation based field boundary perception method and software for autonomous agricultural machinery path planning - Hao Wang; Zhifeng Ma; Yaxin Ren; Siqi Du; Hao Lu; Yehua Shang; Shupeng Hu; Guangqiang Zhang; Zhijun Meng; Changkai Wen; Weiqiang Fu (Computers and Electronics in Agriculture, 2024)

Examining active travel behavior through explainable machine learning: Insights from Beijing, China - Ganmin Yin; Zhou Huang; Chen Fu; Shuliang Ren; Yi Bao; Xiaolei Ma (Transportation Research Part D: Transport and Environment, 2024)

Genomic evidence for climate-linked diversity loss and increased vulnerability of wild barley spanning 28 years of climate warming - Yu Zhou; Ruilian Song; Eviator Nevo; Xiaoqin Fu; Xiaofang Wang; Yixiang Wang; Chengyang Wang; Junpeng Chen; Genlou Sun; Dongfa Sun; Xifeng Ren (Science of The Total Environment, 2024)

Nitrate transformation and source tracking of rivers draining into the Bohai Sea using a multi-tracer approach combined with an optimized Bayesian stable isotope mixing model - Xinwei Ren; Fu-Jun Yue; Jianhui Tang; Cai Li; Si-Liang Li (Journal of Hazardous Materials, 2024)

Degradation of pharmaceuticals in UV/H2O2 process: EEM-based kinetic model, transformation products and corresponding toxicity evaluation - Shaoting Lei; LinChang Guan; Fu Liu; Qingmiao Yu; Ke Xu; Hongqiang Ren; Jinju Geng (Journal of Environmental Chemical Engineering, 2024)

An ultra-thin nickel electrodeposited stainless steel mesh with superhydrophobic property and high mechanical durability for oil-water separation - Xin Zhang; Chuanbo Hu; Xinye Fu; Si Zhang; Tingzhen Li; Beiyue Ma; Kangning Ren (Journal of Environmental Chemical Engineering, 2024)

Experimental study on the regulation of NOX in co-pyrolysis of maize straw and woody biomass - Yongkun Fu; Yaohong Yu; Jinglun Qiang; Yun Deng; Sihao Ren; Hussien Elshareef; Huan Li; Renjie Dong; Yuguang Zhou (Fuel, 2024)

A colorimetric and phosphorescent dual-mode nanosensing platform for the sensitive detection of tobramycin in dairy products - Songlin Liu; Mina Wang; Hui Deng; Xin Deng; Ying Xiong; Qian Wen; Wang Li; Jiali Ren; Xiangjin Fu; Yanni Chen (Food Bioscience, 2024)

Substituting readily available nitrogen fertilizer with controlled-release nitrogen fertilizer improves crop yield and nitrogen uptake while mitigating environmental risks: A global meta-analysis - Yajun Zhang; Weichen Ren; Kuanyu Zhu; Jiangyao Fu; Weilu Wang; Zhiqin Wang; Junfei Gu; Jianchang Yang (Field Crops Research, 2024)

Effective degradation of phenol by activating PMS with bimetallic Mo and Ni Co-doped g C3N4 composite catalyst: A Fenton-like degradation process promoted by non-free radical 1O2 - Miao Tian; Xuechang Ren; Suying Ding; Ning Fu; Yajun Wei; Zhenyu Yang; Xiaoqing Yao (Environmental Research, 2024)

Collagen-derived peptides as prebiotics to improve gut health - Baojing Ren; Kaiyan Yue; Yuhao Zhang; Yu Fu (Current Opinion in Food Science, 2024)

Manganese doped hollow cobalt oxide catalysts for highly efficient oxygen evolution in wide pH range - Jing-Yi Xie; Fu-Li Wang; Xue-Jun Zhai; Xin Li; Yu-Sheng Zhang; Ruo-Yao Fan; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Harsh environment resistible and recyclable thermoplastic polyurea adhesive based on stable and density hydrogen bonds - Dongqi Wang; Kai Yang; Sisi Cheng; Meishan Fu; Zhihong Wang; Lixia Li; Xin Zhao; Lijing Han; Wenzhi Ren; Fang Yang; Ruoyu Zhang (Chemical Engineering Journal, 2024)

Synergetic construction of color and multifunction for sustainable lyocell fabric by microbial nano pigment - Jing Wu; Ranran Fu; Maochang Xiao; Qiumeng Zheng; Lin Wu; Kuanjun Fang; Yanfei Ren (Chemical Engineering Journal, 2024)

Superior toughness Anticorrosion-Bioactive integrated multilayer coating with excellent adhesion for biodegradable Magnesium-Based stents - Jiayi Zhang; Zhen Xiang; Xingrong Ren; Bo Zhang; Daihua Fu; Yunbing Wang (Chemical Engineering Journal, 2024)

Transformation and aging of organic matter during degradation and preservation in marine sediment of the northern South China Sea - Fuqiang Wang; Xu Tian; Weikun Xu; Wenjing Fu; Peng Ren; Chunle Luo; Hongmei Zhang; Honghua Shi; Xuchen Wang (Chemical Geology, 2024)

Biochar induces different responses of intracellular and extracellular antibiotic resistance genes and suppresses horizontal transfer during lincomycin fermentation dregs composting - Mengmeng Wang; Chenhao Wang; Jie Yang; Xiangyu Liu; Binghan Xie; Peng Ren; Xiaowei Kong; Yunxia Fu (Bioresource Technology, 2024)

Long-term impact of nano zero-valent iron on methanogenic activity, microbial community structure, and transcription activity in anaerobic wastewater treatment system - Runhua Su; Huimin Fu; Lili Ding; Bo Fu; Su He; Haijun Ma; Haidong Hu; Hongqiang Ren (Bioresource Technology, 2024)

Fabrication of shaping catalyst SO42−/SnO2-RC for high efficient and continuous synthesis of trimethylolpropane oleate in fixed bed reactor - Jinhua Liang; Zihan Wei; Xiaotong Li; Rongcheng Xiang; Wenya Fu; Xiaorui Yang; Wenlong Xu; Jianliang Zhu; Xiaoqian Ren (Biomass and Bioenergy, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Transcriptome analysis of foxtail millet inflorescence tissue in response to Sclerospora graminicola infection - Yurong Sun; Zhenxin Fu; Xue Wang; Zhixian Ren; Jinye Wang; Yanqing Han; Yuanhuai Han; Baojun Zhang; Fan Mu (Physiological and Molecular Plant Pathology, 2024)

Efficient recovery of vanadium from calcification roasted-acid leaching tailings enhanced by ultrasound in H2SO4-H2O2 system - Haoyu Li; Qian Ren; Jinfeng Tian; Shihong Tian; Jun Wang; Xuejun Zhu; Yuanhong Shang; Jiayuan Liu; Liping Fu (Minerals Engineering, 2024)

Reversible, ultra-strong underwater adhesive based on supramolecular interaction for instant liquid leakage sealing and robust tissue adhesion - Hailong Yang; Wenquan Wang; Canjie Zhu; Guoqi Chen; Jingxia Zheng; Shengnan Li; Jiayuan Ren; Jun Fu (Chemical Engineering Journal, 2024)

Relationships between structural design and synthesis engineering of Cu-based catalysts for CO2 to C2 electroreduction - Zichen Song; Xiaolei Wang; Zhiyu Ren; Honggang Fu (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Strain-insensitive and multiplexed potentiometric ion sensors via printed PMMA molecular layer - Quansheng Lu; Yun Wang; Yu Lu; Yiping Ren; Ran Fu; Wenbin Chen; Guan Jiang (Analytica Chimica Acta, 2024)

Effects of aridification on soil total carbon pools in China's drylands - Zhuobing Ren; Changjia Li; Bojie Fu; Shuai Wang; Lindsay C. Stringer (Global Change Biology, 2024)
Drylands are important carbon pools and are highly vulnerable to climate change, particularly in the context of increasing aridity. However, there has been limited research on the effects of aridification on soil total carbon including soil organic carbon and soil inorganic carbon, which hinders comprehensive understanding and projection of soil carbon dynamics in drylands. To determine the response of soil total carbon to aridification, and to understand how aridification drives soil total carbon variation along the aridity gradient through different ecosystem attributes, we measured soil organic carbon, inorganic carbon and total carbon across a ~4000 km aridity gradient in the drylands of northern China. Distribution patterns of organic carbon, inorganic carbon, and total carbon at different sites along the aridity gradient were analyzed. Results showed that soil organic carbon and inorganic carbon had a complementary relationship, that is, an increase in soil inorganic carbon positively compensated for the decrease in organic carbon in semiarid to hyperarid regions. Soil total carbon exhibited a nonlinear change with increasing aridity, and the effect of aridity on total carbon shifted from negative to positive at an aridity level of 0.71. In less arid regions, aridification leads to a decrease in total carbon, mainly through a decrease in organic carbon, whereas in more arid regions, aridification promotes an increase in inorganic carbon and thus an increase in total carbon. Our study highlights the importance of soil inorganic carbon to total carbon and the different effects of aridity on soil carbon pools in drylands. Soil total carbon needs to be considered when developing measures to conserve the terrestrial carbon sink.

Effect of glass transition on the formation of drying cracks in the component parts of maize kernels - Zhaohui Zheng; Liuyang Ren; Hanyu Fu; Pei Yang; Lanlan Lv; Jingshen Xu; Deyong Yang (Biosystems Engineering, 2023)

Chlorpyrifos induces placental oxidative stress and barrier dysfunction by inducing mitochondrial apoptosis through the ERK/MAPK signaling pathway: In vitro and in vivo studies - Jun Bai; Siwei Deng; Huiyang Fu; Qing Yang; Fazheng Ren; Shenming Zeng; Zhaohui Chen; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2023)

Long-term grazing improved soil chemical properties and benefited community traits under climatic influence in an alpine typical steppe - Yu-Wen Zhang; Ze-Chen Peng; Sheng-Hua Chang; Zhao-Feng Wang; Duo-Cai Li; Yu-Feng An; Fu-Jiang Hou; Ji-Zhou Ren (Journal of Environmental Management, 2023)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Analyzing the effects of nonthermal pretreatments on the quality of microwave vacuum dehydrated beef using terahertz time-domain spectroscopy and near-infrared hyperspectral imaging - Yuqiao Ren; Ying Fu; Da-Wen Sun (Food Chemistry, 2023)

Phenylalanine diminishes M1 macrophage inflammation - Qingzhuo Zhang; Siyuan Chen; Yan Guo; Fang He; Jian Fu; Wenkai Ren (Science China Life Sciences, 2023)

Budget of atmospheric nitrous acid (HONO) during the haze and clean periods in Shanghai: Importance of heterogeneous reactions - Jialiang Feng; Ensi Ren; Ming Hu; Qingyan Fu; Yusen Duan; Cheng Huang; Yue Zhao; Shunyao Wang (Science of The Total Environment, 2023)

All-in-one self-floating porous foams as robust heat-blocking layers for efficient photothermal conversion and solar desalination - Liping Ren; Wei Zhou; Lei Wang; Kuo Lin; Yachao Xu; Jiaxing Wu; Ying Xie; Honggang Fu (Science Bulletin, 2023)

Characterization and function of Japanese flounder (Paralichthys olivaceus) slc2a6 in response to lymphocystis disease virus infection - Yucong Yang; Yitong Zhang; Yuqin Ren; Zhongwei He; Wei Cao; Yufeng Liu; Jiangong Ren; Yufen Wang; Guixing Wang; Yuanshuai Fu; Jilun Hou (Fish & Shellfish Immunology, 2023)

Biomimetic anode with atomically dispersed iron sites to enhance biotic-abiotic interfacial interaction towards efficient wastewater energy recovery in bioelectrochemical systems - Mengxi Yin; Boya Fu; Tengfei Ren; Mingwei Wang; Xiaoxin Cao; Xia Huang; Xiaoyuan Zhang (Chemical Engineering Journal, 2023)

DBC2 Attenuates the Stemness of CD44 Positive Gastric cancer Stem Cells by Suppressing Notch1 Signaling Pathway - Pu Xia; Da-Hua Liu; Fu Ren (Stem Cell Reviews and Reports, 2023)

Gut microbiota bridges dietary nutrients and host immunity - Lijuan Fan; Yaoyao Xia; Youxia Wang; Dandan Han; Yanli Liu; Jiahuan Li; Jie Fu; Leli Wang; Zhending Gan; Bingnan Liu; Jian Fu; Congrui Zhu; et al. (Science China Life Sciences, 2023)

Investigation of Physics-Informed Neural Networks to Reconstruct a Flow Field with High Resolution - Zhou Yang; Yuwang Xu; Jionglin Jing; Xuepeng Fu; Bofu Wang; Haojie Ren; Mengmeng Zhang; Tongxiao Sun (Journal of Marine Science and Engineering, 2023)
Particle image velocimetry (PIV) is a widely used experimental technique in ocean engineering, for instance, to study the vortex fields near marine risers and the wake fields behind wind turbines or ship propellers. However, the flow fields measured using PIV in water tanks or wind tunnels always have low resolution; hence, it is difficult to accurately reveal the mechanics behind the complex phenomena sometimes observed. In this paper, physics-informed neural networks (PINNs), which introduce the Navier–Stokes equations or the continuity equation into the loss function during training to reconstruct a flow field with high resolution, are investigated. The accuracy is compared with the cubic spline interpolation method and a classic neural network in a case study of reconstructing a two-dimensional flow field around a cylinder, which is obtained through direct numerical simulation. Finally, the validated PINN method is applied to reconstruct a flow field measured using PIV and shows good performance.

The effects of earthworm inoculation on cadmium-contaminated rice field in Southern China: a pot experiment and a field test - Yin Zhang; Chunyun Guan; Can Chen; Zhiqiang Fu; Ren Wang; Quan Zhang; Zhengjun Yu; Huang Huang (Environmental Science and Pollution Research, 2023)

Geolocated social media data for measuring park visitation in Shenzhen, China - Langjiao Li; Qingyun Du; Fu Ren; Lei Huang; Mihai Voda; Pengfei Ning (Urban Forestry & Urban Greening, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Modeling potential arsenic enrichment and distribution using stacking ensemble learning in the lower Yellow River Plain, China - Wengeng Cao; Yu Fu; Yanpei Cheng; Wenhua Zhai; Xiaoyue Sun; Yu Ren; Deng Pan (Journal of Hydrology, 2023)

Urinary essential and toxic metal mixtures, and type 2 diabetes mellitus: Telomere shortening as an intermediary factor? - Duo Zhang; Xiao Chen; Ke Huang; Quanzhi Zheng; Ying Fu; Jiaojiao Ma; Xiaohu Ren; Benhong Xu; Peiyi Liu; Jianjun Liu; Shaoyou Lu (Journal of Hazardous Materials, 2023)

Interfacial polymerization process based on diffusion control: Role of chemical composition and morphology on fouling resistance - Xiaomin Ren; Lingxuan Wang; Hongyan Fu; Yu Wang; Dan Hu; Xudong Feng (Journal of Environmental Chemical Engineering, 2023)

Spherical-like Mo2C/ZnIn2S4 heterojunctions with boosting photo-carriers separation for effective tetracycline removal in water via synergistic adsorption and photocatalytic process - Gang Wu; Fu Liu; Maoqing Tian; Xionghui Deng; Xuxiang Zhang; Hongqiang Ren; Jinju Geng (Journal of Environmental Chemical Engineering, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

4D printing of biomimetic anisotropic self-sensing hydrogel actuators - Shengnan Li; Hailong Yang; Guoqi Chen; Jingxia Zheng; Wenquan Wang; Jiayuan Ren; Canjie Zhu; Yabin Yang; Yang Cong; Jun Fu (Chemical Engineering Journal, 2023)

Electrospun Ce–Mn oxide as an efficient catalyst for soot combustion: Ce–Mn synergy, soot-catalyst contact, and catalytic oxidation mechanism - Yuxi Liao; Peng Liu; Jun Zhang; Can Wang; Longwen Chen; Dengfeng Yan; Quanming Ren; Xiaoliang Liang; Mingli Fu; Suib Steven L.; Daiqi Ye (Chemosphere, 2023)

A visual circuit related to the habenula mediates the prevention of cocaine relapse by bright light treatment - Yunwei Fu; Yan Yang; Lu Huang; Xiaodan Huang; Qian Yang; Qian Tao; Jijin Wu; Kwok-Fai So; Song Lin; Ti-Fei Yuan; Chaoran Ren (Science Bulletin, 2023)

Estimating soil water retention curves from thermal conductivity measurements: A percolation-based effective-medium approximation - Yongwei Fu; Lin Liu; Yili Lu; Robert Horton; Tusheng Ren; Joshua Heitman (Journal of Hydrology, 2023)

Three-dimensional singular spectrum analysis for precise land cover classification from UAV-borne hyperspectral benchmark datasets - Hang Fu; Genyun Sun; Li Zhang; Aizhu Zhang; Jinchang Ren; Xiuping Jia; Feng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Structural characterization of a novel fucosylated trisaccharide prepared from bacterial exopolysaccharides and evaluation of its prebiotic activity - Mengshi Xiao; Xinmiao Ren; Jiaying Cheng; Xiaodan Fu; Rong Li; Changliang Zhu; Qing Kong; Haijin Mou (Food Chemistry, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

The sensitivity of a mid-latitude maritime stratocumulus cloud to surface fluxes - Yangze Ren; Shizuo Fu; Huiwen Xue (Atmospheric Research, 2023)

Analysis of seismic escape accessibility and risk in old community with unreinforced masonry buildings - Meiling Xiao; Jianbin Xie; Cuilin Liu; Haiyan Zhu; Yong Zhu; Yujie Fu; Jun Ren (Stochastic Environmental Research and Risk Assessment, 2023)

Early-Middle Devonian adakitic magmatism generated by slab retreat in southern West Junggar, NW China: implications for tectonic correlation with central and East Kazakhstan - Rong Ren; Bo Liu; Bao-Fu Han; Shu-Wei Guan (International Geology Review, 2023)

Co-exposure to parabens and triclosan and associations with cognitive impairment in an elderly population from Shenzhen, China - Xiaohu Ren; Yilan Deng; Wei Liu; Jinfeng Fu; Zhihong Huang; Duo Zhang; Qinru Xiao; Xiangyu Li; Xiao Chen; Xinfeng Huang; Jianjun Liu; Shaoyou Lu (Chemosphere, 2023)

Effect of aeration/micro-aeration on lignocellulosic decomposition, maturity and seedling phytotoxicity during full-scale biogas residues composting - Xingyao Meng; Qingping Wang; Xixi Zhao; Yafan Cai; Jingyi Fu; Mingcheng Zhu; Xuguang Ma; Pan Wang; Rufei Liu; Yongjing Wang; Wei Liu; Lianhai Ren (Waste Management, 2023)

Design, synthesis and biological activity of novel triketone herbicides containing natural product fragments - Zi-Bin Jiang; Shuang Gao; Wei Hu; Bo-Ren Sheng; Juan Shi; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

Depth-driven responses of microbial residual carbon to nitrogen addition approaches in a tropical forest: Canopy addition versus understory addition - Luhui Kuang; Zhijian Mou; Yue Li; Xiaofei Lu; Yuanwen Kuang; Jun Wang; Faming Wang; Xi'an Cai; Wei Zhang; Shenglei Fu; Dafeng Hui; Hans Lambers; et al. (Journal of Environmental Management, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Mesomechanical characteristics of rock failure under variable amplitude cyclic loading by DEM - Ze-han Liu; Jin Yu; Chong-hong Ren; De-fu Zhu; Xiao-qin Chen (Bulletin of Engineering Geology and the Environment, 2023)

Effect of non-simultaneous movement of adjacent twin-trapdoor on soil arching effect through discrete-element method simulation - Ren-Peng Chen; Xiang-Shen Fu; Qi-Wei Liu; Han-Lin Wang; Fanyan Meng (Transportation Geotechnics, 2023)

A novel Q-learning based variable neighborhood iterative search algorithm for solving disassembly line scheduling problems - Yaxian Ren; Kaizhou Gao; Yaping Fu; Hongyan Sang; Dachao Li; Zile Luo (Swarm and Evolutionary Computation, 2023)

Evaluation the role of soluble microbial products for denitrification sludge characteristic under starvation stress - Qian-Qian Zhang; Yan Yu; Jin-Ze Liu; Wen-Jing Fu; Jin-Yang Quan; Ying Chen; Jian-Qiang Zhao; Sha Wang; Ren-Cun Jin (Science of The Total Environment, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Data-driven collapse strength modelling for the screen pipes with internal corrosion defect based on finite element analysis and tree-based machine learning - Yudan Peng; Guangming Fu; Baojiang Sun; Jiying Chen; Weiguo Zhang; Meipeng Ren; Heen Zhang (Ocean Engineering, 2023)

Enhanced degradation of pharmaceuticals in wastewater by coupled radical and non-radical pathways: Further unravelling kinetics and mechanism - Fu Liu; Hongzhou Li; Shaoting Lei; Qingmiao Yu; Hongqiang Ren; Jinju Geng (Journal of Hazardous Materials, 2023)

Strong photo-thermal coupling effect boosts CO2 reduction into CH4 in a concentrated solar reactor - Lei Xu; Yuqi Ren; Yiwei Fu; Maochang Liu; Fengfan Zhu; Miao Cheng; Jiancheng Zhou; Wenshuai Chen; Ke Wang; Nan Wang; Naixu Li (Chemical Engineering Journal, 2023)

Ionic accelerator based on metal–semiconductor contact for fast electrode kinetics and durable Zn-metal anode - Hao Fu; Yuzhen Liu; Zhuohong Xie; Youjoong Kim; Ren Ren; Woochul Yang; Guicheng Liu (Chemical Engineering Journal, 2023)

Solar radiation utilization of five upland–paddy cropping systems in low-light regions promoted by diffuse radiation of paddy season - Qi Liu; Zhiping Yang; Wei Zhou; Tao Wang; Yong Fu; Xueping Yue; Hong Chen; Youfeng Tao; Fei Deng; Xiaolong Lei; Wanjun Ren; Yong Chen (Agricultural and Forest Meteorology, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Rubochingosides A - J, labdane-type diterpene glycosides from leaves of Rubus chingii - Jianxiong Wang; Xiaowu Xiao; Nian Zhou; Minmin Zhao; Shuqin Lang; Qi Ren; Dong Wang; Huizheng Fu (Phytochemistry, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Study on the taste active compounds in Douchi using metabolomics method - Weidan Guo; Yu Zhang; Zhao Long; Xiangjin Fu; Kangzi Ren (Food Chemistry, 2023)

An oral nano-antioxidant for targeted treatment of inflammatory bowel disease by regulating macrophage polarization and inhibiting ferroptosis of intestinal cells - Jing Yang; Yunhao Bai; Shuilin Shen; Xinyue Tao; Chengyu Ma; Bowen Fu; Qihao Dai; Jian Wu; Zhengjie Meng; Qingmin Sun; Xueming Li; Hao Ren (Chemical Engineering Journal, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Capacitively coupled effect and capacitive decoupling of multichannel controlled-source audio magnetotellurics observations - Da Lei; Qi-hui Zhen; Ruo Wang; Chang-min Fu; Hao Ren (Applied Geophysics, 2023)

Response of Salmonella enterica serovar Typhimurium to alginate oligosaccharides fermented with fecal inoculum: integrated transcriptomic and metabolomic analyses - Jiaying Cheng; Mengshi Xiao; Xinmiao Ren; Francesco Secundo; Ying Yu; Shihao Nan; Weimiao Chen; Changliang Zhu; Qing Kong; Youtao Huang; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2023)
Alginate oligosaccharides (AOS), extracted from marine brown algae, are a common functional feed additive; however, it remains unclear whether they modulate the gut microbiota and microbial metabolites. The response of Salmonella enterica serovar Typhimurium, a common poultry pathogen, to AOS fermented with chicken fecal inocula was investigated using metabolomic and transcriptomic analyses. Single-strain cultivation tests showed that AOS did not directly inhibit the growth of S . Typhimurium. However, when AOS were fermented by chicken fecal microbiota, the supernatant of fermented AOS (F-AOS) exhibited remarkable antibacterial activity against S . Typhimurium, decreasing the abundance ratio of S . Typhimurium in the fecal microbiota from 18.94 to 2.94%. Transcriptomic analyses showed that the 855 differentially expressed genes induced by F-AOS were mainly enriched in porphyrin and chlorophyll metabolism, oxidative phosphorylation, and Salmonella infection-related pathways. RT-qPCR confirmed that F-AOS downregulated key genes involved in flagellar assembly and the type III secretory system of S . Typhimurium, indicating metabolites in F-AOS can influence the growth and metabolism of S . Typhimurium. Metabolomic analyses showed that 205 microbial metabolites were significantly altered in F-AOS. Among them, the increase in indolelactic acid and 3-indolepropionic acid levels were further confirmed using HPLC. This study provides a new perspective for the application of AOS as a feed additive against pathogenic intestinal bacteria.

Exploring the seasonality of surface urban heat islands using enhanced land surface temperature in a semi-arid city - Liying Han; Linlin Lu; Peng Fu; Chao Ren; Meng Cai; Qingting Li (Urban Climate, 2023)

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Gold-silver alloy hollow nanoshells-based lateral flow immunoassay for colorimetric, photothermal, and SERS tri-mode detection of SARS-CoV-2 neutralizing antibody - Tianyu Zhao; Penghui Liang; Jiaqi Ren; Jinyue Zhu; Xianning Yang; Hongyu Bian; Jingwen Li; Xiaofeng Cui; Chunhui Fu; Jinyan Xing; Congying Wen; Jingbin Zeng (Analytica Chimica Acta, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Preparation of a g-C3N4/Ag3PO4 composite Z-type photocatalyst and photocatalytic degradation of Ofloxacin: Degradation performance, reaction mechanism, degradation pathway and toxicity evaluation - Renhua Chen; Suying Ding; Ning Fu; Xuechang Ren (Journal of Environmental Chemical Engineering, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Prediction of column failure modes based on artificial neural network - Haitao Wan; Yongle Qi; Tiejun Zhao; Wenjuan Ren; Xiaoyan Fu (Earthquake Engineering and Engineering Vibration, 2023)

Photoinduced transformation of ferrihydrite in the presence of aqueous sulfite and its influence on the repartitioning of Cd - Jinwen Qiu; Xiaokang Hou; Yuan Ren; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Ziyuan Huang; Huanxin Ma; Zhenqing Shi; Chunhua Feng (Water Research, 2023)

Mechanoluminescent optical fiber sensors for human–computer interaction - Biyun Ren; Bing Chen; Xianhui Zhang; Honglei Wu; Yu Fu; Dengfeng Peng (Science Bulletin, 2023)

A linkage between early Silurian Nb-REE enriched alkaline magmatism and Neoproterozoic subduction metasomatized mantle in South Qinling, Central China - Jian-Hui Su; Xin-Fu Zhao; Xiao-Chun Li; Sheng-Ren Chang; Yuan-Bao Wu; Carl Spandler (Lithos, 2023)

Evidence of aircraft activity impact on local air quality: A study in the context of uncommon airport operation - Hao Xu; Kai Xiao; Jun Pan; Qingyan Fu; Xiaodong Wei; Junrui Zhou; Yamei Yu; Xue Hu; Huarui Ren; Jinping Cheng; Shitao Peng; Ningning Hong; et al. (Journal of Environmental Sciences, 2023)

Discovery of natural polyphenols from the wild vegetable Suaeda salsa L. with potential cardioprotective functions - Kuo Xu; Xinhai Cui; Xia Ren; Jie Meng; Xianjun Fu; Qing Xia (Food Chemistry, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Fitness consequences of oviposition choice by an herbivorous insect on a host plant colonized by an endophytic entomopathogenic fungus - Hui Zhu; Jun Fu; Han Wang; Michael J. Bidochka; Mingyi Duan; Wenjing Xu; Li Sui; Bingzhong Ren; Qiyun Li; Zhengkun Zhang (Journal of Pest Science, 2023)

FAS-mediated circRNA-miRNA-mRNA Crosstalk Network Regulates Immune Cell Infiltration in Cerebral Infarction - Ke Ying; Juan Chen; Zhenhui Fu; Bo Ren (Journal of Molecular Neuroscience, 2023)

Size-Resolved Characteristics and Sources of Inorganic Ions, Carbonaceous Components and Dicarboxylic Acids, Benzoic Acid, Oxocarboxylic Acids and α-Dicarbonyls in Wintertime Aerosols from Tianjin, North China - Subba Rao Devineni; Chandra Mouli Pavuluri; Shuang Wang; Lujie Ren; Zhanjie Xu; Peisen Li; Pingqing Fu; Cong-Qiang Liu (Aerosol Science and Engineering, 2023)

Comparative Transcriptome Analysis Identifies MAPK Signaling Pathway Associated with Regulating Ovarian Lipid Metabolism during Vitellogenesis in the Mud Crab, Scylla paramamosain - Yuanhao Ren; Wei Wang; Yin Fu; Zhiqiang Liu; Ming Zhao; Likun Xu; Tianyong Zhan; Ting Huang; Minghao Luo; Wei Chen; Chunyan Ma; Fengying Zhang; et al. (Fishes, 2023)
The mud crab, Scylla paramamosain, has abundant nutrients in the ovary, where numerous lipids accumulate during ovarian maturation. However, the mechanism behind the accumulation of lipids in the ovary of mud crab during ovarian maturation is largely unknown. This study conducted a comparative transcriptome analysis of the ovaries of mud crabs at various stages of ovarian maturation. A total of 63.69 Gb of clean data was obtained, with a Q30 of 93.34%, and 81,893 unigenes were identified, including 10,996 differentially expressed genes (DEGs). After KEGG enrichment of these DEGs, MAPK signaling pathway was significantly enriched during vitellogenesis. Moreover, the expression levels of genes involved in carbohydrate, amino acid, and lipid metabolism were found to be higher during vitellogenesis. The two genes (Sp-Eip75B and Sp-Eip78C) that are homologous to the vertebrate gene PPARγ in the PPAR signaling pathway, were identified. Additionally, genes in MAPK signaling pathway might regulate lipid metabolism through PPAR signaling pathway based on Protein-Protein Interaction (PPI) network. These findings suggest that MAPK signaling pathway plays a critical role in lipid metabolism in the ovary during vitellogenesis, which provides new insights into the mechanism of lipid accumulation during ovarian maturation in mud crabs.

How anaerobic sludge microbiome respond to different concentrations of nitrite, nitrate, and ammonium ions: a comparative analysis - Runhua Su; Lina Zhou; Lili Ding; Bo Fu; Huimin Fu; Yanan Shuang; Lin Ye; Haidong Hu; Haijun Ma; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

Drag coefficients of double unequal-diameter flexible cylinders in tandem undergoing vortex/wake-induced vibrations - Bing Zhao; Mengmeng Zhang; Shixiao Fu; Xuepeng Fu; Haojie Ren; Yuwang Xu (Ocean Engineering, 2023)

Spatial distribution and controlling mechanisms of high fluoride groundwater in the coastal plain of Bohai Rim, North China - Wengeng Cao; Zhuo Zhang; Huaming Guo; Yu Fu; Zhipeng Gao; Tian Nan; Yu Ren; Zeyan Li (Journal of Hydrology, 2023)

Effects of biofilms on the retention and transport of PFOA in saturated porous media - Jiaju Fu; Bin Gao; Hongxia Xu; Shefeng Hao; Jinghua Ren; Jichun Wu; Yuanyuan Sun (Journal of Hazardous Materials, 2023)

Peroxymonosulfate activation for effective atrazine degradation over a 3D cobalt-MOF: Performance and mechanism - Ya Li; Fei Wang; Xueying Ren; Peng Wang; Fu-Xue Wang; Hong-Yu Chu; Shijie Gao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2023)

Diurnal variations in primary and secondary organic aerosols in an eastern China coastal city: The impact of land-sea breezes - Qiang Zhang; Wei Hu; Hong Ren; Jianbo Yang; Junjun Deng; Dawei Wang; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Environmental Pollution, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

Boosting wastewater bioelectricity recovery via solvent mediation and zinc fencing: Dual regulation for catalyst spatial structure and active sites - Mengxi Yin; Tengfei Ren; Ting Xu; Boya Fu; Xiaoxin Cao; Xia Huang; Xiaoyuan Zhang (Chemical Engineering Journal, 2023)

Mapping knowledge domains for mine heat hazard: a bibliometric analysis of research trends and future needs - Jiale Zhao; Fu-Qiang Yang; Yong Guo; Xin Ren (Environmental Science and Pollution Research, 2023)

Establishment and characterization of a cell line from the brain of the Japanese flounder (Paralichthys olivaceus) and its application in the study of viral infection - Zhaodi Sun; Yuqin Ren; Yitong Zhang; Yucong Yang; Guixing Wang; Zhongwei He; Yufeng Liu; Wei Cao; Yufen Wang; Yuanshuai Fu; Jilun Hou (Aquaculture, 2023)

Transmission characteristics, source apportionment and health risk assessment of PM2.5 in a typical industrial city in Northwest China - Kai Xiao; Xiaoqing Yao; Xuechang Ren; Xi Zhang; Ning Fu; Qiuhong Shi (Urban Climate, 2023)

Occurrence, spatial heterogeneity, and risk assessment of perfluoroalkyl acids (PFAAs) in the major rivers of the Tibetan Plateau - Jiao Ren; Mengjiao Yu; Feng Chen; Liang Cui; Yuzhi Zhang; Junming Li; Mengke Chen; Xiaoping Wang; Jianjie Fu (Science of The Total Environment, 2023)

Anchored growth of highly dispersed LDHs nanosheets on expanded graphite for fluoride adsorption properties and mechanism - Mingming Zheng; Jue Wang; Dong Fu; Binqiao Ren; Xiaoxiao Song; Kan Kan; Xiaochen Zhang (Journal of Hazardous Materials, 2023)

Magnetically controlled super-wetting surface switching between ultra-low and ultra-high droplet adhesion - Limei Tian; Haixu Dou; Yanlong Shao; Yaozhen Yi; Xue Fu; Jie Zhao; Yong Fan; Weihua Ming; Luquan Ren (Chemical Engineering Journal, 2023)

Simultaneous regulation of Li-ion intercalation and oxygen termination decoration on Ti3C2Tx MXene toward enhanced oxygen electrocatalysis for Li-O2 batteries - Shidong Song; Fangfang Yin; Yue Fu; Jiahao Ren; Junjie Ma; Yanan Liu; Run Ma; Wanyu Ye (Chemical Engineering Journal, 2023)

Eco-friendly waterborne superhydrophobic/superoleophilic FEVE composite coating with prolonged mechanochemical and anti-scaling properties - Zhanjian Liu; Lina Ren; Baoshuang Zhang; Jing Jing; Xiguang Zhang; Meiling Li; Yuxin Fu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Scalable anti-infection polyurethane catheters with long-acting and autoclavable properties - Zongpeng Xiu; Meiping Yang; Ruonan Wu; Chengyue Lei; Hui-Min Ren; Bingran Yu; Shuai Gao; Shun Duan; Dimeng Wu; Fu-Jian Xu (Chemical Engineering Journal, 2023)

Study on Agricultural Drought Risk Assessment Based on Information Entropy and a Cluster Projection Pursuit Model - Wei Pei; Lei Hao; Qiang Fu; Yongtai Ren; Tianxiao Li (Water Resources Management, 2023)

Projecting extreme climate events in China’s Loess Plateau: multiple RCMs and emission scenarios corrected by a trend-preserving method - Yuling Ren; Jingpeng Zhang; Bingbing Li; Jinxia Fu; Zhi Li (Theoretical and Applied Climatology, 2023)

The Critical Factors and Preventive Measures of Impoundment of Tailings Using Active Surface Subsidence Zones - Yang Liu; Yanjun Zhou; Rongxing He; Jianli Cao; Fengyu Ren; Fu Yu; Lu Yue (Geotechnical and Geological Engineering, 2023)

Dynamic changes in provincial exhaust emissions in China in the carbon peak and neutrality setting: based on the effects of energy consumption and economic growth - Xiaopeng Guo; Yihan Fu; Dongfang Ren; Xinyue Zhang (Environmental Science and Pollution Research, 2023)

Streptomyces Spinosirectus sp. nov., Isolated From the Medicinal Plant Xanthium Sibiricum - Yin-Feng Wang; Si-Ren Hu; Li Fu; Yan Xiao; Xin-Ke Tang; Jian Gao (Current Microbiology, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Cloning of Two HSP Genes of Eriocheir hepuensis and Their Expression under Vibrio parahaemolyticus Stress - Qianni Fu; Jinxia Liu; Tianjiao Ren; Zining Zhang; Zihang Ma; Zhenyu Lan; Yitao Duan; Ziwei Liang; Boyu Chen; Yan Zhang; Peng Zhu; Yongyan Liao (Fishes, 2022)
Heat shock proteins (HSPs) are molecular chaperone proteins that can help maintain cellular protein homeostasis, assist in correcting the folding of cellular proteins, and protect organisms from stress when the body is under stress conditions such as temperature changes or bacterial infections. In this study, the HSP10 and HSP40 genes of Eriocheir hepuensis were cloned and named Eh-HSP10 and Eh-HSP40. The results show that the coding sequence length of the HSP10 and HSP40 genes of E. hepuensis was 309 bp and 1191 bp, encoding 102 and 396 amino acids, respectively. The results of protein domain prediction show that Eh-HSP10 has a Cpn10 domain. The Eh-HSP40 protein contains a DnaJ domain, which is characteristic of the HSP40 gene family. The results of qRT-PCR show that the Eh-HSP10 and Eh-HSP40 genes were expressed in different normal tissues, with the highest expression in the heart. Under Vibrio parahaemolyticus stress, the Eh-HSP10 genes peaked at 6 h, and the Eh-HSP40 peaked at 9 h in the hepatopancreas. In the gill, Eh-HSP10 showed a double peak at 24 and 48 h, and the expression of Eh-HSP40 was time-dependent. In the heart, the expression of Eh-HSP10 increased first and then decreased, whereas Eh-HSP40 peaked at 48 h. The results indicate that the Eh-HSP10 and Eh-HSP40 proteins may play a role in protecting E. hepuensis under V. parahaemolyticus infection and that they may be involved in the innate immune response of E. hepuensis against bacteria.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Five NUCLEAR FACTOR-Y subunit B genes in rapeseed (Brassica napus) promote flowering and root elongation in Arabidopsis - Ruixin Fu; Ji Wang; Mengjia Zhou; Xuyang Ren; Jianyang Hua; Mingxiang Liang (Planta, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Analysis of 3D anisotropic characteristics for E-Ex wide-field electromagnetic method - Ji-Feng Zhang; Ji-Ren Liu; Bing Feng; Fu-Xiang Zhang (Applied Geophysics, 2022)

Genome analysis and 2’-fucosyllactose utilization characteristics of a new Akkermansia muciniphila strain isolated from mice feces - Wei Gao; Mengshi Xiao; Ziqiang Gu; Xiaodan Fu; Xinmiao Ren; Ying Yu; Zhemin Liu; Changliang Zhu; Qing Kong; Haijin Mou (Molecular Genetics and Genomics, 2022)

Evaluation of the symbiosis level of the water-energy-food complex system based on the improved cloud model: a case study in Heilongjiang Province - Yabin Fu; Yongtai Ren; Wei Pei (Environmental Science and Pollution Research, 2022)

Comparative Methylome Analysis Reveals Epigenetic Signatures Associated with Growth and Shell Color in the Pacific Oyster, Crassostrea gigas - Chao Tan; Chenyu Shi; Yin Li; Wen Teng; Yongjing Li; Huiru Fu; Liting Ren; Hong Yu; Qi Li; Shikai Liu (Marine Biotechnology, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Spatiotemporally varied extreme precipitation events simultaneously controlled by multiple circulation factors in China's Loess Plateau - Yuling Ren; Jingpeng Zhang; Jinxia Fu; Shouzhang Peng; Zhi Li (International Journal of Climatology, 2022)
The intensive and frequent extreme precipitation events (EPE) greatly contribute to the severe soil loss in China's Loess Plateau, and it is thus essential to understand how and why EPE varies with space and time. Particularly, the combined influence of multiple factors on EPE has rarely been explored. This study analysed the spatiotemporal variability of EPE for 1961–2017 after defining six indices for intensity, frequency, and duration of EPE (R5d, SDII, R90t, R90n, CDD, CWD). We employed 12 atmospheric circulation factors to determine their combined effects on EPE on different time scales over time by the multiple wavelet coherence. The EPE indices spatially varied with obvious southeast‐northwest gradients. Averaged across the whole plateau, SDII, R90t, and R90n increased insignificantly, while R5d, CDD, and CWD decreased insignificantly. In addition, the change trend had spatial variations with most wet EPE indices increasing in the north and the southernmost areas and decreasing in the middle‐south areas. SDII, R90t, and R90n at 68%, 66%, and 53% of stations tended to increase, respectively, and R5d, CDD, and CWD decreased at 66%, 70%, and 77% of stations, respectively. The temperature had a greater correlation with the duration of EPE in summer and on the intensity and frequency of EPE in winter. El Niño‐Southern Oscillation (ENSO), Pacific North American teleconnection pattern (PNA), ENSO‐Arctic Oscillation (AO), and ENSO‐AO‐PNA were found to be the main factors influencing EPE individually or simultaneously. This study provides technical support for the identification of combined effects of multiple factors, and the results are helpful for regional environmental management. Specific to the Loess Plateau, the identified individual or multiple factors can be used to project future changes in EPE, and the more frequent and intensive EPE in some regions may increase the difficulty in future soil loss control.

A Review on Hydraulic Fracture Height Growth for Layered Formation - Peng Tan; Jiawei Kao; Fushan Cheng; Yiliu Sun; Shihao Fu; Lejia Ren (Geotechnical and Geological Engineering, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Investigation of VOC characteristics, source analysis, and chemical conversions in a typical petrochemical area through 1-year monitoring and emission inventory - Guimei Qin; Song Gao; Qingyan Fu; Shuang Fu; Haohao Jia; Qingrui Zeng; Linping Fan; Huarui Ren; Jinping Cheng (Environmental Science and Pollution Research, 2022)

Differences in Rice Productivity and Growth Attributes Under Different Paddy-Upland Cropping Systems - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Wanjun Ren (International Journal of Plant Production, 2022)

Rapid triage for ischemic stroke: a machine learning-driven approach in the context of predictive, preventive and personalised medicine - Yulu Zheng; Zheng Guo; Yanbo Zhang; Jianjing Shang; Leilei Yu; Ping Fu; Yizhi Liu; Xingang Li; Hao Wang; Ling Ren; Wei Zhang; Haifeng Hou; et al. (EPMA Journal, 2022)
Background Recognising the early signs of ischemic stroke (IS) in emergency settings has been challenging. Machine learning (ML), a robust tool for predictive, preventive and personalised medicine (PPPM/3PM), presents a possible solution for this issue and produces accurate predictions for real-time data processing. Methods This investigation evaluated 4999 IS patients among a total of 10,476 adults included in the initial dataset, and 1076 IS subjects among 3935 participants in the external validation dataset. Six ML-based models for the prediction of IS were trained on the initial dataset of 10,476 participants (split participants into a training set [80%] and an internal validation set [20%]). Selected clinical laboratory features routinely assessed at admission were used to inform the models. Model performance was mainly evaluated by the area under the receiver operating characteristic (AUC) curve. Additional techniques—permutation feature importance (PFI), local interpretable model-agnostic explanations (LIME), and SHapley Additive exPlanations (SHAP)—were applied for explaining the black-box ML models. Results Fifteen routine haematological and biochemical features were selected to establish ML-based models for the prediction of IS. The XGBoost-based model achieved the highest predictive performance, reaching AUCs of 0.91 (0.90–0.92) and 0.92 (0.91–0.93) in the internal and external datasets respectively. PFI globally revealed that demographic feature age, routine haematological parameters, haemoglobin and neutrophil count, and biochemical analytes total protein and high-density lipoprotein cholesterol were more influential on the model’s prediction. LIME and SHAP showed similar local feature attribution explanations. Conclusion In the context of PPPM/3PM, we used the selected predictors obtained from the results of common blood tests to develop and validate ML-based models for the diagnosis of IS. The XGBoost-based model offers the most accurate prediction. By incorporating the individualised patient profile, this prediction tool is simple and quick to administer. This is promising to support subjective decision making in resource-limited settings or primary care, thereby shortening the time window for the treatment, and improving outcomes after IS.

Fiber connectivity density mapping in end-stage renal disease patients: a preliminary study - Chi Ma; Xinghai Jiang; Yande Ren; Gaojie Gu; Airong Fu; Chengjian Wang; Peirui Bai; Tong Zhou; Shanshan Qin; Shengli Fu (Brain Imaging and Behavior, 2022)

Overexpression of a putative 12-oxophytodienoate reductase gene, EpOPR1, enhances acetylshikonin production in Echium plantagineum - Jiangyan Fu; Ran Ren; Suo Jin; Rongjun Fang; Zhongling Wen; Minkai Yang; Xuan Wang; Bao Liu; Tongming Yin; Guihua Lu; Yonghua Yang; Jinliang Qi (In Vitro Cellular & Developmental Biology - Plant, 2022)

Correction to: High‑Throughput MicroRNA and mRNA Sequencing Reveals that MicroRNAs may be Involved in Peroxidase‑Mediated Cold Tolerance in Potato - Chongchong Yan; Qianqian Wang; Nan Zhang; Yuying Fu; Gang Wu; Xueqiang Ren; Bingjie Xue; Xiyu Liu; Zhihong Xu; Huajun Liao (Plant Molecular Biology Reporter, 2022)

Correction to: Chitosan‑based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu‑Wei Huang; Fang‑Ching Yeh; You‑Ren Ji; Ying‑Fu Su; Ying‑shih Su; Ming‑Hsien Chiang; Shian‑Chiuan Tzeng; Chien‑Yao Fu; Aristine Cheng; Yung‑Chih Wang; Yi‑Tzu Lee (Drug Delivery and Translational Research, 2022)

An autopolyploid-suitable polyBSA-seq strategy for screening candidate genetic markers linked to leaf blight resistance in sugarcane - Zhoutao Wang; Hui Ren; Chao Pang; Guilong Lu; Fu Xu; Wei Cheng; Youxiong Que; Liping Xu (Theoretical and Applied Genetics, 2022)

Risk analysis and influencing factors of drought and flood disasters in China - Wei Pei; Cuizhu Tian; Qiang Fu; Yongtai Ren; Tianxiao Li (Natural Hazards, 2022)

Enhancing the production of physiologically active vitamin D3 by engineering the hydroxylase CYP105A1 and the electron transport chain - Bing Fu; Qian Ren; Jian Ma; Qingwei Chen; Qili Zhang; Ping Yu (World Journal of Microbiology and Biotechnology, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Advances in the Global Distribution, Chemical Constituents, and Pharmacology of Hippocampus, a Traditional Marine Chinese Medicine - Xinhai Cui; Xiangfeng Zhao; Jintong Li; Ziwei Li; Xia Ren; Yangang Zhao; Xianjun Fu; Xiuxue Li (Frontiers in Marine Science, 2021)
Hippocampus is an important traditional marine Chinese medicinal resource that has been used to warm and tonify kidney yang in the clinic for a long time in China. Modern pharmacological studies show that its active ingredients display a wide range of pharmacological activities associated with the kidney, such as anti-inflammation, antioxidation, antitumor, and neuroprotective effects. Herein, we systematically summarize and analyze the research progress on the resource distribution, active ingredients, pharmacological activities, and clinical application of Hippocampus . First, the species and worldwide distribution of Hippocampus were assessed to clarify the existing resources, and the results showed that 44 species of Hippocampus have been found in 159 countries and regions worldwide. Then, based on the analysis of 16 kinds of active ingredients and extraction methods, the relationship between the ingredient extraction and pharmacological activities of Hippocampus was revealed. This review may provide a foundation for further research on the potential active ingredients and mechanisms of Hippocampus . In addition, the research status of traditional prescriptions containing Hippocampus was evaluated. The results implied that research on Hippocampus is still in its infancy, and the mechanism and material basis of its efficacy have not been clarified. This paper should provide directions for further studies on Hippocampus .

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Genome sequence analysis of Cronobacter phage PF-CE2 and proposal of a new species in the genus Pseudotevenvirus - Mengshi Xiao; Xinmiao Ren; Ying Yu; Han Sun; Haijin Mou; Xiaodan Fu (Archives of Virology, 2021)

Estrogen prevents cellular senescence and bone loss through Usp10-dependent p53 degradation in osteocytes and osteoblasts: the role of estrogen in bone cell senescence - Yu Wei; Jiayao Fu; Wenjing Wu; Pengfei Ma; Le Ren; Junhua Wu (Cell and Tissue Research, 2021)

The “8·21” rainfall-induced Zhonghaicun landslide in Hanyuan County of China: surface features and genetic mechanisms - Fei Ye; Wen-Xi Fu; Hong-Fu Zhou; Yue Liu; Ren-Ji Ba; Shuang Zheng (Landslides, 2021)

Two metabolites isolated from endophytic fungus Coniochaeta sp. F-8 in Ageratina adenophora exhibit antioxidative activity and cytotoxicity - Jie Fu; Liwen Hu; Zhen Shi; Wei Sun; Dong Yue; Ya Wang; Xiaoping Ma; Zhihua Ren; Zhicai Zuo; Guangneng Peng; Zhijun Zhong; Junliang Deng; et al. (Natural Product Research, 2021)

High-Throughput MicroRNA and mRNA Sequencing Reveals that MicroRNAs may be Involved in Peroxidase-Mediated Cold Tolerance in Potato - Huajun Liao; Qianqian Wang; Nan Zhang; Yuying Fu; Gang Wu; Xueqiang Ren; Bingjie Xue; Xiyu Liu; Zhihong Xu; Chongchong Yan (Plant Molecular Biology Reporter, 2021)

RNA-binding protein Hfq plays a vital role in cellulose decomposition throughout affecting cellulase gene expression - Xingtao Yang; Mengyao Dong; Ziyao Zhou; Lei Deng; Cao Deng; Haifeng Liu; Zhijun Zhong; Hualin Fu; Zhihua Ren; Yanchun Hu; Liuhong Shen; Yi Geng; et al. (Biotechnology Letters, 2021)

Chitosan-based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu-Wei Huang; Fang-Ching Yeh; You-Ren Ji; Ying-Fu Su; Ying-shih Su; Ming-Hsien Chiang; Shian-Chiuan Tzeng; Chien-Yao Fu; Aristine Cheng; Yung-Chih Wang; Yi-Tzu Lee (Drug Delivery and Translational Research, 2021)

A survey of chloramphenicol residues in aquatic products of Shenzhen, South China - Lan Luo; Shaoyou Lu; Chengpeng Huang; Fu Wang; Yan Ren; He Cao; Qihui Lin; Zhiqiang Tan; Xiaodong Wen (Food Additives & Contaminants: Part A, 2021)

A search method for probabilistic critical slip surfaces with arbitrary shapes and its application in slope reliability analysis - Yibiao Liu; Weizhong Ren; Chenchen Liu; Guijun Fu; Wenhui Xu; Simin Cai (Natural Hazards, 2021)

Laboratory investigation on calcium nitrate induced coupling reactions between nitrogen, phosphorus, sulfur, and metals in contaminated sediments - Juan Lin; Zhen Fu; Shiming Ding; Mingyin Ren; Shuaishuai Gao (Environmental Science and Pollution Research, 2021)

Land Use/Cover Change and Its Policy Implications in Typical Agriculture-forest Ecotone of Central Jilin Province, China - Yulin Dong; Zhibin Ren; Yao Fu; Ran Yang; Hongchao Sun; Xingyuan He (Chinese Geographical Science, 2021)

Role and application of quorum sensing in anaerobic ammonium oxidation (anammox) process: A review - Quan Zhang; Nian-Si Fan; Jin-Jin Fu; Bao-Cheng Huang; Ren-Cun Jin (Critical Reviews in Environmental Science and Technology, 2021)

Soil bacterial communities vary with grassland degradation in the Qinghai Lake watershed - Ze Ren; Zhaomin Wang; Ying Wang; Panpan Ma; Decao Niu; Hua Fu; James J. Elser (Plant and Soil, 2021)

Transcriptomic and metabolomic analyses of non-structural carbohydrates in red maple leaves - Xiaoyu Lu; Zhu Chen; Xinyi Deng; Mingyuan Gu; Zhiyong Zhu; Jie Ren; Songling Fu (Functional & Integrative Genomics, 2021)

Different effects of canopy and understory nitrogen addition on soil organic carbon and its related processes in a subtropical forest - Xiaofei Lu; Wendan Ren; Enqing Hou; Songbo Tang; Lingling Zhang; Zhanfeng Liu; Yongbiao Lin; Shenglei Fu; Dazhi Wen; Yuanwen Kuang (Journal of Soils and Sediments, 2021)

Expression and function of WNT4 involved in larvae development and limb regeneration in Portunus trituberculatus - Zhiming Ren; Yuanyuan Fu; Lei Liu; Xiao Liu; Chunlin Wang (Journal of Oceanology and Limnology, 2021)

Planting models and mulching material strategies to reduce bundle sheath cell leakage and improve photosynthetic capacity and maize production in semi-arid climate - Lixin Fu; Honglei Ren; Shengjun Xu; Shaoxin Hu; Jianfei Yang; Chang Liu (Environmental Science and Pollution Research, 2021)

Air pollution characteristics, health risks, and source analysis in Shanxi Province, China - Hui Song; Huimin Zhuo; Sanze Fu; Lijun Ren (Environmental Geochemistry and Health, 2021)

Residual nitrogen from preceding garlic crops is important for double-cropped rice - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Nkrumah Malik; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Long-term follow-up of optic neuropathy in chronic low cerebrospinal fluid pressure monkeys: the Beijing Intracranial and Intraocular Pressure (iCOP) Study - Jing Li; Diya Yang; Jacky M. K. Kwong; Jidi Fu; Ruowu Hou; Jost B. Jonas; Huaizhou Wang; Zheng Zhang; Weiwei Chen; Zhen Li; Jinghong Sang; Xiaobin Xie; et al. (Science China Life Sciences, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Growth and Distribution of Amphioctopus fangsiao (d’Orbigny, 1839–1841) in Haizhou Bay, Yellow Sea - Yumeng Pang; Yongjun Tian; Caihong Fu; Yiping Ren; Rong Wan (Journal of Ocean University of China, 2020)

Semi-empirical prediction method for monthly precipitation prediction based on environmental factors and comparison with stochastic and machine learning models - Huihui Zhang; Hugo A. Loáiciga; Fu Ren; Qingyun Du; Da Ha (Hydrological Sciences Journal, 2020)

Next-generation sequencing and single-cell RT-PCR reveal a distinct variable gene usage of porcine antibody repertoire following PEDV vaccination - Ren Li; Fang Fu; Li Feng; PingHuang Liu (Science China Life Sciences, 2020)

Examination of a coupling coordination relationship between urbanization and the eco-environment: a case study in Qingdao, China - Sanze Fu; Huimin Zhuo; Hui Song; Jianchun Wang; Lijun Ren (Environmental Science and Pollution Research, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Experimental Investigation on Vortex-Induced Vibration of a Flexible Pipe under Higher Mode in an Oscillatory Flow - Haojie Ren; Mengmeng Zhang; Jingyun Cheng; Peimin Cao; Yuwang Xu; Shixiao Fu; Chang Liu (Journal of Marine Science and Engineering, 2020)
Different from the previous studies of the vortex-induced vibration (VIV) dominated by first mode of flexible pipe in an oscillatory flow, the features of a higher mode dominated are experimentally investigated in the ocean basin. The flexible pipe is forced to harmonically oscillate with different combinations of a period and amplitude. The design dominant mode consists of first and second modes under the maximum reduced velocity (VR) of approximately 5.5 with a KC number ranging from 22 to 165. The VIV responses between only the excited first mode and the excited higher mode are compared and studied using displacement reconstruction and wavelet transform methods. The discrepancies of spatial and temporal response between smaller and larger KC numbers (KC = 56 and 121) are first observed. The strong alternate mode dominance and lock-in phenomena occur in the case of larger KC numbers, while they cannot be observed in the case of smaller KC numbers under higher modes. The VIV dominant frequency in the in-line (IL) direction is found to be always triple the oscillatory flow frequency and not twice that in the cross flow (CF) direction. The dominant frequency in the CF direction can be predicted by the Strouhal law, and the Strouhal number is approximately 0.18 under VR = 5.5, which is not affected by the excited mode. Moreover, differences of response motion trajectory are also revealed in this paper. The present work improves the basic understanding of vessel motion induced VIV and provides helpful references for developing prediction methods of VIV in an oscillatory flow.

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Response of individual sizes and spatial patterns of Deyeuxia angustifolia to increasing water level gradient in a freshwater wetland - Heng Ren; Fu-xi Shi; Rong Mao; Yue-dong Guo; Wen-zhi Zhao (Environmental Science and Pollution Research, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Soil bacteria and fungi respond differently to plant diversity and plant family composition during the secondary succession of abandoned farmland on the Loess Plateau, China - Zekun Zhong; Xinyi Zhang; Xing Wang; Shuyue Fu; Shaojun Wu; Xuqiao Lu; Chengjie Ren; Xinhui Han; Gaihe Yang (Plant and Soil, 2020)

Development of Nitrogen Fertilizer Topdressing Model for Winter Wheat Based on Critical Nitrogen Dilution Curve - Yang Wang; Youliang Ye; Yufang Huang; Yanan Zhao; Ning Ren; Wen Fu; Songhua Yue (International Journal of Plant Production, 2020)

Source analysis and risk assessment of heavy metals in development zones: a case study in Rizhao, China - Huimin Zhuo; Xu Wang; Heng Liu; Sanze Fu; Hui Song; Lijun Ren (Environmental Geochemistry and Health, 2020)

Nonlinear optimal moisture perturbations as excitation of primary MJO events in a hybrid coupled climate model - Yuntao Wei; Hong-Li Ren; Mu Mu; Joshua-Xiouhua Fu (Climate Dynamics, 2020)
Although the moisture feedback has been well known to be essential in the Madden–Julian Oscillation (MJO) dynamics, whether its pre-moistening effect plays a key role in exciting the onset of primary MJO events, as has been confirmed in the successive initiation, remains elusive. In this study, using a hybrid coupled climate model that has a good fidelity in simulating the intraseasonal variability, we develop a new framework of methodology to investigate the nonlinear excitation of primary MJO event, of which the key achievement is the successful implementation of the conditional nonlinear optimal perturbation (CNOP). In an application of this new framework, the CNOP-type moisture perturbations are calculated for the pre-chosen non-MJO reference states and generally favor a moistening in the equatorial region while drying in the poleward. Comparisons of the model simulation with observation give credibility to the existence of moisture signals several weeks before some primary MJO events. A suite of numerical experiments confirms that the CNOPs of moisture can contribute to the excitation and propagation of strong primary MJO events while random perturbations cannot. The moisture budget analysis further reveals the central importance of the horizontal moisture advection, especially the nonlinearly upscaled moisture transports associated with the high-frequency disturbances on the quasi-3–4-day and 6–8-day synoptic time scales, in supporting the nonlinear excitation of the primary MJO events. The subgrid-scale processes of evaporation, condensation and eddy transport of moisture are found to be critical for the pre-moistening effect in the boundary layer as well. This study directly supports the vital importance of the moisture perturbations, which are characterized by a particular pattern concentrated at low levels, to the nonlinear growth and propagation of the primary MJO events.

Does pipelaying method affect the development of pipeline geohazards and maintenance cost? A case study of Zhongxian-Wuhan gas pipeline, China - Qinglu Deng; Min Fu; Xingwei Ren (Bulletin of Engineering Geology and the Environment, 2020)

Evolution and Current Applications of Robot-Assisted Fracture Reduction: A Comprehensive Review - Jing-Xin Zhao; Changsheng Li; Hongliang Ren; Ming Hao; Li-Cheng Zhang; Pei-Fu Tang (Annals of Biomedical Engineering, 2020)

Physiological functions of urea transporter B - Lanying Yu; Tiantian Liu; Shuang Fu; Li Li; Xiaoping Meng; Xin Su; Zhanfeng Xie; Jiayan Ren; Yan Meng; Xuejiao Lv; Yanwei Du (Pflügers Archiv - European Journal of Physiology, 2019)
Urea transporters (UTs) are membrane proteins in the urea transporter protein A (UT-A) and urea transporter protein B (UT-B) families. UT-B is mainly expressed in endothelial cell membrane of the renal medulla and in other tissues, including the brain, heart, pancreas, colon, bladder, bone marrow, and cochlea. UT-B is responsible for the maintenance of urea concentration, male reproductive function, blood pressure, bone metabolism, and brain astrocyte and cardiac functions. Its deficiency and dysfunction contribute to the pathogenesis of many diseases. Actually, UT-B deficiency increases the sensitivity of bladder epithelial cells to apoptosis triggers in mice and UT-B-null mice develop II-III atrioventricular block and depression. The expression of UT-B in the rumen of cow and sheep may participate in digestive function. However, there is no systemic review to discuss the UT-B functions. Here, we update research approaches to understanding the functions of UT-B.

Evaluation of Stripe Rust Resistance in Hungarian Winter Wheat Cultivars in China - D. Huang; H. Zhang; M. Tar; Y. Zhang; F. Ni; J. Ren; D. Fu; L. Purnhauser; J. Wu (Cereal Research Communications, 2019)

Functional zoning and space management of Three-River-Source National Park - Mengdi Fu; Junliang Tian; Yueheng Ren; Junsheng Li; Weiwei Liu; Yanpeng Zhu (Journal of Geographical Sciences, 2019)

Soil heavy metal contamination and health risk assessment associated with development zones in Shandong, China - Huimin Zhuo; Sanze Fu; Heng Liu; Hui Song; Lijun Ren (Environmental Science and Pollution Research, 2019)

Characterization of the complete chloroplast genomes of the endangered shrub species Prunus mongolica and Prunus pedunculata (Rosales: rosaceae) - Yi-Zhong Duan; Ye-Hua Shen; Fu-Ren Kang; Jian-Wu Wang (Conservation Genetics Resources, 2019)

Evaluating sea-level rise vulnerability assessments in the USA - Xinyu Fu; Bowen Sun; Kathryn Frank; Zhong-Ren Peng (Climatic Change, 2019)

Cascading influences of grassland degradation on nutrient limitation in a high mountain lake and its inflow streams - Ze Ren; Decao Niu; Panpan Ma; Ying Wang; Hua Fu; James J. Elser (Ecology, 2019)
Nitrogen (N) and phosphorus (P) are key growth‐limiting nutrients for organisms and their absolute and relative supplies regulate the structure and function of ecosystems. Landcover changes lead to modifications of terrestrial biogeochemistry, consequently influencing aquatic nutrient conditions. This study sought to evaluate the potential impacts of grassland degradation on nutrient availability and nutrient limitation in the Qinghai Lake (China) and its inflow streams. We sampled nutrient concentrations and tested stream nutrient limitation by conducting nutrient diffusing substrata ( NDS ) bioassays in streams flowing through subbasins with different grassland status. To test nutrient limitation and the responses of lake phytoplankton to stream inflows, bioassays were conducted by adding different nutrients (N, P, and joint NP ) as well as water from different streams to lake water with phytoplankton, respectively. In general, N concentrations as well as N:P ratios decreased while P concentrations increased with decreased normalized difference vegetation index ( NDVI , an index of vegetation status), especially in September, suggesting that grassland degradation (low NDVI ) has the potential to differentially decrease N availability and increase P availability in streams. Consistent with this, relative responses ( RR ) of stream periphyton to P and combined NP enrichments in the NDS bioassays decreased with stream P concentrations while increased with stream water N:P ratios. Lake phytoplankton responded strongly to P and combined NP addition indicating strong P‐limitation of lake phytoplankton. RR of lake phytoplankton to stream water decreased with nitrate concentration and N:P ratios in stream water and increased with the concentrations of ammonium, total phosphorus, and soluble reactive phosphorus, indicating that stream water with higher P but lower N and N:P from degraded subcatchments is associated with increased impact on P‐limited Lake phytoplankton. Overall, this study suggests that grassland degradation has the potential to differentially influence the nutrients delivered to streams with substantial increases in P but decreases in N and N:P, alleviating P limitation of stream periphyton and, ultimately, stimulating P‐limited phytoplankton growth in the lake.

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Whole-exome sequencing identified four loci influencing craniofacial morphology in northern Han Chinese - Wei Wu; Guiying Zhai; Zejun Xu; Bo Hou; Dahua Liu; Tianyi Liu; Wei Liu; Fu Ren (Human Genetics, 2019)

The China Multi-Model Ensemble Prediction System and Its Application to Flood-Season Prediction in 2018 - Hong-Li Ren; Yujie Wu; Qing Bao; Jiehua Ma; Changzheng Liu; Jianghua Wan; Qiaoping Li; Xiaofei Wu; Ying Liu; Ben Tian; Joshua-Xiouhua Fu; Jianqi Sun (Journal of Meteorological Research, 2019)

Vascularized composite allograft rejection is delayed by infusion of IFN-γ-conditioned BMSCs through upregulating PD-L1 - Yaojun Wang; Yunfeng Xi; Fu Han; Yang Liu; Na Li; Zhongliang Ren; Jiajie Xue; Lei Guo; Dahai Hu (Cell and Tissue Research, 2019)

Impacts of climate warming on maximum aviation payloads - Diandong Ren; Robert E. Dickinson; Rong Fu; Janet F. Bornman; Weidong Guo; Song Yang; Lance M. Leslie (Climate Dynamics, 2019)

Ethical considerations of cellular immunotherapy for cancer - Sang-sang Ren; Jing-wen Deng; Meng Hong; Yan-li Ren; Hai-jing Fu; Yan-ning Liu; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Simplified method for estimating throw radius of rotating sprinklers on sloping land - Lin Zhang; Boyang Fu; Xin Hui; Naiwang Ren (Irrigation Science, 2018)

A new abietane diterpenoid from the roots of Tripterygium regelii - Zhi-Hua Jiang; Yan-Ping Liu; Miao He; Jin-Hua Zhao; Ting-Ting Wang; Xing-Yang Feng; Hao Yue; Ren-Bo An; Yan-Hui Fu (Natural Product Research, 2018)

Polychlorinated biphenyls and their hydroxylated metabolites in the serum of e-waste dismantling workers from eastern China - Shengtao Ma; Guofa Ren; Xiangying Zeng; Zhiqiang Yu; Guoying Sheng; Jiamo Fu (Environmental Geochemistry and Health, 2018)

Two thymol derivatives from the flower buds of Lonicera japonica and their antibacterial activity - Jing Yang; Yong-Chao Li; Xiu-Ren Zhou; Xin-Juan Xu; Qing-Yun Fu; Chang-Zhong Liu (Natural Product Research, 2018)

Three different downstream fates of the boreal-summer MJOs on their passages over the Maritime Continent - Joshua-Xiouhua Fu; Wanqiu Wang; Hong-Li Ren; Xiaolong Jia; Toshiaki Shinoda (Climate Dynamics, 2018)

miR-128-3p regulates 3T3-L1 adipogenesis and lipolysis by targeting Pparg and Sertad2 - Chen Chen; Yuan Deng; Xionggui Hu; Huibo Ren; Ji Zhu; Shengcai Fu; Julan Xie; Yinglin Peng (Journal of Physiology and Biochemistry, 2018)

A new polyoxygenated cyclohexene derivative from Artabotrys hainanensis - Jin-Ying Tang; Yan-Ping Liu; Peng-Kun Ju; Xiu-Lan Luo; Zhi-Jie Zhang; Peng Ren; Liang Lai; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2018)

Plantar blood flow response to accumulated pressure stimulus in diabetic people with different peak plantar pressure: a non-randomized clinical trial - Fang Pu; Weiyan Ren; Hongyuan Fu; Xuan Zheng; Min Yang; Yih-Kuen Jan; Yubo Fan (Medical & Biological Engineering & Computing, 2018)

The role of heat shock protein 70 in oxidant stress and inflammatory injury in quail spleen induced by cold stress - Jiayi Ren; Chunpeng Liu; Dan Zhao; Jing Fu (Environmental Science and Pollution Research, 2018)

Does planned retreat matter? Investigating land use change under the impacts of flooding induced by sea level rise - Jie Song; Xinyu Fu; Ruoniu Wang; Zhong-Ren Peng; Zongni Gu (Mitigation and Adaptation Strategies for Global Change, 2018)

Molecular characterization of a stress-induced NAC gene, GhSNAC3, from Gossypium hirsutum - Zhan-Ji Liu; Fei Li; Li-Guo Wang; Ren-Zhong Liu; Jun-Jun Ma; Ming-Chuan Fu (Journal of Genetics, 2018)

Transdimensional Bayesian inversion of time-domain airborne EM data - Zong-Hui Gao; Chang-Chun Yin; Yan-Fu Qi; Bo Zhang; Xiu-Yan Ren; Yong-Chao Lu (Applied Geophysics, 2018)

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

Microarray expression profiling and co-expression network analysis of circulating LncRNAs and mRNAs associated with neurotoxicity induced by BPA - Wei Pang; Fu-Zhi Lian; Xue Leng; Shu-min Wang; Yi-bo Li; Zi-yu Wang; Kai-ren Li; Zhi-xian Gao; Yu-gang Jiang (Environmental Science and Pollution Research, 2018)

Screen for Inhibitors of Crystal Growth to Identify Desirable Carriers for Amorphous Solid Dispersions Containing Felodipine - Jinping Fu; Lin Cui; Congbin Yang; Hui Xiong; Guobin Ren; Xingyuan Ma; Qiufang Jing; Fuzheng Ren (AAPS PharmSciTech, 2018)

3D forward modeling and response analysis for marine CSEMs towed by two ships - Bo Zhang; Chang-Chun Yin; Yun-He Liu; Xiu-Yan Ren; Yan-Fu Qi; Jing Cai (Applied Geophysics, 2018)

Soil physical properties response to tillage practices during summer fallow of dryland winter wheat field on the Loess Plateau - Jian-Fu Xue; Ai-Xia Ren; Hui Li; Zhi-Qiang Gao; Tian-Qing Du (Environmental Science and Pollution Research, 2018)

Influence of phosphorous fertilization on copper phytoextraction and antioxidant defenses in castor bean (Ricinus communis L.) - Guoyong Huang; Muhammad Shahid Rizwan; Chao Ren; Guangguang Guo; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Science and Pollution Research, 2018)

Familial Parkinson’s Disease-Associated L166P Mutant DJ-1 is Cleaved by Mitochondrial Serine Protease Omi/HtrA2 - Kai Fu; Yanfei Wang; Dongkai Guo; Guanghui Wang; Haigang Ren (Neuroscience Bulletin, 2017)

Morphological and molecular divergence of Rhipicephalus turanicus tick from Albania and China - Hong-Yu Li; Shan-Shan Zhao; Sándor Hornok; Róbert Farkas; Li-Ping Guo; Chuang-Fu Chen; Ren-Fu Shao; Ji-Zhou Lv; Yuan-Zhi Wang (Experimental and Applied Acarology, 2017)

Synergistic effects of temperature and humidity on the symptoms of COPD patients - Zhe Mu; Pei-Li Chen; Fu-Hai Geng; Lei Ren; Wen-Chao Gu; Jia-Yun Ma; Li Peng; Qing-Yun Li (International Journal of Biometeorology, 2017)

The Physicochemical Investigation of 17β-Estradiol Crystalline Prepared by In Situ pH-Dependent Solubility Technique with Polyvinylpyrrolidone - Hui Xiong; Jinping Fu; Hanjing Sun; Enfu Wang; Yunhui Ding; Guobin Ren; Qiufang Jing; Fuzheng Ren (AAPS PharmSciTech, 2017)

Chronological constraints on the tectonic evolution of the Chinese Tianshan Orogen through detrital zircons from modern and palaeo-river sands - Rong Ren; Shu-Wei Guan; Bao-Fu Han; Li Su (International Geology Review, 2017)

Black-and-white snub-nosed monkey (Rhinopithecus bieti) feeding behavior in a degraded forest fragment: clues to a stressed population - Zhi-Pang Huang; Matthew B. Scott; Yan-Peng Li; Guo-Peng Ren; Zuo-Fu Xiang; Liang-Wei Cui; Wen Xiao (Primates, 2017)

The increased expression of follicle-stimulating hormone leads to a decrease of fecundity in transgenic Large White female pigs - Kai Jiang; Pan Xu; Wanbo Li; Qiang Yang; Longyun Li; Chuanmin Qiao; Huanfa Gong; Hao Zheng; Zhimin Zhou; Hao Fu; Qiuyan Li; Yuyun Xing; et al. (Transgenic Research, 2017)

IR Spectra of Different O2-Content Hemoglobin from Computational Study: Promising Detector of Hemoglobin Variant in Medical Diagnosis - Su-qin Zhou; Tu-nan Chen; Guang-fu Ji; En-ren Wang (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Hydrogen enhances adaptation of rice seedlings to cold stress via the reestablishment of redox homeostasis mediated by miRNA expression - Sheng Xu; Yilong Jiang; Weiti Cui; Qijiang Jin; Yihua Zhang; Duo Bu; Jiangyan Fu; Ren Wang; Feng Zhou; Wenbiao Shen (Plant and Soil, 2017)

Two new ent -atisane diterpenoids from the whole plants of Euphorbia wallichii - Yi Kuang; Shen-Yuan Fu; Fei Wang; Fu-Cai Ren; Dong-Feng Yang; Sheng-Xiang Yang; Yuan Gao (Natural Product Research, 2017)

Identification and functional analysis of the GTPV bidirectional promoter region - Hui Zhang; Zhihua Sun; Na Zhang; Zhiqiang Li; Pengyan Wang; Qiang Fu; Yan Ren; Xuehua Shao; Yu Zhang; Zhiru Guo; Chuangfu Chen (Archives of Microbiology, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

The integrated impacts of human activities and rising sea level on the saltwater intrusion in the east coast of the Yucatan Peninsula, Mexico - Yujun Deng; Caitlin Young; Xinyu Fu; Jie Song; Zhong-Ren Peng (Natural Hazards, 2017)

Polymorphic microsatellite markers in Taxus chinensis var. mairei (Taxaceae) - WEI FU; ZHI-XIN DU; HE REN; NOPPARAT BUAHOM; HONG-WEI LIU; XIN HUANG (Journal of Genetics, 2016)

What caused the spring intensification and winter demise of the 2011 drought over Texas? - D. Nelun Fernando; Kingtse C. Mo; Rong Fu; Bing Pu; Adam Bowerman; Bridget R. Scanlon; Ruben S. Solis; Lei Yin; Robert E. Mace; John R. Mioduszewski; Tong Ren; Kai Zhang (Climate Dynamics, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Radial propagation of magnetospheric substorm-injected energetic electrons observed using a BD-IES instrument and Van Allen Probes - QiuGang Zong; YiXin Hao; Hong Zou; SuiYan Fu; XuZhi Zhou; Jie Ren; LingHua Wang; ChongJing Yuan; ZhiYang Liu; XiangHong Jia; Lin Quan; Ying Liu; et al. (Science China Earth Sciences, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Molecular characterization of two divergent variants of sugarcane bacilliform viruses infecting sugarcane in China - Sheng-Ren Sun; Mona B. Damaj; Olufemi J. Alabi; Xiao-Bin Wu; T. Erik Mirkov; Hua-Ying Fu; Ru-Kai Chen; San-Ji Gao (European Journal of Plant Pathology, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Zircon U–Pb dating constraints on the crustal melting event around 8 Ma in the eastern Himalayan syntaxis - Ji-Yao Tu; Jian-Qing Ji; Jun-Feng Gong; Quan-Ren Yan; Bao-Fu Han (International Geology Review, 2016)

Persistence Parameter: a Reliable Measurement for Behavioral Responses of Medaka (Oryzias latipes) to Environmental Stress - Li Yin; Haitang Yang; Guiyun Si; Qing Ren; Rongshu Fu; Biao Zhang; Xu Zhang; Xiaoguang Wang; Pingping Qi; Chunlei Xia; Zongming Ren; Tae-Soo Chon; et al. (Environmental Modeling & Assessment, 2016)

Effect of in planta phosphorus on aluminum-induced inhibition of root elongation in wheat - Ji Feng Shao; Jing Che; Rong Fu Chen; Jian Feng Ma; Ren Fang Shen (Plant and Soil, 2015)

ALFF Value in Right Parahippocampal Gyrus Acts as a Potential Marker Monitoring Amyotrophic Lateral Sclerosis Progression: a Neuropsychological, Voxel-Based Morphometry, and Resting-State Functional MRI Study - Wenjia Zhu; Xiaoling Fu; Fang Cui; Fei Yang; Yuting Ren; Xiaoyun Zhang; Xiaolan Zhang; Zhaohui Chen; Li Ling; Xusheng Huang (Journal of Molecular Neuroscience, 2015)

Spectral Characteristics of Tropical Anvils Obtained by Combining TRMM Precipitation Radar with Visible and Infrared Scanner Data - Yuan-Jian Yang; Da-Ren Lu; Yun-Fei Fu; Feng-Jiao Chen; Yu Wang (Pure and Applied Geophysics, 2015)

Improving the forecast precision of river stage spatial and temporal distribution using drain pipeline knowledge coupled with BP artificial neural networks: a case study of Panlong River, Kunming, China - Zhiqiang Xie; Qingyun Du; Fu Ren; Xiaowei Zhang; Sam Jamiesone (Natural Hazards, 2015)

iTRAQ-based quantitative proteomic analysis of longissimus muscle from growing pigs with dietary supplementation of non-starch polysaccharide enzymes - Ji-ze Zhang; Yang Gao; Qing-ping Lu; Ren-na Sa; Hong-fu Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

An Analytic Solution Method for Retrieving Land Surface Temperature from Remotely Sensed Thermal Infrared Imagery - Hongrui Zhao; Hui Ren; Gang Fu (Journal of the Indian Society of Remote Sensing, 2015)

Genetic diversity and association mapping of cadmium tolerance in bermudagrass [Cynodon dactylon (L.) Pers.] - Yan Xie; Xiaoyan Sun; Jing Ren; Jibiao Fan; Yanhong Lou; Jinmin Fu; Liang Chen (Plant and Soil, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Prevalence and Risk Factors for Farmer’s Lung in Greenhouse Farmers: An Epidemiological Study of 5,880 Farmers from Northeast China - Shuo Liu; Donghong Chen; Shuang Fu; Yangang Ren; Lingling Wang; Yibing Zhang; Mingjing Zhao; Xiaoyu He; Xiaoge Wang (Cell Biochemistry and Biophysics, 2015)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

New wheat-rye 5DS-4RS·4RL and 4RS-5DS·5DL translocation lines with powdery mildew resistance - Shulan Fu; Zhenglong Ren; Xiaoming Chen; Benju Yan; Feiquan Tan; Tihua Fu; Zongxiang Tang (Journal of Plant Research, 2014)

Characteristics of Rocky Basin Structure of Yongshu Reef in the Southern South China Sea - Qing-Shan Meng; Ke-Fu Yu; Ren Wang; Yue Qin; Hou-Zhen Wei; Xin-Zhi Wang (Marine Georesources & Geotechnology, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

Muscular tubes of urethra engineered from adipose-derived stem cells and polyglycolic acid mesh in a bioreactor - Ying Wang; Qiang Fu; Ren-Yan Zhao; Chen-Liang Deng (Biotechnology Letters, 2014)

Molecular cytogenetic characteristics of a translocation line between common wheat and Thinopyrum intermedium with resistance to powdery mildew - Xueqin Tang; Dong Shi; Jie Xu; Yinglu Li; Wenjing Li; Zhenglong Ren; Tihua Fu (Euphytica, 2014)

Determinants of public goods investment in rural communities in mountainous areas of Sichuan Province, China - Shi-li Guo; Shao-quan Liu; Ren-fu Luo; Lin-xiu Zhang (Journal of Mountain Science, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

The Late Pleistocene activity of the eastern part of east Kunlun fault zone and its tectonic significance - JunLong Zhang; JinWei Ren; ChangYun Chen; JunDong Fu; PanXin Yang; RenWei Xiong; ChaoZhong Hu (Science China Earth Sciences, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Horizontal gene transfer in plants - Caihua Gao; Xiaodong Ren; Annaliese S. Mason; Honglei Liu; Meili Xiao; Jiana Li; Donghui Fu (Functional & Integrative Genomics, 2014)

Naphtho[1,2-b]furan-4,5-dione inhibits MDA-MB-231 cell migration and invasion by suppressing Src-mediated signaling pathways - Pei-Chien Tsai; Chiao-Lun Chu; Yaw-Syan Fu; Chih-Hua Tseng; Yeh-long Chen; Long-Sen Chang; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2014)

Physiological and Molecular Responses to Salt Stress in Wild Emmer and Cultivated Wheat - Liang Chen; Jing Ren; Haiyan Shi; Xiaodong Chen; Miaomiao Zhang; Yue Pan; Jibiao Fan; Eviatar Nevo; Dongfa Sun; Jinming Fu; Junhua Peng (Plant Molecular Biology Reporter, 2013)

Breed-linked polymorphisms of porcine toll-like receptor 2 (TLR2) and TLR4 and the primary investigation on their relationship with prevention against Mycoplasma pneumoniae and bacterial LPS challenge - Xiaomin Fang; Xiao Liu; Cui Meng; Yanfeng Fu; Xuemin Wang; Bixia Li; Feng Tu; Fang Zhao; Shouwen Ren (Immunogenetics, 2013)

Aluminum tolerance of wheat does not induce changes in dominant bacterial community composition or abundance in an acidic soil - Chao Wang; Xue Qiang Zhao; Rong Fu Chen; Hai Yan Chu; Ren Fang Shen (Plant and Soil, 2013)

Yeast-Incorporated Gallium Attenuates Glucocorticoid-Induced Bone Loss in Rats by Inhibition of Bone Resorption - Zhaozhou Ren; Liqing Yang; Feng Xue; Qingjie Meng; Kejia Wang; Xian Wu; Chao Ji; Teng Jiang; Da Liu; Long Zhou; Jing Zhang; Qin Fu (Biological Trace Element Research, 2013)

Palaeozoic multiphase magmatism at Barleik Mountain, southern West Junggar, Northwest China: implications for tectonic evolution of the West Junggar - Zhao Xu; Bao-Fu Han; Rong Ren; Yin-Zhang Zhou; Li Su (International Geology Review, 2013)

Nicardipine in the treatment of aneurysmal subarachnoid haemorrhage: a meta-analysis of published data - Ren-qiang Huang; Fu-gang Jiang; Zi-min Feng; Tian-yi Wang (Acta Neurologica Belgica, 2013)

Inducible regulation of GDNF expression in human neural stem cells - ShuYan Wang; Ping Ren; YunQian Guan; ChunLin Zou; LinLin Fu; Yu Zhang (Science China Life Sciences, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Signaling Effects of Nitric Oxide, Salicylic Acid, and Reactive Oxygen Species on Isoeuphpekinensin Accumulation in Euphorbia pekinensis Suspension Cells Induced by an Endophytic Fungal Elicitor - Fu-Kang Gao; Cheng-Gang Ren; Chuan-Chao Dai (Journal of Plant Growth Regulation, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Anti-inﬂammatory effects of active constituents extracted from Chinese medicinal herbs against Propionibacterium acnes - Shiyu Fu; Changlei Sun; Xinyi Tao; Yuhong Ren (Natural Product Research, 2012)

Characterization of transcriptional activation and inserted-into-gene preference of various transposable elements in the Brassica species - Caihua Gao; Meili Xiao; Lingyan Jiang; Jiana Li; Jiaming Yin; Xiaodong Ren; Wei Qian; Ortegón Oscar; Donghui Fu; Zhanglin Tang (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A Comparison Study Between Spring and Summer Fogs in the Yellow Sea-Observations and Mechanisms - Suping Zhang; Man Li; Xiangui Meng; Gang Fu; Zhaopeng Ren; Shanhong Gao (Pure and Applied Geophysics, 2012)

Dual Porosity and Dual Permeability Modeling of Horizontal Well in Naturally Fractured Reservoir - Ren-Shi Nie; Ying-Feng Meng; Yong-Lu Jia; Fu-Xiang Zhang; Xiang-Tong Yang; Xin-Nian Niu (Transport in Porous Media, 2012)

Expression of Eph A molecules during swine embryo implantation - Yanfeng Fu; Jinluan Fu; Qian Ren; Xiao Chen; Aiguo Wang (Molecular Biology Reports, 2012)

Unequal chromosome division and inter-genomic translocation occurred in somatic cells of wheat–rye allopolyploid - Zongxiang Tang; Shulan Fu; Benju Yan; Huaiqiong Zhang; Zhenglong Ren (Journal of Plant Research, 2012)

The Ran-binding protein RanBPM can depress the NF-κB pathway by interacting with TRAF6 - Lan Wang; Chengbo Fu; Yingbin Cui; Yunfei Xie; Yuhe Yuan; Xin Wang; Hong Chen; Bing-Ren Huang (Molecular and Cellular Biochemistry, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Insights into the pH up-shift responsive mechanism of Acidithiobacillus ferrooxidans by microarray transcriptome profiling - Qian Li; Youhua Ren; Guanzhou Qiu; Nuo Li; Hongwei Liu; Zhimin Dai; Xian Fu; Li Shen; Yili Liang; Huaqun Yin; Xueduan Liu (Folia Microbiologica, 2011)

Induction of heme oxygenase-1 with β-CD-hemin complex mitigates cadmium-induced oxidative damage in the roots of Medicago sativa - Guangqing Fu; Liefeng Zhang; Weiti Cui; Yanqin Wang; Wenbiao Shen; Yong Ren; Tianqing Zheng (Plant and Soil, 2011)

Expression of tissue inhibitor of metalloproteinases-3 messenger RNA and protein in porcine endometrium during implantation - Qian Ren; Shu Guan; Jinluan Fu; Aiguo Wang (Molecular Biology Reports, 2011)

Delineation of the translocation of colicin E7 across the inner membrane of Escherichia coli - Yuh-Ren Chen; Tsung-Yeh Yang; Guang-Sheng Lei; Lung-JR Lin; Kin-Fu Chak (Archives of Microbiology, 2011)

Modeling the mudslide aftermath of the 2007 Southern California Wildfires - Diandong Ren; Rong Fu; Lance M. Leslie; Robert E. Dickinson (Natural Hazards, 2011)

COD removal from expanded granular sludge bed effluent using a moving bed biofilm reactor and their microbial community analysis - Bo Fu; Xiaoyi Liao; Rui Liang; Lili Ding; Ke Xu; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2011)

Isolation and characterization of polymorphic microsatellite markers for the ariake icefish (Salanx ariakensis kishinouye) - Juan Hu; Sheng-Jie Ren; Cui-Zhang Fu; Xiao-Ling Gong (Conservation Genetics Resources, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Isolation of rye-specific DNA fragment and genetic diversity analysis of rye genus Secale L. using wheat SSR markers - Shulan Fu; Zongxiang Tang; Zhenglong Ren; Huaiqiong Zhang; Benju Yan (Journal of Genetics, 2010)

Characterization of microbial community in an aerobic moving bed biofilm reactor applied for simultaneous nitrification and denitrification - Bo Fu; Xiaoyi Liao; Lili Ding; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2010)

Transfer to wheat (Triticum aestivum) of small chromosome segments from rye (Secale cereale) carrying disease resistance genes - S. Fu; Z. Tang; Z. Ren; H. Zhang (Journal of Applied Genetics, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

Molecular characterization, expression profile and association analysis with fat deposition traits of the porcine APOM gene - Gang Pan; Yayuan Fu; Bo Zuo; Zhuqing Ren; Dequan Xu; Minggang Lei; Rong Zheng; Yuan-Zhu Xiong (Molecular Biology Reports, 2010)

Potential adenovirus-mediated gene therapy of glioma cancer - Yue-Jun Fu; Jun Du; Ren-Jia Yang; Li-Tian Yin; Ai-Hua Liang (Biotechnology Letters, 2010)

Inter- and intra-genomic transfer of small chromosomal segments in wheat-rye allopolyploids - Shulan Fu; Zongxiang Tang; Zhenglong Ren (Journal of Plant Research, 2010)

Undisturbed Strata Succession Sampling Technology and the Engineering Geological Characteristics of an Atoll in the Southern South China Sea - Qing-Shan Meng; Ren Wang; Ke-Fu Yu; Ming-Jian Hu; Xin-Zhi Wang; Chao Yang (Marine Georesources & Geotechnology, 2009)

Sequence Polymorphism and Evolution of Three Cetacean MHC Genes - Shi Xia Xu; Wen Hua Ren; Shu Zhen Li; Fu Wen Wei; Kai Ya Zhou; Guang Yang (Journal of Molecular Evolution, 2009)

Rapid Evolution of Simple Sequence Repeat Induced by Allopolyploidization - Zongxiang Tang; Shulan Fu; Zhenglong Ren; Yuting Zou (Journal of Molecular Evolution, 2009)

Development and characterization of a new 1BL.1RS translocation line with resistance to stripe rust and powdery mildew of wheat - Tian-Heng Ren; Zu-Jun Yang; Ben-Ju Yan; Huai-Qiong Zhang; Shu-Lan Fu; Zheng-Long Ren (Euphytica, 2009)

The Avoidance Responses of Daphnia magna to the Exposure of Organophosphorus Pesticides in an On-Line Biomonitoring System - Zong-Ming Ren; Zhi-Liang Li; Jin-Miao Zha; Kai-feng Rao; Mei Ma; Zijian Wang; Rong-Shu Fu (Environmental Modeling & Assessment, 2009)

Behavioral Responses of Daphnia Magna to Stresses of Chemicals with Different Toxic Characteristics - Zongming Ren; Zhiliang Li; Mei Ma; Zijian Wang; Rongshu Fu (Bulletin of Environmental Contamination and Toxicology, 2009)

Inhibition of hepatitis B virus replication by small interference RNA induces expression of MICA in HepG2.2.15 cells - Kai-Fu Tang; Min Chen; Jing Xie; Guan-Bin Song; Yi-Song Shi; Qi Liu; Zhe-Chuan Mei; Alexander Steinle; Hong Ren (Medical Microbiology and Immunology, 2009)

Root phosphate exudation and pH shift in the rhizosphere are not responsible for aluminum resistance in rice - Rong Fu Chen; Ren Fang Shen (Acta Physiologiae Plantarum, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Association analysis of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Qian-Fu Gan; Lu-Pei Zhang; Jun-Ya Li; Guan-Yu Hou; Heng-De Li; Xue Gao; Hong-Yan Ren; Jin-Bao Chen; Shang-Zhong Xu (Journal of Applied Genetics, 2008)

Production of a new wheat cultivar with a different 1B.1R translocation with resistance to powdery mildew and stripe rust - Z. Tang; S. Fu; Z. Ren; H. Zhang; Z. Yang; B. Yan; H. Zhang (Cereal Research Communications, 2008)

Differentiation of commercial strains of Agaricus species in China with inter-simple sequence repeat marker - Xue-Juan Guan; Lu Xu; Yan-Chun Shao; Zhuo-Ren Wang; Fu-Sheng Chen; Xin-Chang Luo (World Journal of Microbiology and Biotechnology, 2008)

Secretion of malate and citrate from roots is related to high Al-resistance in Lespedeza bicolor - Xiao Ying Dong; Ren Fang Shen; Rong Fu Chen; Zhao Liang Zhu; Jian Feng Ma (Plant and Soil, 2008)

Effects of land use on phosphorus loss in the hilly area of the Loess Plateau, China - Qinghua Meng; Bojie Fu; Xiaoping Tang; Hongchang Ren (Environmental Monitoring and Assessment, 2008)

Use of geochemical modeling to evaluate the hydraulic connection of aquifers: a case study from Chianan Plain, Taiwan - Hsueh-Yu Lu; Tsung-Kwei Liu; Wen-Fu Chen; Tsung-Ren Peng; Chung-Ho Wang; Meng-Hsun Tsai; Tai-Sheng Liou (Hydrogeology Journal, 2008)

Generation and characterization of two novel low phytate mutations in soybean (Glycine max L. Merr.) - Feng-Jie Yuan; Hai-Jun Zhao; Xue-Liang Ren; Shen-Long Zhu; Xu-Jun Fu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Isolation and characterization of microsatellite loci in Cryptocarya chinensis in lower subtropical China - Zheng-Feng Wang; Gang Li; Sheng-Lei Fu; Hai Ren (Conservation Genetics, 2007)

Identification and chromosomal locations of novel genes for resistance to powdery mildew and stripe rust in a wheat line 101-3 - Zhu Zeng; Tihua Fu; Yuan Tang; Ye Chen; Zhenglong Ren (Euphytica, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Generation and characterization of low phytic acid germplasm in rice (Oryza sativa L.) - Qing-Long Liu; Xiu-Hong Xu; Xue-Liang Ren; Hao-Wei Fu; Dian-Xing Wu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Buckwheat accumulates aluminum in leaves but not in seeds - Ren Fang Shen; Rong Fu Chen; Jian Feng Ma (Plant and Soil, 2006)

Calcium-antagonizing activity of S -petasin, a hypotensive sesquiterpene from Petasites formosanus , on inotropic and chronotropic responses in isolated rat atria and cardiac myocytes - Guei-Jane Wang; Jyh-Fei Liao; Kadon K. Hintz; Chuen-Chao Shi; Chieh-Fu Chen; Wen-Pin Chen; Ming-Jai Su; Yun-Lian Lin; Jun Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Study on the framework system of digital agriculture - Yong Liang; Xiu-shan Lu; De-gui Zhang; Fu Liang; Zhi-bo Ren (Chinese Geographical Science, 2003)

Origin of a large breccia-vein system in the Sanerlin uranium deposit, southern China: a reinterpretation - Jian-Wei Li; Mei-Fu Zhou; Xian-Fu Li; Zi-Jin Li; Zhao-Ren Fu (Mineralium Deposita, 2002)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)